707 Dermal absorption of fluoride and hydrogen ions following topical exposure to hydrofluoric acid - Kilo, Sonja; Dennerlein, Kathrin; Korinth, Gintautas; Göen, Thomas; Drexler, Hans (Occupational and Environmental Medicine 2018, 2018)
Introduction Despite being an extremely hazardous liquid, hydrofluoric acid (HF) is commonly used in industry due to its unique chemical properties. Chemically HF is defined as a ‘weak’ acid but fluoride ions can induce serious systemic toxic effects. Upon contact with low concentrated HF, symptoms such as pain or local lesions may be delayed. The aim of this study was to characterise changes in intradermal pH and dermal fluoride penetration following HF application. Methods A static diffusion cell model was used to study dermal fluoride penetration for 6–72 hour following application of varying amounts of HF (c=5%–50%, 100–160 µl/0.64cm2, 1–10 min.) on human skin (thickness 0.9 or 2.5 mm). Intra- and transdermal amounts of fluoride and intradermal pH were determined. Result Transdermal penetration of fluoride increased exponentially with increasing HF concentration. In addition, penetration increased four-times by extending the exposure time from 1 to 3 min. No further increase was seen with longer HF application (5 and 10 min.). The increased amount of HF penetrated through 0.9 mm compared to 2.5 mm skin within one hour was levelled out at later time points. Intradermal accumulation of fluoride increased dose-dependently but to a lower degree. Intradermal pH dropped with increasing HF concentration and exposure time. Additionally, the lag time between HF application and onset of pH changes decreased with increasing HF concentration and application time. Discussion The results of the present study show that following 3 min. HF application maximal amounts of fluorides seem to have penetrated the skin. The longer lag time in pH drop with lower concentrated HF might explain the delay between HF contact and onset of pai

914 Hydrofluoric acid – effects of skin decontamination on the bioavailability of fluoride - Dennerlein, Kathrin; Hahn, Theresa; Göen, Thomas; Drexler, Hans; Kilo, Sonja (2018)
Introduction After dermal contact to occupational hazardous substances the cleaning of exposed skin areas is an important first aid measure to reduce adverse health effects. Due to possible severe systemic intoxication following dermal exposure to hydrofluoric acid (HF) the decontamination of skin should focus on the inactivation of free fluoride ions. The present ex-vivo study investigated the effects of exposure duration and different antidotes on the potential systemic uptake of fluoride. Methods The transdermal penetration of HF (c=30%) through excised human skin was investigated by using static diffusion cells. After dermal application of the acid (100 µl/0.64 cm2) for 1 min the excess was removed using one dry cotton swab. Subsequently, the skin was cleaned with water, calcium gluconate (CaGl), polyethylene glycol (PEG) 400 or hexafluorine© using a standardised protocol. In a further study, the application time was extended to 3 min to assess the effect of exposure duration. Chemical analyses of fluoride were carried out by GC-MS or via a fluoride-sensitive electrode. Result Extension of the exposure time from 1 to 3 min led to an enhancement in the transdermal penetration of fluoride, however with similar penetration kinetics. At the end of experiments (6 hour) a 7–fold higher fluoride amount was detected in the receptor fluid (16 vs 114 µg). In all test series maximum flux was achieved within the first hour past exposure. Decontamination of the skin reduced the cumulative penetrated amount of fluoride by 28% (PEG 400), 49% (water) and 64% (CaGl/hexafluorine©) compared to control. Discussion The results indicate that the systemic uptake of fluoride ions and therefore possible systemic intoxication after exposure to hydrofluoric acid can be diminished by shortening the exposure duration. Reduction was further increased by decontamination of skin – most by substances which are known to supply the complexation of fluoride ion

A German Model Project for Workplace Health Promotion— Flow of Communication, Information, and Reasons for Non-Participation in the Offered Measures - Lutz, Regina; Fischmann, Wolfgang; Drexler, Hans; Nöhammer, Elisabeth (International Journal of Environmental Research and Public Health, 2022)
Background: Workplace health promotion (WHP) as a part of workplace health management (WHM) was strengthened in German legislature with the Prevention Act of 2015. However, smaller enterprises often do not offer WHM or WHP. Accordingly, a model-project for improving the uptake and implementation, particularly in micro-, small, and medium-sized enterprises (MSMEs) was carried out. The aim of the study was to determine reasons for non-participation in WHP offers and analyze communication issues, both from the employee’s and employer’s perspective. Methods: In total, 21 managers or persons responsible for WHP participated in the first online survey between March and April 2020, and 156 employees responded to the second online survey between June and October 2021. The importance of barriers and communication issues was investigated. Based on a principal component analysis on non-participation, differences regarding sociodemographic variables were analyzed. Results: Most employees knew about the offered measures and that the measures were cost free. There was no significant association between having communicated the offers to the employees and considering them suitable for their needs. Most of the managers or persons responsible for WHP rated the measures as sufficiently varied and allowed staff to take part during working-time. Reasons for non-participation from the managers’ point of view were travel time to the location of the offers, lack of time, and a missing fit between offers and employees’ needs. From the employees’ point of view, workload (including working time) was the main barrier to participation. Conclusions: For the practical implementation of model projects in MSMEs, special attention should be paid to ensuring opportunity to participate, which may be easier with in-house offers.
CRIS-Team Scopus Importer:2022-07-08
Keywords: communication; dissemination; Germany; health promotion; information; medium-sized businesses; microenterprises; occupational health; small businesses

Aluminium in dermatologischen Externa – gibt es für den Einsatz Kontraindikationen aufgrund der systemischen Toxizität? - Drexler, Hans (Dermatologie in Beruf und Umwelt, 2018)
Aluminum is used in antiperspirants for the general population as well as for hyper-hidrosis patients. The debate on the possible toxicity is unsettling not only the population, but also physicians. The neurotoxicity of aluminum was proven in patients after treatment with aluminum containing dialysis fluids. However, the observed encephalopathy with dementia syndrome is not to be equated with dementia of Alzheimer`s disease. It remains unclear, whether the high aluminum concentrations in the brain of Alzheimer's patients are the cause or consequence of the Alzheimer's pathology. In terms of carcinogenicity there is currently no consistent data confirming a link between aluminum and development of breast cancer. The potentially critical effect of aluminum is the neurotoxicity of the central nervous system observed at very high exposures. Even subclinical changes can be prevented in medical applications by compliance to the urine and plasma limit values.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Aluminum; Alzheimer's disease; Biomonitoring; Breast cancer; Neurotoxicity

Antimon-Biomonitoring – Ein Beispiel für die kohärente Arbeitsweise der Arbeitsgruppen der Ständigen Senatskommission zur Prüfung gesundheitsschädlicher Arbeitsstoffe - Weistenhöfer, Wobbeke; Eckert, Elisabeth; Schäferhenrich, Anja; Göen, Thomas; Drexler, Hans; Hartwig, Andrea (60. Jahrestagung der DGAUM 2020, 2020)

Antimon- und Blei-Belastungen durch Schießtraining bei Polizisten - Hiller, Julia; Göen, Thomas; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2018)
Aim: Elevated and potentially hazardous antimony levels in Berlin police officers were reported in spring 2016, giving rise to a critical look at occupational hygiene in police shooting ranges. The study objective was to assess occupational exposure to antimony among police officers in Bavaria by means of biological exposure monitoring. Collective and Method: Levels of antimony and lead were ascertained in male police officers with additional firearms training in two series of examinations between July and December 2016. Initially, a baseline value (n = 8) for antimony in urine was determined and rechecked after a collective firing practice (n = 6). Subsequently, a larger collective (n = 38) was checked for antimony in blood and urine and for lead in blood. Antimony and lead were analysed by ICP-MS. Results: In the first series of examinations the reference value for antimony in urine was exceeded by 25 % of the police officers. Progressive measurements after the practice showed no direct association between the individual antimony exposure and the firearms training. In the second series of examinations antimony in urine and blood exceeded the reference values in 11 % and 21 %, respectively, of the police officers. Additionally, two persons showed elevated lead levels in the blood. Both of them also shoot privately on a regular basis. Conclusions: A direct association between firearms training and internal antimony exposure was not observed. Nevertheless, the exceedance frequency of the reference values indicated a slight increment to the background antimony exposure among the police officers examined. However, since the toxicological and carcinogenic effects of antimony only occur in the event of high-dose exposure, antimony-induced health hazards are not expected at the determined exposure levels. Private shooting which explains the elevated lead levels was identified as a significant factor influencing antimony levels.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Antimony; Firearms training; Lead; Police; Toxicology

Äquivalenzwerte im biologischen Material - Beurteilung bei Exposition gegenüber kanzerogenen Arbeitsstoffen - Drexler, Hans (Zentralblatt für Arbeitsmedizin, Arbeitsschutz und Ergonomie, 2016)
Biological monitoring has been used for many years in workers exposed to carcinogenic substances at the workplace, even though threshold values cannot be evaluated. As a rule, no concentrations can be given for carcinogenic substances where below these limits a danger to health no longer exists; however, for many carcinogenic substances used at the workplace relationships between the external (ambient in air) and internal (biological material) exposure can be derived (exposure equivalents for carcinogenic substances). In this way it can be recognized whether the internal concentrations correspond to the external concentrations or whether an additional exposure (e.g. skin resorption) exists. In Germany a classification into tolerable and acceptable risk-related levels for certain concentrations in air is applied for occupational exposure to carcinogenic hazardous substances at the workplace. These ambient concentrations are assigned to 910 equivalence values in biological material in the technical regulations for hazardous substances (TRGS), by which it can be seen whether the exposure of individual workers lies within the acceptable or still tolerable ranges of these risks. If these risks have not been described or data are lacking to describe the relationship between external and internal exposure, the biological reference values for hazardous workplace substances can be consulted for the assessment. A clear exceedance of the reference value threshold indicates an additional exposure with the accompanying health risks, without being quantifiable. Under these circumstances measures for workplace hygiene should be initiated.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Biomonitoring; Carcinogens; Primary prevention; Reference values; Risk assessment

Arbeiten 4.0: Herausforderung für die arbeitsmedizinische Versorgung in der Zukunft - Drexler, Hans; Nesseler, Thomas (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2016)
CRIS-Team Scopus Importer:2020-05-11

Arbeitsmedizinische Vorsorge für Beschäftigte im Freien, die gegenüber natürlicher UV-Strahlung exponiert sind - Drexler, Hans; Diepgen, T. L.; Letzel, Stephan (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2019)
CRIS-Team Scopus Importer:2019-07-26

Arbeitsmedizin und Facharztausbildung bei Medizinstudierenden - Hollederer, A.; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2018)
Aims: The occupational medicine’s significance increases clearly due to labour market developments in Germany. Information about the medical students’ specialist fields preferences and their influencing factors are essential for recruiting in occupational medicine. Method: In October 2016, 177 out of 208 participating medical students of the university Erlangen-Nuremberg were randomised assigned within the scope of mandatory internships in health services research. At the beginning, every one of the 177 participated voluntarily in an anonymous questionnaire (100% response rate). Results: 93% of the medical students attended the ninth or tenth semester, 58.2% were women. Training as specialists in internal medicine is chosen most often by the students followed by general medicine. 0.6% of the students would have chosen occupational medicine qualification; for 2.8% of the students, it would be worth considering in general. The non-professional factors variety in the job, a work-life-balance and income possibilities were of high importance. For students preferring training as specialists in occupational medicine, team-orientation with other health professionals and between specialist disciplines is especially important. As main reasons against a further training in occupational medicine it was stated the preference of other specialist fields, range of medical methods, a lack of variety in the job and a low level of information. Conclusions: The survey reveals reasons for the choice of occupational medicine qualification and “soft factors” like work-life-balance and team-orientation. It States needs for information about the methods and practice of occupational medicine. A stronger integration of occupational medicine into university education is recommended.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Medical students; Occupational health care; Occupational medicine; Occupational medicine qualification

Arbeitsschutz: Im Netzwerk geht es leichter! Netzwerkarbeit im Modellvorhaben zum Präventionsgesetz - Letzel, Stephan; Lösch, Regina; Fischmann, Wolfgang; Amler, Nadja; Sedlaczek, Sabine; Quittkat, Christine; Drexler, Hans (26. Erfurter Tage: Symposium zur Prävention arbeitsbedingter Gesundheitsgefahren und Erkrankungen, 2019)
Keywords: Arbeitsschutz; Netzwerke; Unternehmen

Arbeits- und Gesundheitsschutz meets betriebliches Gesundheitsmanagement - Fischmann, Wolfgang; Lösch, Regina; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2020)
CRIS-Team Scopus Importer:2024-12-16

Arbeits- und Gesundheitsschutz meets betriebliches Gesundheitsmanagement. Netzwerke für Kleinst-, kleine und mittlere Unternehmen am Beispiel des Modellvorhabens „Gesund arbeiten in Thüringen“ (GAIT) in Thüringen - Fischmann, Wolfgang; Lösch, Regina; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2020)
Keywords: Betriebliches Gesundheitsmanagement; Arbeitsschutz; Gesundheitsschutz; BGM; Unternehmen

Arbeits- und Gesundheitsschutz und Betriebliches Eingliederungsmanagement in Deutschland – Ein systematisches Review zum Umsetzungsstand gesetzlicher Vorgaben - Lösch, Regina; Amler, Nadja; Drexler, Hans (Gesundheitswesen, 2021)
Ziel der Studie: Zur Frage der Umsetzung der gesetzlichen Vorgaben im Arbeits- und Gesundheitsschutz sowie im Betrieblichen Eingliederungsmanagement in Deutschland weisen einzelne Studien aus den letzten Jahren auf teilweise erhebliche Mängel hin. Ziel dieser Übersichtsarbeit ist eine nach Unternehmensgrößen und im Zeitverlauf differenzierte, quantitative Analyse der Erfüllung gesetzlicher Vorgaben im betrieblichen Arbeits- und Gesundheitsschutz sowie im Betrieblichen Eingliederungsmanagement in deutschen Betrieben. Methodik: Es wurde im Oktober 2019 in den Datenbanken PubMed, PsycInfo und WISO eine systematische Literaturrecherche deutsch- und englischsprachiger, repräsentativer Befragungen zu Umsetzungsquoten des Arbeits- und Gesundheitsschutzes sowie des Betrieblichen Eingliederungsmanagements in Deutschland durchgeführt. Ein Update der Studienlage erfolgte im Oktober 2020. Querverweise sowie graue Literatur wurde ebenfalls in die Suche mit einbezogen. Die Bewertung erfolgte durch 2 unabhängige Gutachter. Ergebnisse: Es konnten 16 relevante Studien identifiziert werden. Für die arbeitsmedizinische und sicherheitstechnische Betreuung zeigt sich im Zeitverlauf ein leichter Rückgang der Umsetzungsquoten. Hinsichtlich des Betreuungsmodells lässt sich feststellen, dass mit steigender Mitarbeiterzahl sowohl die Regelbetreuung als auch die bedarfsorientierte Betreuung zunimmt. Im Zeitverlauf und über alle Unternehmensgrößen hinweg steigen die Umsetzungsquoten der Gefährdungsbeurteilung (inkl. Beurteilung psychischer Belastungen) kontinuierlich an. Auch die Umsetzungsquoten der Betriebsbegehungen und des Betrieblichen Eingliederungsmanagements können über die Zeit einen Zuwachs verzeichnen. Schlussfolgerung: Trotz steigender Umsetzungsraten in vielen Teilbereichen des betrieblichen Arbeits- und Gesundheitsschutzes bzw. des Betrieblichen Eingliederungsmanagements innerhalb der letzten 20 Jahre zeigt sich insgesamt, dass eine flächendeckende Umsetzung gesetzlicher Vorgaben noch nicht erreicht ist. Für die zukünftige Konzeption von Studien in diesem Bereich indizieren die Ergebnisse eine Vereinheitlichung der methodischen Vorgehensweisen. Für den Erhalt der Beschäftigungsfähigkeit der Arbeitnehmerinnen und Arbeitnehmer stellt die Umsetzung gesetzlicher Vorgaben eine wichtige Voraussetzung da

Artificial intelligence in melanoma diagnosis: Three scenarios, shifts in competencies, need for regulation, and reconciling dissent between humans and AI - Zoellick, Jan C.; Drexler, Hans; Drexler, Konstantin (Journal for Technology Assessment in Theory and Practice, 2024)
Tools based on machine learning (so-called artificial intelli-gence, AI) are increasingly being developed to diagnose malignant melanoma in dermatology. This contribution discusses (1) three scenarios for the use of AI in different medical settings, (2) shifts in competencies from dermatologists to non-specialists and empowered patients, (3) regulatory frameworks to ensure safety and effectiveness and their consequences for AI tools, and (4) cognitive dissonance and potential delegation of human decision-making to AI. We conclude that AI systems should not replace human medical expertise but play a supporting role. We identify needs for regulation and provide recommendations for action to help all (human) actors navigate safely through the choppy waters of this emerging market. Potential dilemmas arise when AI tools provide diagnoses that conflict with human medical expertise. Reconciling these conflicts will be a major challenge.
CRIS-Team Scopus Importer:2024-03-29
Keywords: artificial intelligence; diagnosis; diagnostic accuracy; melanoma; patient– doctor relationship

Assessment of occupational cancer: important facts to consider - Schmid, Klaus; Drexler, Hans (Deutsche Medizinische Wochenschrift, 2015)
Background | Persons suffering from malignant tumors who had been exposed to carcinogens at their workplace must be compensated if occupational exposure probably caused the disease. However, the assessment of the causes of cancers is particularly difficult.Method | For the evaluation the authors analyzed selectively researched literature and considered publications of the German Social Accident Insurance and legal regulations.Result | Often the quantification of the occupational exposure is not possible. Cumulative exposures neglect important factors, e.g. high peak concentrations. Even in the general population exposure to noxious agents occurs. This raises the question what amount of occupational exposure must be considered as sufficient for compensation and how non-occupational factors, such as genetic susceptibility, should influence the expert's opinion. Syncancerogenetic effects are currently not sufficiently considered in the legal ordinance on occupational diseases.Conclusion | At best, only a very rough estimate of the probability of causation can be stated. If there is insufficient scientific evidence then there is a need of "makeshift" recommendations within the social consensus, which occupational exposure is considered to be relevant for occupational disease. If there are no reliable data on occupational exposure due to failure of the employer, this should not be stacked against the insured.
EVALuna2:9728

Assessment values in biological material for carcinogenic substances by the example of 1,4-dichlorobenzene - Weistenhöfer, Wobbeke; Drexler, Hans; Hartwig, A.; Schmitz-Spanke, Simone (NAUNYN-SCHMIEDEBERGS ARCHIVES OF PHARMACOLOGY, 2020)
CRIS-Team WoS Importer:2020-03-10

Ausrichtung innovativer Versorgungskonzepte für multimorbide Patienten - Grässel, Elmar; Hollederer, Alfons; Drexler, Hans; Kolominsky-Rabas, Peter (Public Health Forum, 2016)
Innovative care concepts for multimorbid patients should be oriented towards eliminating healthcare deficits. These are inappropriate care, different health care providers acting in isolation, failure to involve family caregivers in intervention planning, regional differences in healthcare and failure to take into account the specific care needs of people with dementia. An outline for an innovative healthcare concept is presented.
CRIS-Team Scopus Importer:2020-05-11
Keywords: care concept; dementia; healthcare provision; multimorbid patients; regional differences in healthcare

Auswirkungen von Stuhlmechaniken, Sitzhaltungen und -konzepten bei Büroarbeitsstühlen auf die Rückengesundheit - Ein systematisches Review. - Schäfer, Elisabeth; Petersen, Jens; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2014)

Auszeichnungen für herausragende Leistungen - Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2016)
CRIS-Team Scopus Importer:2020-05-11

Auszeichnungen für herausragende Leistungen - Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2018)
CRIS-Team Scopus Importer:2020-05-11

Basal cell carcinoma risk and solar UV exposure in occupationally relevant anatomic sites: do histological subtype, tumor localization and Fitzpatrick phototype play a role? A population-based case-control study. - Bauer, A.; Haufe, E.; Heinrich, L.; Seidler, A.; Schulze, H. J.; Elsner, P.; Drexler, Hans; Letzel, S.; John, S. M.; Fartasch, M.; Bruening, T.; Dugas-Breit, S.; et al. (Journal of Occupational Medicine and Toxicology, 2020)
Background: A two-fold risk increase to develop basal cell carcinoma was seen in outdoor workers exposed to high solar UV radiation compared to controls. However, there is an ongoing discussion whether histopathological subtype, tumor localization and Fitzpatrick phototype may influence the risk estimates. Objectives: To evaluate the influence of histological subtype, tumor localization and Fitzpatrick phototype on the risk to develop basal cell carcinoma in highly UV-exposed cases and controls compared to those with moderate or low solar UV exposure. Methods: Six hundred forty-three participants suffering from incident basal cell carcinoma in commonly sun-exposed anatomic sites (capillitium, face, lip, neck, dorsum of the hands, forearms outside, décolleté) of a population-based, case-control, multicenter study performed from 2013 to 2015 in Germany were matched to controls without skin cancer. Multivariate logistic regression analysis was conducted stratified for histological subtype, phototype 1/2 and 3/4. Dose-response curves adjusted for age, age2, sex, phototype and non-occupational UV exposure were calculated. Results: Participants with high versus no (OR 2.08; 95% CI 1.24-3.50; p = 0.006) or versus moderate (OR 2.05; 95% CI 1.15-3.65; p = 0.015) occupational UV exposure showed a more than two-fold significantly increased risk to develop BCC in commonly UV-exposed body sites. Multivariate regression analysis did not show an influence of phototype or histological subtype on risk estimates. The restriction of the analysis to BCC cases in commonly sun-exposed body sites did not influence the risk estimates. The occupational UV dosage leading to a 2-fold increased basal cell carcinoma risk was 6126 standard erythema doses. Conclusion: The risk to develop basal cell carcinoma in highly occupationally UV-exposed skin was doubled consistently, independent of histological subtype, tumor localization and Fitzpatrick phototype.
EVALuna2:280863

Basal cell carcinoma risk and solar UV exposure in occupationally relevant anatomic sites: do histological subtype, tumor localization and Fitzpatrick phototype play a role? A population-based case-control study - Bauer, Andrea; Haufe, Eva; Heinrich, Luise; Seidler, Andreas; Schulze, H. -J.; Elsner, Peter; Drexler, Hans; Letzel, Stephan; John, Swen Malte; Fartasch, Manige; Bruening, Thomas; Dugas-Breit, Susanne; et al. (Journal of Occupational Medicine and Toxicology, 2020)

Bayerischer Projektverbund "Messung, Charakterisierung und Bewertung ultrafeiner Partikel" - Pfleger, Elisabeth; Drexler, Hans; Adrian, Christoph; Zeh, Reimar (9. Bayerischer Kongress für den Öffentlichen Gesundheitsdienst, 2021)

Bedeutung von Biomonitoring-Ergebnissen für die Regulation - Drexler, Hans (Zentralblatt für Arbeitsmedizin, Arbeitsschutz und Ergonomie, 2018)
For many hazardous substances an ambient air monitoring is not sufficient for a valid health risk assessment. Human biological monitoring can assess the individual exposure or the burden caused by exposure and the individual risk more precisely. Biomonitoring is a part of preventive occupational health care; however, the results cannot be directly implemented for surveillance and regulation as medical science is being applied and biomonitoring is therefore part of medical professional regulations and doctors must observe medical confidentiality. The Occupational Safety Act, the Preventive Occupational Medical Care Ordinance and the Medical Rules for Occupational Medical Care 11.1 regulate the application of human biological monitoring for the occupational risk assessment and protection.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Agents at work; Ambient monitoring; Biological limit value; Risk assessment; Toxicology

Belastung und Beanspruchung pflegender Angehöriger – Ein systematisches Review - Wischlitzki, Elisabeth; Lehner, Sarah; Drexler, Hans; Lösch, Regina (61. Wissenschaftliche Jahrestagung der Deutschen Gesellschaft für Arbeitsmedizin und Umweltmedizin, 2021)
Einleitung Ehrenamtliche Pflege von Angehörigen ist ein wichtiger Pfeiler in unserem Gesundheitssystem. Jedoch kann die Doppelbelastung insbesondere von Menschen, welche noch im Berufsleben stehen, zu enormen Herausforderungen und auch zu gesundheitlichen Einschränkungen führen. Ziel dieses systematischen Reviews ist es, den aktuellen Stand der Forschung zu Belastung und Beanspruchung pflegender Angehöriger zu eruieren. Methoden Eine systematische Literaturrecherche wurde anhand der elektronischen Datenbanken Medline und PSYNDEX durchgeführt. Die Ergebnisse wurden mittels zuvor gemäß PICO (participants, interventions, comparisons, outcomes) definierter Ein- und Ausschlusskriterien jeweils von zwei Gutachtern*innen unabhängig voneinander ausgewertet [1]. Ergebnisse Bis zum Zeitpunkt der Einreichung des Abstracts wurden 518 Treffer gescreent und 55 Studien in die qualitative Analyse eingeschlossen. Ein Update der Studienlage wird durchgeführt. Beeinflusst wird die gesundheitliche Situation der pflegenden Angehörigen gemäß der Studien insbesondere durch den Pflegeumfang, den Schweregrad der Symptomatik sowie die Beziehung zum Patienten. Im Rahmen der gesundheitlichen Konsequenzen weisen die Studien insbesondere auf eine depressive Symptomatik der pflegenden Angehörigen hin. Diskussion Die eingeschlossenen Publikationen beziehen sich weitestgehend auf Gelegenheitsstichproben. Es muss dabei in Erwägung gezogen werden, dass sich insbesondere jene Personen an Studien beteiligt haben könnten, welche noch über ausreichende zeitliche und emotionale Kapazitäten verfügten und somit unter Umständen auch einen besseren Gesundheitszustand aufwiesen. In diesem Zusammenhang ist ein möglicher Selektionsbias zu berücksichtigen. Schlussfolgerung Insbesondere der Betriebsarzt kann auf Basis seiner Schweigepflicht einen wertvollen Beitrag leisten, auf die gesundheitliche Situation pflegender Angehöriger im Betrieb einzugehen und hier positiv einzuwirken. Die vorliegenden Daten können hier unterstützend herangezogen werden, um die Situation sowie mögliche gesundheitliche Folgen der Betroffenen einschätzen zu können. Literatur [1] Higgins JPT, Green S. Cochrane Handbook for Systematic Reviews of Interventions Version 5.1.0 [updated March 2011]. 5th ed. The Cochrane Collaboration; 2011. <
Keywords: ehrenamtliche Pflege; Depression

Benzoyl Peroxide's Sensitisation Potential and Potency in Experimental Methods and Review of Contact Allergy and Allergic Contact Dermatitis - Egele, Kerstin; Drexler, Hans; Fartasch, Manigé; van Kampen, Vera; Merk, Hans F.; Nowak, Dennis; Schnuch, Axel; Uter, Wolfgang; Kreis, Patricia; Blömeke, Brunhilde (Contact Dermatitis, 2025)
Positive patch test responses to benzoyl peroxide (BPO) have been reported from patients without and with known exposure. Up to 6.5% were found in the United States and 7.8% in a study including patients from Germany, Austria and Switzerland. We provide an overview of the skin sensitisation potential and potency of BPO based on animal experiments and non-animal methods. BPO tested positive in Guinea Pig Tests and the Local Lymph Node Assay. Application of the current OECD guideline to identify a skin sensitizer by combining non-animal method results gave differing outcomes. Moreover, patch test responses of patients to BPO were considered to determine the importance of BPO as a relevant occupational contact allergen. Another well-known BPO exposure is the topical application to treat acne. Despite widespread use, extensive and long-term skin exposure, we found for this group only studies reporting few positive patch test reactions. Further, occupational handling of BPO and contact allergy is reported by dental technicians. In-depth evaluation of the prevalence of contact allergy in different professions with suspected BPO exposure did not reveal an association with occupational handling of BPO. Consequently, a generally increased risk for those professions is not supported.
CRIS-Team Scopus Importer:2025-02-14
Keywords: allergic contact dermatitis; benzoyl peroxide [CAS-no. 94-36-0]; non-animal methods; occupational allergen

Bericht zur Zwischenbilanz in der Ultrafeinstaubforschung. Bergfest im Projektverbund BayUFP - Pfleger, Elisabeth; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2022)

Berufliche Hautmittel: Hautschutz, Hautpflege und Hautreinigung - Fartasch, M.; Diepgen, T. L.; Drexler, Hans; Eisner, P.; John, S. M.; Schliemann, S. (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2016)
CRIS-Team Scopus Importer:2020-05-11

Berufszufriedenheit in der Arbeitsmedizin – alles gut, nur keine Anerkennung? - Amler, Nadja; Quittkat, Christine; Sedlazcek, Sabine; Nesseler, Thomas; Letzel, Stephan; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2020)

Bestandsaufnahme und Perspektive der arbeitsmedizinischen Betreuung in Deutschland - Stork, J.; Drexler, Hans; Hasselhorn, H. M.; Panter, W. (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2015)
CRIS-Team Scopus Importer:2020-05-11

Betriebliche Gesundheitsförderung, Betriebliches Gesundheitsmanagement und Netzwerkarbeit in Kleinst-, kleinen und mittelständischen Unternehmen - Ergebnisse einer Befragung im Rahmen des Modellprojekts "Gesund arbeiten in Thüringen" - Lösch, Regina; Fischmann, Wolfgang; Amler, Nadja; Frassek, Anna-Lena; Voss, Amanda Sophie; Sedlaczek, Sabine; Quittkat, Christine; Letzel, Stephan; Drexler, Hans (60. Wissenschaftliche Jahrestagung der DGAUM, 2020)
Hintergrund: In den letzten Jahren ist die Betriebliche Gesundheitsförderung (BGF) und das Betriebliche Gesundheitsmanagement (BGM) zunehmend auch in den Fokus von Kleinst-, kleinen und mittelgroßen Unternehmen (KKMU) gerückt. Allerdings mangelt es an flächendeckenden Konzepten zur praktischen Umsetzung. Um diesem Mangel entgegenzuwirken und den Arbeits- und Gesundheitsschutz zu stärken, wurden im Rahmen des Modellvorhabens „Gesund arbeiten in Thüringen (GAIT)“ 3 Unternehmens-Netzwerke gegründet. Diese bestehen aus 32 Kleinst-, kleinen und mittelgroßen Unternehmen (KKMU) verschiedener Branchen. Methode: Die vorliegende Studie stellt die Ergebnisse einer leitfadengestützten, telefonischen Befragung von 32 Geschäftsführern, Personalverantwortlichen bzw. leitenden Angestellten vor. Ziel der Befragung war es, einen umfassenden Überblick zu den Themen Bedarf, Angebot, Evaluation und Herausforderungen im BGF/BGM sowie zur Gefährdungsbeurteilung psychischer Belastungen innerhalb der Netzwerke zu erhalten. Darüber hinaus wurden den Teilnehmern gezielte Fragen bezüglich Ihrer Netzwerkteilnahme gestellt. Die Dokumentation der Antworten erfolgte als Protokoll während des jeweiligen Gespräches. Anschließend wurden die Daten mit IBM SPSS Statistics Version 25 ausgewertet. Zur Kodierung der Freitexte wird die manuelle qualitative Datenanalyse genutzt. Ergebnisse: Die Befragung zeigt, dass 81 % der Firmen ein BGM haben bzw. BGF-Maßnahmen durchführen. Die angebotenen Leistungen im Bereich BGF erstrecken sich von mobiler Massage über ergonomische Arbeitsplätze bis hin zu Gesundheitstagen, Vorträgen und Einzelgesprächen. Als Herausforderungen werden fehlende finanzielle Ressourcen und zeitliche Engpässe sowie mangelndes Wissen bezüglich der zur Verfügung stehenden Möglichkeiten berichtet. 53 % der Firmen erheben im Rahmen der Gefährdungsbeurteilung auch die psychischen Belastungen bei Ihren Mitarbeitern. Derzeit erfolgt die Auswertung der Gründe zum Netzwerkbeitritt sowie der Erwartungen und Ziele hinsichtlich der Netzwerkarbeit. Fazit und Ausblick: Im Rahmen der Netzwerkarbeit wird die Steigerung der Anzahl von Unternehmen, welche die Gefährdungsbeurteilung psychischer Belastungen erheben, angestrebt. Die Ergebnisse der Erwartungen an die und die Ziele der Netzwerkarbeit werden zukünftig bei der Erstellung von (KKMU)-Netzwerkkonzepten mit einbezogen.
Keywords: Betriebliches Gesundheitsmanagement; Netzwerke; Gesund arbeiten in Thüringen; BGM; BGF; Arbeits- und Gesundheitsschutz

Betriebliche Gesundheitsförderung in kleinen, mittleren und großen Unternehmen des Gesundheitssektors – Häufigkeit, Handlungsgründe der Unternehmensleitungen und Hürden der Realisierung - Schäfer, Elisabeth; Drexler, Hans; Kiesel, Johannes (Gesundheitswesen, 2016)
The aim of this study was to gain insight into worksite health promotion in small and medium-sized companies compared to large concerns in Middle Franconia. Action in worksite health promotion, obstacles and demand for networks for workplace health promotion were determined.A standardised telephone interview served for collecting data for this cross-sectional study. The interviewee was always the manager or their proxy. 106 companies were contacted. The results of this study were analysed via qualitative and quantitative methods in SPSS(®) 20.It was possible to reach and interview 80 companies, a return rate of 75.5%. More than half the companies (68.8%) implemented at least one activity for worksite health promotion, especially ergonomic measures and measures to promote physical activity. Taking the size of the company into consideration when analysing the results, previous study results are confirmed. With an increasing size of the company, the relative frequency of measures for workplace health promotion rises. The motivation for worksite health promotion ranges from keeping the employees healthy (38.2%) to worksite health promotion as part of the business culture (9.1%). 81.1% of the companies consider their activity in worksite health promotion to be successful. Furthermore, 80.0% of the firms that implemented worksite health promotion were supported by a partner like a health insurance (43.2%). Those companies that did not implement any activities for worksite health promotion, state as a prime reason that they did not think about it as yet (44.0%). Besides, 44.0% of the companies without any worksite health promotion would like to implement measures. 65.5% of the companies that already took action in worksite health promotion and 56.0% of the companies that did not would like to cooperate with other firms in a network for workplace health promotion. Mutual exchange is the most important factor for them.The results of this study show that almost half of the companies that did not implement measures for worksite health promotion as yet would like to take action in this regard. For a bigger establishment of worksite health promotion, networks are predestinated and are best accompanied and supported by external professionals like health insurances, mutual indemnity associations or universitie
EVALuna2:9748
Keywords: small and medium-sized enterprises; networks; workplace health promotion

Betriebsärztliche Betreuung von Studierenden der Humanmedizin und der Zahnmedizin - Drexler, Hans; Schmid, Klaus; Nauert, Thomas; Letzel, Stephan (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2016)
CRIS-Team Scopus Importer:2020-05-11

Bewertung von Biomonitoring-Befunden - Drexler, Hans; Weistenhöfer, Wobbeke (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2024)
CRIS-Team Scopus Importer:2024-03-15

Biological monitoring of exposure and effects in workers employed in a selenium-processing plant - Göen, Thomas; Schaller, Barbara; Jäger, Thomas; Braeu-Duemler, Ch.; Schaller, Karl-Heinz; Drexler, Hans (International Archives of Occupational and Environmental Health, 2015)
The aim of the study was to assess external and internal selenium exposure and potential biological effects in employees working in a selenium-processing plant.Twenty male employees of a selenium-processing plant (exposed) and 20 age-matched male individuals without occupational selenium exposure (controls) participated in the study. Exposure to selenium at the workplace was determined by personal air sampling. Internal exposure was assessed by measuring total selenium concentration in plasma after a workshift and after holidays as well as by measuring the selenium concentration in urine before and after shift and after holidays. The activity of glutathione peroxidase (GPx) in blood and the prothrombin time were determined as biological effect parameters.The exposure to selenium in the workplace air ranged from 8 to 950 µg/m(3) and exceeded in a large part current occupational exposure limits. The selenium levels in plasma samples of the exposed ranged from 49 to 182 µg/L during exposure and were significantly higher than the plasma levels observed after holidays as well as in the control group. The selenium concentration in pre- and post-shift urine samples did not differ significantly, and the average urinary selenium levels of the employees (18-1,104 µg/g creatinine) were significantly higher than those measured after holidays or determined in controls. Both the concentration of selenium in plasma and in urine did not correlate with the current external exposure of the employees at the workplace. However, we found a strong and significant association between the two biomonitoring parameters. In spite of the considerable high external exposure to elemental selenium, we did not find any effect on the GPx activity in blood as well as on the prothrombin time.Both the selenium levels in plasma and urine may be used as biological monitoring parameters for the assessment of chronic occupational exposure to selenium. Nevertheless, the toxicokinetics of the urinary excretion of selenium remain still unclear and require further investigations. Moreover, our findings emphasise the necessity of a re-evaluation of occupational exposure limits for elemental selenium and inorganic selenium compounds.
EVALuna2:9725

Blaulichtgefährdung der Augen durch Lichtemittierende Dioden (LED)? - König, Yanyan; Huchzermeyer, Cord; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2020)
Background: In occupational and domestic environments people are increasingly exposed to artificial ligiit from light-emitting diodes (LEDs). LEDs flave peak emission in the blue range. In this review, we summarise the current knowledge of the possible effects of blue light exposure on ocular health. Effects of blue light on the regulation of physiological functions will be considered elsewhere. Methods: We performed a narrative review. We included preclinical data as well as epidemiological studies. We searched MEDLINE, Pubmed, the Cochrane Library and International Standard Randomised Controlled Trial Number (ISRCTN)-Register clinical trial registers from 01 January 2014 to 31 May 2019. Results: The accumulated experimental evidence obtained from different experimental models has indicated that excessive exposure to blue light can induce damage in the retinal pigment epithelium (RPE), in photoreceptors and ganglion cells. Previous epidemiological findings are equivocal regarding any causal links between blue light exposure and the development of macular degeneration (AMD). In vitro and in vivo evidence suggests that blue light exposure may influence the progression of uveal melanoma. Conclusions: Long-term effects of LEDs on ocular health cannot be definitively assessed on the basis of current knowledge. Susceptibility to blue light damage varies among the different species. The severity of light-induced retinal damage changes with the time of the day and depends on the diet and genetic background. Additional studies on the safety of long-term exposure to low levels of blue light are needed to determine the safety of LEDs for ocular health.
CRIS-Team Scopus Importer:2024-12-16
Keywords: blue light; light-emitting diode; macular degeneration; uveal melanoma

Calcium, magnesium and aluminium ions as decontaminating agents against dermal fluoride absorption following hydrofluoric acid exposure - Mini Vijayan, Suvarna; Göen, Thomas; Dennerlein, Kathrin; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans; Kilo, Sonja (Toxicology in Vitro, 2021)
The fluoride ions of the industrially largely irreplaceable, locally corrosive hydrofluoric acid (HF) can scavenge cations in biological tissues, which explains their high toxic potential, and also leads to local acidification through proton release. The influence of three complexing agents, calcium (Ca2+) gluconate (as 2.5% Ca2+gel and individually (2.84%) or commercially (10%) formulated Ca2+solution), magnesium (Mg2+) gluconate (2.84%) solution and aluminium (Al3+) solution (Hexafluorine®, pure and diluted) on the absorption of fluoride following HF exposure (1–3 min, 100 μl, 30%/0.64 cm2) through human skin was investigated in an ex-vivo diffusion cell model. Fluoride absorption was assessed over 6–24 h and analysed with a fluoride electrode. Decreasing the contamination time reduced the fluoride absorption distinctly which was further reduced by the application of fluoride-binding decontamination agents (Ca2+, Mg2+, Al3+) or water alone without being significantly different. Ca2+ appeared slightly more effective than Mg2+ in reducing fluoride absorption. Moreover, the addition of pH adjusting buffer promoted the decontamination efficacy. Fluoride-binding agents can facilitate the decontamination of dermal HF exposure. However, prompt decontamination appeared to be the key to successful limitation of fluoride absorption and pushes the choice of decontamination agent almost into the background.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Aluminium; Calcium gluconate; Decontamination; Fluoride absorption; Human skin; Hydrofluoric acid

Changes in the law for occupational diseases - effects on the assessment of reduced earning capacity (MdE) in the case of work-related skin diseases within the meaning of BK no. 5101 - Krohn, S.; Skudlik, C.; Bauer, A.; Bernhard-Klimt, C.; Dickel, H.; Drexler, Hans; Elsner, P.; Engel, D.; Fartasch, M.; Glaubitz, S.; Gauglitz, G.; Goergens, A.; et al. (Dermatologie in Beruf und Umwelt, 2020)
CRIS-Team WoS Importer:2021-01-01

Cooperation between the occupational health insurance and physicians practicing occupational dermatology: optimization potential in quality assurance - Elsner, Peter; Aberer, Werner; Bauer, Andrea; Diepgen, Thomas Ludwig; Drexler, Hans; Fartasch, Manige; John, Swen Malte; Schuhmacher-Stock, Uta; Wehrmann, Wolfgang; Weisshaar, Elke (Journal der Deutschen Dermatologischen Gesellschaft, 2014)
Quality assurance is a task of the medical profession, but it is also a duty of the occupational health insurance (OHI). Data on the interaction quality between physicians practicing occupational dermatology and the OHI are limited.An online survey was performed in 854 German members of the Working Group on Occupational and Environmental Dermatology in October 2013. Items included demographic data, a judgment on the cooperation between the dermatologists and OHI companies, an economic grading of the current compensation scheme, and prioritization of optimization tasks.182 members (21.3 % of the invited population) participated in the survey. The cooperation with the OHI companies was judged as "very good" by 10.8 %, as "good" by 56.7  %, as "satisfactory" by 24.2 %, as "sufficient" by 7.0 % and as "inadequate" by 1.3 %. 93.4 % of the interviewed mentioned problems and improvement potentials in the cooperation of their practice or clinic with OHI companies. Main points of criticisms were reimbursement (44.7 %), followed by impairments of the treatment options (36.5 %) and the delay or scope of the treatment in the dermatologist's procedure (29.4 %).While most physicians practicing occupational dermatology give a positive judgment of their cooperation with OHI companies, quality optimization potentials exist regarding the reimbursement of dermatological services, especially regarding time-intensive counselling in the prevention of occupational skin diseases, in the enablement of diagnostic and therapeutic procedures according to current guidelines and in a timely preventive intervention to use the therapeutic window before chronification of skin diseases may occur.
EVALuna2:9711

Cross-sectional study on N,N-dimethylformamide (DMF); effects on liver and alcohol intolerance - Kilo, Sonja; Göen, Thomas; Drexler, Hans (International Archives of Occupational and Environmental Health, 2016)
There are still concerns regarding occupational exposure to hepatotoxic DMF. This study was designed to evaluate possible liver damaging effects of DMF under current workplace conditions in synthetic fibres industries.Among other laboratory parameters, liver function parameters (alkaline phosphatase (ALP), aspartate aminotransferase, alanine aminotransferase and gamma-glutamyltransferase), the mean corpuscular erythrocyte volume (MCV) and carbohydrate-deficient transferrin (CDT) of the workforce of two companies present at the days of study were investigated. Internal exposure to DMF was assessed via three different biomarkers [sum of N-methylformamide and N-hydroxymethyl-N-methylformamide, N-acetyl-S-(N-carbamoyl)cysteine (AMCC) and 3-methyl-5-isopropylhydantoin (MIH)]. Alcohol consumption was assessed by means of direct ethanol metabolites (ethylglucuronide and ethylsulfate).None of the tested liver enzyme activities showed a positive association with any of the three exposure markers, nor did CDT and MCV. CDT was negatively associated with AMCC and the ALP activity negatively with all three exposure markers. Changes in liver function are seen mainly in conjunction with ethanol consumption but also with increasing body weight and age. MCV was associated with smoking. Almost half of the workers stated to experience alcohol flush reaction.The present study indicates that long-term exposure to DMF, which was specified by median urinary AMCC levels of 4.84 mg/g creatinine and DMF haemoglobin adduct levels of 60.5 nmol/MIH/g globin, respectively, does not result in any adverse liver effects. In contrast, these DMF exposure levels still elicit certain alcohol intolerance reactions.
EVALuna2:9751

Current and historical individual data about exposure of workers in the rayon industry to carbon disulfide and their validity in calculating the cumulative dose - Göen, Thomas; Schramm, Axel; Baumeister, Thomas; Uter, Wolfgang; Drexler, Hans (International Archives of Occupational and Environmental Health, 2014)
The objective of the study was to investigate how exposure to carbon disulfide (CS2) in a rayon-manufacturing plant has changed within two decades and whether it is possible to calculate valid data for the individual cumulative exposure.The data for CS2 concentration in air and biological exposure monitoring (2-thio-1,3-thiaxolidine-4-carboxylic acid (TTCA) in urine) from two cross-sectional studies, performed in 1992 (n = 362) and 2009 (n = 212) in a German rayon-manufacturing plant, were compared to data obtained from company-internal measurements between the studies.Using the data from the cross-sectional studies and company-internal data, cumulative external exposure and the cumulative internal exposure were calculated for each worker. External and internal CS2 exposure of the employees decreased from 1992 (medians 4.0 ppm and 1.63 mgTTCA/g creatinine) to 2009 (medians 2.5 ppm and 0.86 mg/g). However, company-internal CS2 data do not show a straight trend for this period. The annual medians of the company-internal measurement of external exposure to CS2 have varied between 2.7 and 8.4 ppm, in which median values exceeded 5 ppm generally since 2000. The annual medians for the company-internal biomonitoring assessment ranged between 1.2 and 2.8 mg/g creatinine. The cumulative CS2 exposure ranged from 8.5 to 869.5 ppm years for external exposure and between 1.30 and 176.2 mg/g creatinine years for the internal exposure. Significant correlations were found between the current air pollution and the internal exposure in 2009 but also between the cumulative external and internal CS2 exposure.Current exposure data, usually collected in cross-sectional studies, rarely allow a reliable statement on the cumulative dose, because of higher exposure in the past and of fluctuating courses of exposure. On the other hand, company-internal exposure data may be affected by non-representative measurement strategies. Some verification of the reliability of cumulative exposure data may be possible by testing the correlation between cumulative exposure data of external assessment and biological monitoring.
EVALuna2:5395

Degree of Actinic Elastosis Is a Surrogate of Exposure to Chronic Ultraviolet Radiation and Correlates More Strongly with Cutaneous Squamous Cell Carcinoma than Basal Cell Carcinoma. - Drexler, Konstantin; Drexler, Hans; Karrer, Sigrid; Landthaler, Michael; Haferkamp, Sebastian; Zeman, Florian; Berneburg, Mark; Niebel, Dennis (Life, 2023)
(1) Background: Keratinocyte cancer (KC) is associated with exposure to ultraviolet (UV) radiation. However, data are controversial as to whether chronic UV exposure or high intermittent UV exposure are key drivers of carcinogenesis in cutaneous squamous cell carcinoma (cSCC) and basal cell carcinoma (BCC). Prolonged sun exposure of the skin causes photo-aging, which is associated with actinic elastosis, a condition characterized by the degeneration of elastin in the upper dermis, which is assessable via conventional histology. In this study, we aimed to compare the degree of actinic elastosis in different types of KC with regard to various patient characteristics. (2) Methods: We defined a semiquantitative score for the degree of actinic elastosis ranging from 0 = none to 3 = total loss of elastic fibers (basophilic degeneration). The extent was measured histometrically by two independent dermatohistopathologists in the immediate vicinity of 353 KC. The scores were merged and matched with tumor types (cSCC and BCC with subtypes), and clinical variables such as body site, sex and age. (3) Results: As expected, the degree of actinic elastosis correlated with age. However, it was significantly higher in cSCC compared to BCC irrespective of age, sex, body site and tumor subtypes. (4): Conclusions: Lifetime sun exposure may be estimated via routine histology using this scoring technique for actinic elastosis as a surrogate marker. cSCCs are more strongly associated with chronic UV exposure than BCCs, even in sun-exposed localizations such as the face.
EVALuna2:532035

Der demografische Wandel in unserer Gesellschaft und die zukünftige arbeitsmedizinische Versorgung - Drexler, Hans; Letzel, Stephan; Nesseler, Thomas; Tautz, Andreas (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2016)
CRIS-Team Scopus Importer:2020-05-11

Dermal absorption and skin damage following hydrofluoric acid exposure in an ex vivo human skin model - Dennerlein, Kathrin; Kiesewetter, Franklin; Kilo, Sonja; Jäger, Thomas; Göen, Thomas; Korinth, Gintautas; Drexler, Hans (Toxicology Letters, 2016)
The wide industrial use of hydrofluoric acid (HF) poses a high risk for accidental dermal exposure. Despite local and systemic hazards associated with HF, information on percutaneous penetration and tissue damage is rare. In the present ex vivo study, the dermal absorption of HF (detected in terms of fluoride ions) was quantified and the skin damaging potential as a function of concentration and exposure duration was assessed. Percutaneous penetration of HF (c=5, 30, and 50%) at 3 exposure durations (3, 5, and 10min) was investigated in a static diffusion cell model using freshly excised human skin. Alterations of skin were histologically evaluated. HF rapidly penetrated through skin under formation of a considerable intradermal reservoir ( 13-67% of total absorbed fluoride). Histologically, epidermal alterations were detected already after exposure to 5% HF for 3min. The degree of skin damage increased with rising concentration and exposure duration leading to coagulation necrosis. For HF concentrations of >=30%, skin damage progressed into deeper skin layers. Topically applied HF concentration was the principal parameter determining HF induced skin effects. The intradermal HF retention capacity associated with progression and prolongation of HF induced skin effects must be considered in the review of skin decontamination procedures.
EVALuna2:9745

Dermal penetration and resorption of beta-naphthylamine and N-phenyl-beta-naphthylamine from lubricants in an ex vivo human skin model - Dennerlein, Kathrin; Göen, Thomas; Zobel, Melanie; Boos, Anja; Drexler, Hans; Kilo, Sonja (Chemosphere, 2017)
Dermal Penetration of aromatic amines (AA's), often suspected or known to be carcinogenic, can play an important role in the overall human exposure. However, information on penetration of certain AA's is poor and inconsistent. Penetration of the former lubricant additive N-phenyl-beta-naphthylamine (PBNA) and its contaminant beta-naphthylamine (BNA) a known carcinogen was investigated and the influence of formulation and co-application characterized. Percutaneous penetration of BNA and PBNA through freshly excised human skin (n = 8; 48 h) was investigated using an ex vivo diffusion cell model. Both AA's were applied in a technical-conform lubricant or dissolved in hexane. The amount of BNA and PBNA applied to skin was 0.52 and 259 ?g/0.64 cm2. The analytical determination of AA's was performed by GC-MS. Both, BNA and PBNA penetrated through human skin (38 vs. 5% of applied dose). In contrast to BNA, the percutaneous penetration of PBNA continued beyond the end of exposure. Co-exposure of both AA's increased the intradermal uptake of BNA and PBNA (p < 0.05). Exposure in lubricant showed the least overall penetration (2.9 and 1.9% of applied dose). The results clearly reveal that dermal penetration of both AA's depends strongly on the mode of application. Co-application and formulation alters the penetration of the AA's.
EVALuna2:9769

Der Rettungsanker am Unfallort: Erste Erkenntnisse einer qualitativen Studie über das Erleben kollegialer Erstbetreuung nach potenziell traumatisierenden Ereignissen - Wrenger, Nina; Staples, Ronald; Grässel, Elmar; Drexler, Hans; Clarner, Annika (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2015)
Objectives: Health care experts recommend prompt low-threshold psychosocial assistance for employees who have experienced a potentially traumatic event. Collegial first response constitutes such a form of acute care: colleagues of those involved in the accident come straight to the scene, where it is their job to look after the employees concerned. How this is viewed by the people involved has been unclear until now. The objective, therefore, was to gather initial findings about the experience of collegial first response within the context of a potentially traumatic event. Methods: As part of a prospective cohort study, 22 drivers at a German transport company were asked in guideline-based interviews about their experience of suffering an accident at work and the care provided at the scene of the accident. The material collected was assessed with the help of a structured content analysis based on Mayring and a classification system designed to be deductive/inductive. Findings: The experience of the accident could be broken down into four consecutive periods of time: the moment of the accident, the ensuing interval, the time spent dealing with the damage and the departure from the scene of the accident. During this time the people affected felt helpless and overwhelmed at first. They then looked for something that could give them security and guidance. The arrival of a collegial peer supporter at the scene of the accident came as a great relief to the people concerned. The peer supporter was perceived as someone who could give them a sense of no longer being alone at the scene of the accident, of being cared for and receiving assistance. Conclusions: The experience of an accident cannot be reduced down to the moment in which it suddenly occurs. In fact, for those affected it continues until leaving the scene of the accident and beyond. Their state of health at this time cannot typically be described as stable. Collegial first response plays a vital role in the system of assistance deployed at the scene of the accident from the perspective of the people involved.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Accident; Collegial peer support; Psychological first aid; Research in medical care; Transport; Trauma

Determination of eleven small selenium species in human urine by chromatographic-coupled ICP-MS methods - Hildebrand, Jörg; Greiner, Annette; Drexler, Hans; Göen, Thomas (Journal of Trace Elements in Medicine and Biology, 2020)
Background: The determination of various selenium species in urine enables a specific biomonitoring of the exposure to different selenium compounds. Methods: For this task a coupling of three chromatographic techniques with ICP-MS was developed for the separate quantification of eleven species in urine. The first procedure was based on reverse phase chromatography and was designed for the separate determination of methyl-2-acetamido-2-deoxy-1-seleno-b-D-galactopyranoside (SeSug1), methyl-2-acetamido-2-deoxy-1-seleno-b-D-glucopyranoside (SeSug2), selenomethionine (SeMet), methylselenocysteine (MeSeC), seleno-D,L-ethionine (SeEt), methylselenic acid (MeSeA) and methylselenoglutathione (MeSeG); the second procedure was based on anion exchange chromatography and measured selenate (Se (VI)) and selenite (Se (IV)); the third procedure was based on cationic exchange chromatography and determined methyl-2-amino-2-deoxy-1-seleno-b-D-galactopyranoside (SeSug3) and the trimethylselenium ion (TMSe). A fourth method for the more sensitive determination of TMSe was upgraded by an on-line after-column reaction process. Results: The validation of the methods yielded sensitive detection limits of the species between 0.03 and 0.10 μg Se/L. For TMSe a detection limit of 0.02 μg Se/L resulted by the fourth method. An intra-day precision of 2.7–10.6% and a relative recovery between 87 % and 108 % confirm the robustness of the methods. Conclusion: The developed procedures enable a separate and sensitive determination of eleven selenium species in urine and thus permit the exploring of metabolic factors in the general population and particularly exposed individuals.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Anionic exchange chromatography; Cationic exchange chromatography; LC-ICP-MS; Reverse phase chromatography; Selenium species

DGAUM zur Sonnenschein-Richtlinie - Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
CRIS-Team Scopus Importer:2020-05-11

Die Berücksichtigung von Schwangerschaftsgruppen bei der Evaluierung von Beurteilungswerten in biologischem Material: Sicherheit und Schutz für das ungeborene Leben - Weistenhöfer, Wobbeke; Brinkmann, Britta; Schriever-Schwemmer, Gerlinde; Michaelsen, Sandra; Bartsch, Rüdiger; Klotz, Katrin; Drexler, Hans; Hartwig, Andrea (60. Jahrestagung der DGAUM 2020, 2020)

Effect of an aluminum foil-processed diet on internal human aluminum burden - Hiller, Julia; Göen, Thomas; Seibold-Wulf, Nina; Meyer, Sebastian; Drexler, Hans (Environment International, 2023)
Background and purpose: Aluminum can be released into food by aluminum-containing food-contact materials (Al-FCM) during preparation or storage. There is considerable concern that extra aluminum intake may have negative effects on public health, especially with regard to its high background exposure and neurotoxic properties of aluminum in high exposures. Human in-vivo data on the additional aluminum load from Al-FCM, however, are lacking. As such, the objective of this study was to explore whether the consumption of a diet highly exposed to such products leads to an increased systemic Al load in real-world conditions. Materials and methods: An exploratory, single-arm intervention study with a partially standardized diet was designed and carried out with 11 participants. The same 10-day sequence of dishes was repeated three times. Participants were exposed to Al-FCM from Days 11 to 20, whereas control-phase meals were prepared without Al-FCM during the first and last 10–day periods. Spot urine samples were collected each morning and evening and analyzed for their aluminum concentration; appropriate contamination countermeasures were taken. Principal results: Urinary aluminum excretion showed a strong dependency on the creatinine concentration in urine and required adjustment in further analyses. The creatinine-adjusted aluminum excretion during the exposure phase (median 1.98 µg/g creatinine) was higher than in both control phases (1.78 µg/g creatinine each). Two different mixed-effects regression models showed a significant effect in the exposure phase. Considering a discrete time effect, the creatinine-adjusted mean increase in the exposure phase was estimated to be 0.19 µg/L (95% CI: 0.07–0.31; p = 0.0017). Major conclusions: This study demonstrated a measurable but fully reversible additional Al burden in humans from subacute Al-FCM exposure under real-world conditions. The estimated increase from Al-FCM corresponds to 8% of the baseline concentration. These data enable a more robust assessment of human health risks by Al-FCM.
Created from Fastlane, Scopus look-up
Keywords: Aluminum; Diet; Exposure assessment; Food-contact material

Effect of Skin Protection and Skin Irritation on the Internal Exposure to Carbon Disulfide in Employees of the Viscose Industry - Kilo, Sonja; Zonnur, Nina; Uter, Wolfgang; Göen, Thomas; Drexler, Hans (Annals of Occupational Hygiene, 2015)
Occupational exposure to carbon disulfide (CS2) leads to inhalative and dermal uptake and thereby to internal exposure. In order to prevent occupational contact dermatitis, gloves and skin protection creams are used at the workplace. The aim of the study was the evaluation of the influence of personal skin protection and irritation on the internal exposure to CS2 of employees in the viscose industry.One hundred and eighty-two male CS2-exposed employees were included in the study and were examined regarding working conditions, use of personal protective measures und skin status. Personal air monitoring and biological monitoring was performed and the 'relative internal exposure' (RIE, internal exposure in relation to external exposure) calculated. A multiple regression analysis calculated the influence of skin protection and irritation on CS2 uptake.Usage of skin protection creams and gloves (and both in combination) while working was associated with a significantly higher RIE indicating a higher dermal penetration of CS2. Equally, irritated skin and younger age was associated with a higher internal burden.Gloves and skin protection creams are useful for preventing occupational skin diseases. However, when handling skin-resorptive substances like CS2, they can increase internal exposure or skin irritation. Therefore, we recommend the careful consideration of benefits and risks of protective creams and gloves at the workplace.
EVALuna2:5491

Ehrenpreis der DGAUM an die Geschäftsführerin der Unfallkasse Rheinland-Pfalz: Deutsche Gesellschaft für Arbeitsmedizin und Umweltmedizin zeichnet Beate Eggert aus - Drexler, Hans; Nesseler, Thomas (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2015)
CRIS-Team Scopus Importer:2020-05-11

Eine große Chance im Arbeitsschutz für Beschäftigte im Freien verspielt - Drexler, Hans; Diepgen, Thomas L. (Dermatologie in Beruf und Umwelt, 2019)
CRIS-Team Scopus Importer:2020-05-11

Elevated aluminum excretion in patients by long-term subcutaneous immunotherapy – A cross-sectional case-control study - Hiller, Julia; Göen, Thomas; Drexler, Hans; Berking, Carola; Wagner, Nicola (International Journal of Hygiene and Environmental Health, 2024)
Background: Aluminum (Al) adjuvants have been used in vaccines and subcutaneous immunotherapy (SCIT) for decades. Despite indisputable neurotoxic properties of Al, there is no clear evidence of a causal relationship between their use and any neurotoxic side effects. However, recent rat studies have shown an accumulation of Al from adjuvants in tissues, especially in bones. Objectives: Since the human toxicokinetics of Al-adjuvants are poorly understood, this study aimed to evaluate whether up-dosed or long-term SCIT with Al-coupled extracts leads to increased Al load in humans. Methods: This observational cross-sectional case-control study explored Al excretion in hymenoptera venom allergy patients recruited in 2020 before initiation (n = 10) and during ongoing (n = 12) SCIT with Al-based preparations. Urine samples were collected before and 24 h after the SCIT injections and analyzed for aluminum content by using atomic absorption spectrometry. The cumulative administered Al dose was extracted from patient records. Patients receiving long-term immunotherapy were treated between 2.8 and 13.6 years (mean 7.1). Other potential sources of Al exposure were surveyed. Results: Patients who had received Al-coupled immunotherapy for several years showed significantly (p < 0.001) higher Al excretion than the controls at initiation of immunotherapy (mean 18.2 μg/gC vs. 7.9 μg/gC) and predominantly (73%) were above the 95th percentile of the general populations' exposure (>15 μg/gC), however, without reaching levels of toxicological concern (>50 μg/gC). Taking both groups together excreted Al levels correlated with the cumulative administered Al dose from SCIT (linear regression: Alurine = 8.258 + 0.133*Alcum; p = 0.001). Discussion: These results suggest a relevant iatrogenic contribution of long-term SCIT to human internal Al burden and potential accumulation. Considering the medical benefits of Al-adjuvants and SCIT a differentiated risk-benefit analysis is needed. For certain scenarios of potential toxicological concern in clinical practice biomonitoring might be advisable.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Adjuvant; Aluminum; Biomonitoring; Immunologic desensitization; Risk assessment; Venom hypersensitivity

Empfehlung zur Begutachtung von arbeitsbedingten Hauterkrankungen und Hautkrebserkrankungen – Bamberger Empfehlung - Diepgen, T. L.; Krohn, S.; Bauer, A.; Bernhard-Klimt, C.; Brandenburg, S.; Drexler, Hans; Elsner, P.; Fartasch, M.; John, S. M.; Kleesz, P.; Köllner, A.; Letzel, St; et al. (Dermatologie in Beruf und Umwelt, 2016)
CRIS-Team Scopus Importer:2020-05-11

Evaluation der Durchführung einer Gefährdungsbeurteilung psychischer Belastungen bei Lehrkräften - Wischlitzki, Elisabeth; Fischmann, Wolfgang; Jüngert, Barbara; Voss, Amanda Sophie; Drexler, Hans (58. Jahrestagung der Deutschen Gesellschaft für Arbeitsmedizin und Umweltmedizin (DGAUM), 2018)
Einleitung Die arbeitsmedizinische Versorgung der Lehrkräfte ist in verschiedenen Bundesländern auf Basis der gesetzlichen Vorgaben bereits institutionell verankert. Zur praktischen Umsetzung des Arbeitsschutzes in bayerischen staatlichen Schulen wurde 2013 ein Modellprojekt ins Leben gerufen, innerhalb dessen u.a. das geeignete Vorgehen zur psychischen Gefährdungsbeurteilung bei Lehrern erprobt wurde. Methoden Das Konzept wurde auf Basis der Prozessschritte gemäß GDA Psyche sowie bisheriger Erfahrungen zur psychischen Gefährdungsbeurteilung in Unternehmen entwickelt. 12 Schulen an 13 Standorten waren innerhalb des Modellprojekts involviert, sodass zwei Schulen jeder Schulart vertreten waren. Die Belastungen wurden nach Einteilung in 2 Bereiche (Lehrkräfte und Verwaltungspersonal) mittels schriftlicher Mitarbeiterbefragung erhoben. Nach Vorstellung der Ergebnisse und Hinweisen zu möglichen Maßnahmen erfolgte die Konkretisierung und Durchführung von Interventionen durch die Schulen selbst. Das Vorgehen wurde am Ende des Projekts mittels Fragebögen, welche an die Schulleiter/innen versandt wurden, evaluiert. Beurteilt werden sollte die grundsätzliche Herangehensweise zur psychischen Gefährdungsbeurteilung sowie insbesondere der eingesetzte Fragebogen. Ergebnisse 11 von 13 Fragebögen wurden ausgefüllt (84,6%). Der eingesetzte Bogen zur psychischen Gefährdungsbeurteilung wurde von 8 der 11 Schulen als angemessen in seiner Länge (58 Items) angesehen und deckte die relevanten Belastungen des Lehrerberufs ab. In 8 Von 11 Schulen konnten Maßnahmen auf Basis der Erhebung abgeleitet werden. Im Rahmen der qualitativen Auswertung wurde der Hinweis zur schulartspezifischen Gestaltung des Fragebogens zur Berücksichtigung differierender Arbeitsbedingungen gegeben. Weitere Unterstützung wurde insbesondere bei der Ableitung von Maßnahmen für nötig erachtet. Diskussion Die Auswertung der Daten beruht auf 12 Pilotschulen des Modellprojektes. Von einer hohen Aussagekraft der Evaluationsergebnisse kann jedoch ausgegangen werden, da lediglich eine Schule keinen Evaluationsbogen zurück sendete. Eine weitere Schule mit zwei Standorten füllte einen Bogen für beide Standorte gemeinsam aus. Schlussfolgerung Das Vorgehen innerhalb der psychischen Gefährdungsbeurteilung erwies sich als zielführend. Die Weiterentwicklung des Fragebogens ist auf Basis der Evaluationsergebnisse möglich. Insbesondere innerhalb der Ableitung von Maßnahmen scheint eine engere Unterstützung der Schulen notwendig. <br
Keywords: Schule; Lehrergesundheit; Gefährdungsbeurteilung

Evaluation of biomarkers assessing regular alcohol consumption in an occupational setting - Kilo, Sonja; Hofmann, Birgit; Eckert, Elisabeth; Göen, Thomas; Drexler, Hans (International Archives of Occupational and Environmental Health, 2016)
An estimation of ethanol intake is frequently of importance in the frame work of studies, but not trivial to achieve. Problems are "underreporting", a very short time frame for the detection of ethanol as direct marker and interference of many in- and outside body factors with strain parameters. The aim of this study was to explore the suitability of the direct urinary biomarkers ethyl glucuronide (EtG) and ethyl sulphate (EtS) to assess moderate but regular alcohol consumption.A total of 175 male workers without any known occupational contact to substances influencing liver functions or metabolism of ethanol were examined. Strain parameters of alcohol consumption, i.e. the liver function tests (LFTs: aspartate aminotransferase, alanine aminotransferase, gamma-glutamyltransferase), carbohydrate-deficient transferrin (CDT), mean corpuscular erythrocyte volume (MCV) and the markers of alcohol consumption (EtG and EtS) have been analysed and compared.Up to 14 % of workers had been outside reference range for strain parameters. 62.3 % of the workers had at least traceable amounts of EtG and 84.6 % of EtS. Values above cut-off (indicating voluntary ethanol intake) were found in 34.9 and 51.4 % of the workers for EtG and EtS, respectively. In multiple linear regression analyses, CDT and MCV but not the LFTs showed a dependency from the non-oxidative ethanol metabolites. The LFTs were influenced by BMI.Determination of EtG and EtS in urine is an adequate tool to assess moderate but regular alcohol consumption.
EVALuna2:9752

Evaluation of the effect of skin cleaning procedures on the dermal absorption of chemicals - Dennerlein, Kathrin; Jäger, Thomas; Göen, Thomas; Kilo, Sonja; Schaller, Karl-Heinz; Drexler, Hans; Korinth, Gintautas (Toxicology in Vitro, 2015)
To reduce the internal exposure, skin decontamination is the most important measure after dermal contact to chemicals. However, no harmonized skin cleaning procedure for experimental ex vivo studies is published. In our study, the impact of two skin cleaning techniques on dermal penetration kinetics and intradermal deposition of 1,4-dioxane, 5% hydrofluoric acid (HF, detected in terms of fluoride ions), and anisole was evaluated to develop a reliable ex vivo skin cleaning method using the diffusion cell technique. After exposure (duration: 3 min (HF); 1h (1,4-dioxane and anisole)) of excised human skin (n=6-8) decontamination was performed by (I) water-soaked cotton swabs or (II) direct application of water on the exposure area. The effect of skin cleaning was investigated by analysing the concentration time course of chemicals in the receptor fluid of diffusion cells and by determining the deposition in skin. Both skin cleaning procedures reduced the amount of fluoride in the skin compartments (p<0.05) and the receptor fluid (p<0.1). However, the effect of cleaning on the dermal absorption of the organic test compounds was not significant. The results demonstrate the suitability of the applied ex vivo protocol for investigating the effectiveness of skin cleaning measures following dermal exposure. In addition, data reveal that the determination of test compounds in both, skin compartments as well as receptor fluid as equivalent for the systemic uptake needs to be considered in studies assessing the effectiveness of skin decontamination procedures.
EVALuna2:9730

Evaluation of urinary selenium as a biomarker of human occupational exposure to elemental and inorganic selenium - Greiner, Annette; Hildebrand, Jörg; Feltes, R.; Uter, Wolfgang; Drexler, Hans; Göen, Thomas (International Archives of Occupational and Environmental Health, 2019)
Purpose: Selenium (Se) is an essential trace element, which however, exhibits a narrow safe range of intake. Selenium also occurs at several workplaces, which results in an inhalative selenium exposure of the employees. Thus, an efficient exposure assessment strategy is demanded. The most established parameter, selenium in plasma, mostly consists of protein-bound selenium. This study aimed to investigate urinary total selenium (Se-U) as an additional biomarker of recent human occupational exposure to elemental and inorganic selenium. Methods: Pre- and post-shift urine samples from employees with exposure to selenium-containing dust were analyzed to total selenium and compared with Se levels in urine samples from controls without occupational exposure to selenium as well as correlated with the recent ambient Se exposure by personal air monitoring. Results: Se-U in post-shift samples was considerably increased compared to the levels in pre-shift samples as well as to the controls. However, Se-U in pre-shift urine was elevated compared to the Se-U in controls too. Se-U in post-shift urine and even better the shift increment in Se-U correlated with the air exposure of the present shift. A rough estimation by Se-U shift increment and external exposure accounted for an inhalative resorption rate of about 1%. Conclusion: Our data indicate that Se-U can display the exposure. Pre-shift Se-U levels may be based on previous exposure and indicate a slow urinary elimination kinetics. The results hint for a rather low resorption rate of selenium and inorganic selenium compounds via the lung.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Biomonitoring; Occupational exposure; Resorption; Selenium; Urine

Evaluation on the reliability of the permeability coefficient (Kp) to assess the percutaneous penetration property of chemicals on the basis of Flynn's dataset - Kladt, Carolin; Dennerlein, Kathrin; Göen, Thomas; Drexler, Hans; Korinth, Gintautas (International Archives of Occupational and Environmental Health, 2018)
PURPOSE: The permeability coefficient (Kp) is often used for prediction of the dermal penetration of chemicals. Mathematical models have mostly been derived on Kp data basis. However, confusing Kp values are reported, questioning the general reliability of this parameter. In this study, we tested the plausibility of Kp values expressing the dermal penetration velocity (cm h-1) of chemicals on a larger dataset from literature. METHODS: Kp was applied for the calculation of the time for penetration through skin membranes of defined thickness (tCrossSkin). Kp values were obtained from Flynn's dataset (1990), containing data determined mostly under similar experimental conditions using diffusion cells. Further skin penetration parameters, e.g., times at which the chemicals were firstly measured in the receptor phase, lag times, steady-state times, and exposure duration, where available, were related to Kp values. The data congruence was tested comparing Kp values from Flynn's dataset with those reported in the EDETOX database. Variables, which could bias the results, such as different experimental protocols and research groups were also considered. RESULTS: Kp data for 94 chemicals matched the inclusion criteria were evaluated. According to the Kp values, 21 (22%) compounds would require longer than 100 h, and 20 (21%) further compounds longer than 10 h of exposure to penetrate skin membranes of 0.01-2.5 mm thickness. Obviously, erroneous Kp were found in studies of almost all research groups in Flynn's database, indicating that neither the observer nor the experimental conditions alone biased the values. CONCLUSIONS: Our evaluation demonstrates high implausibility of Kp values to represent the dermal penetration velocity and supports general invalidity of the parameter for implementation in studies using skin membranes. The Kp should not be used to characterize the percutaneous penetration of chemicals or in risk assessment without verification.
EVALuna2:34675

Evidence-based health services research–a short review and implications - Grässel, Elmar; Donath, Carolin; Hollederer, A.; Drexler, Hans; Kornhuber, Johannes; Zobel, A.; Kolominsky-Rabas, Peter (Gesundheitswesen, 2015)
Health services research aims to generate knowledge about care processes of people with illnesses who access health-care services. In addition, the consequences of those processes in the care routine concerning the involved persons and the health system are analyzed. CONCEPT OF THE THEORETICAL WORK: In the first part of the manuscript, an overview concerning the current definitions and subsumptions of the concept of health services research is given. The second part of the manuscript focuses on demonstrating how evidence-based health services research can be used to enable optimization of the care system. The concept is called the "circle of care optimization". In the first step the current care situation concerning its deficits and their reasons is analyzed. In the second step a relevant care goal is defined. In the third step an improvement of an existing care process is developed to achieve the defined care goal. In the fourth step, a comparative empirical study with a high-quality study design is carried out, to assess whether the improved care process is superior to the current care as usual. A health economic evaluation will be performed if applicable. If the results show no or only small advantages, the "circle" starts again with step 3. However, if the results show a significant effect in favour of the new care process and are relevant for the delivery of care and efficient in the context of health economics, a fifth step will be performed which involves developing and testing strategies for implementation. Where relevant, the consequences of implementation are investigated in a sixth step. A "best-practice" practical example is demonstrated to illustrate the "circle of care optimization".conclusions are derived by illustrating future challenges for health services research.
EVALuna2:9737

Exposure of patients to di(2-ethylhexy)phthalate (DEHP) and its metabolite MEHP during extracorporeal membrane oxygenation (ECMO) therapy - Kaestner, Franziska; Seiler, Frederik; Rapp, Daniel; Eckert, Elisabeth; Müller, Johannes; Metz, Carlos; Bals, Robert; Drexler, Hans; Lepper, Philipp M.; Göen, Thomas (PLoS ONE, 2020)
The plasticizer di(2-ethylhexyl)phthalate (DEHP) is often used for PVC medical devices, that are also largely used for intensive care medical treatments, like extracorporeal membrane oxygenation (ECMO) therapy. Due to the toxicological potential of DEHP, the inner exposure of patients with this plasticizer is a strong matter of concern as many studies have shown a high leaching potential of DEHP into blood. In this study, the inner DEHP exposure of patients undergoing ECMO treatment was investigated. The determined DEHP blood levels of ECMO patients and the patients of the control group ranged from 31.5 to 1009 μg/L (median 156.0 μg/L) and from 19.4 to 75.3 μg/L (median 36.4 μg/L), respectively. MEHP blood levels were determined to range from < LOD to 475 μg/L (median 15.9 μg/L) in ECMO patients and from < LOD to 9.9 μg/L (median 3.7 μg/L) in the control group patients, respectively. Increased DEHP exposure was associated with the number of cannulas and membranes of the ECMO setting, whereas residual diuresis decreased the exposure. Due to the suspected toxicological potential of DEHP, its use in medical devices should be further investigated, in particular for ICU patients with long-term exposure to PVC, like in ECMO therapy.
CRIS-Team Scopus Importer:2020-02-11

Exposure of the German general population to platinum and rhodium - Urinary levels and determining factors - Munker, Sven; Kilo, Sonja; Roess, Christoph; Jeitner, Peter; Schierl, Rudolf; Göen, Thomas; Drexler, Hans (International Journal of Hygiene and Environmental Health, 2016)
In this study the exposure of the general population in Germany to platinum and rhodium and its determinants was investigated in 259 participants (subdivided in three groups) by urine analyses and assessment of the dental status. Complementary, an interview including questions characterising possible exposure to traffic exhaust was conducted. The median excretion was 2.42ng platinum/g creatinine and 7.27ng rhodium/g creatinine. The detailed analysis of the collected data showed significant higher platinum excretion values with increasing number of surfaces covered with restorations containing precious metals (R=0.389; p<0.001), but also higher values for habitants of urban areas (median=3.43ng/g creatinine; 95th percentile=25.2ng/g) compared with those of rural areas (median=2.06ng/g creatinine; 95th percentile=20.0ng/g). Also, participants working in urban areas showed higher platinum excretion values (median=3.27ng/g; 95th percentile=19.6ng/g). Male participants living and working next to highly frequented roads showed higher rhodium excretion values (median=7.27ng/g; 95th percentile=13.5 ng/g). In summary, the study showed that exhaust emissions have an influence on platinum and rhodium excretion, but for platinum this influence is rather low compared to the influence of precious metals containing restorations.
EVALuna2:9750

Forschungsprojekt „Durch UV-Strahlung induzierte bösartige Hauttumore“ – Berufliche und außerberufliche Exposition gegenüber UV-Strahlung und Hautkrebs - Schmitt, J.; Haufe, E.; Trautmann, F.; Allam, J. P.; Bachmann, K.; Bauer, A.; Bieber, T.; Bonness, S.; Brans, R.; Brecht, B.; Brüning, T.; Bruhn, I.; et al. (Dermatologie in Beruf und Umwelt, 2017)
CRIS-Team Scopus Importer:2020-05-11
Keywords: Basal cell carcinoma; Case-control study; Occupational diasease; Squamous cell carcinoma; UV-irradiation

Fume Events — wie ist der aktuelle Stand? - Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
CRIS-Team Scopus Importer:2020-05-11

Gender differences in teachers´ perceived physical and mental strain - Wischlitzki, Elisabeth; Fischmann, Wolfgang; Voss, Amanda Sophie; Amler, Nadja; Kiesel, Johannes; Drexler, Hans (32. International Commission on Occupational Health (ICOH) Congress, 2018)

Gender influence on health and risk behavior in primary prevention: a systematic review - Hiller, Julia; Schatz, Kathrina; Drexler, Hans (Journal of Public Health, 2017)
Aim Prevention plays a crucial part in healthcare systems and is greatly influenced by the health and risk behavior of the population. The extent to which special tailoring to the addressed subjects would be helpful in improving the effectiveness of prevention measures is unknown. Therefore, the goal of this systematic review is to assess gender-specific differences in primary prevention actions. Subject and Methods A systematic review was conducted in 2015 by searching the PubMed (Medline) and Cochrane Library databases as well as adding additional studies by cross-referencing. The search focused on studies with an analysis of gender differences in health and risk behavior concerning primary prevention. Therefore, major exclusion criteria were single-gender studies, underage (<18 years) study collectives and secondary or tertiary prevention measures. Results In total, 23 studies from 13 different countries were included in the qualitative evaluation. The studies covered 11 different subtopics of primary prevention, but were too diverse in content and type to draw many fundamental conclusions. A meta-analysis was not possible. Generally a tendency for females to be more health-conscious and engaged in preventive behavior could be seen in most subgroups. Conclusion The importance of gender-specific prevention measures for the healthcare system is being increasingly stressed, but only a few studies specifically analyzing the influence of gender on preventive behavior could be identified. To implement appropriate primary prevention measures tailored to gender-specific needs, more details and studies on gender differences are needed.
Keywords: Gender; Primary prevention; Health behavior; Risk behavior

Grenzwerte am Arbeitsplatz und in der Umwelt: Philosophie und Umsetzung - Hartwig, Andrea; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
CRIS-Team Scopus Importer:2020-05-11

Grenzwertevaluierung von Blei - Drexler, Hans; Hartwig, Anna (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2021)
CRIS-Team Scopus Importer:2024-12-16

Grußwort der Deutschen Gesellschaft für Arbeitsmedizin und Umweltmedizin (DGAUM) e.V. - Drexler, Hans; Nesseler, Thomas (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2015)
CRIS-Team Scopus Importer:2020-05-11

Grußwort der wissenschaftlichen Leitung - Drexler, Hans; Wildgans, Hanns (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
CRIS-Team Scopus Importer:2020-05-11

Halfway time in the Bavarian Project Network Ultrafine Particles (BayUFP): Report on the interim appraisal of the research on ultrafine particles Bergfest im Projektverbund BayUFP Bericht zur Zwischenbilanz in der Ultrafeinstaubforschung - Pfleger, Elisabeth; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2022)
CRIS-Team Scopus Importer:2024-12-16

Has dry/cold weather an impact on the skin condition of cleanroom workers? - Weistenhöfer, Wobbeke; Uter, Wolfgang; Drexler, Hans (Journal of Toxicology and Environmental Health-Part A-Current Issues, 2016)
In previous epidemiological studies irritant skin changes were reported significantly more frequently under dry/cold ambient air conditions. The aim of this study was to assess whether a similar effect might be observed in cleanroom workers, occupationally exposed to strictly controlled ambient conditions. This investigation examined 690 employees of a semiconductor production company in Germany, one half in winter (n = 358) and the other half in spring (n = 332). In both waves, both cleanroom workers, who used occlusive gloves predominantly during the entire shift, and employees in the administration, serving as the control group, were included. Ambient outdoor temperature and relative humidity (RH) were measured and absolute humidity (AH) was calculated. Hands were dermatologically examined with quantitative clinical skin score HEROS, supplemented by transepidermal water loss (TEWL) and stratum corneum hydration measurements. Temperature ranged from -5.41 to 6.51°C in winter (RH 71.04-92.38%; AH 2.85-6.7 g/m(3)) and from 6.35 to 10.26°C in spring (RH 76.17-82.79%; AH 5.66-7.92 g/m(3)). Regarding HEROS, TEWL, and corneometry, no marked consistent pattern regarding an enhanced or decreased risk of irritant skin changes was found. Work in a strictly controlled environment with prolonged wearing of occlusive gloves, with clean hands and without exposure to additional hazardous substances, did not seem to negatively affect the skin. In this particular setting, meteorological conditions also did not appear to adversely affect the skin. It is conceivable that wearing of gloves and air conditioning in the plant protect skin of the hands from adverse effects due to dry and cold air encountered when not working.
EVALuna2:9749

Health Literacy and Environmental Risks Focusing Air Pollution: Results from a Cross-Sectional Study in Germany - Pfleger, Elisabeth; Drexler, Hans; Lutz, Regina (International Journal of Environmental Research and Public Health, 2024)
(1) Background: Environmental risks such as air pollutants pose a threat to human health and must be communicated to the affected population to create awareness, such as via health literacy (HL); (2) Methods: We analyzed HL in the context of environmental health risks, including sources of information and prior knowledge, in a sample from the German general population using Kendall’s rank correlations, regression analyses, and explorative parallel mediation analysis; (3) Results: The survey included 412 German participants aged between 18 and 77. HL was found to be problematic to inadequate. The internet, family and friends, and newspapers were the most frequently cited sources of information. Mobile apps were mostly unknown but were requested by sample subjects. Although subjects expressed environmental concerns and exhibited rather good levels of knowledge, the majority perceived no risk to human health and rated air quality quite positively. Knowledge on particulate matter, the term “ultrafine particles”, and protective measures was found to be rather low. HL was associated with the use of newspapers and commercials as sources of information. The relationship between age and HL is fully mediated by the use of newspapers and information from TV commercials; (4) Conclusion: HL should be promoted by raising awareness of the health effects of environmental pollutants. In particular, the information channels preferred by the affected population should be used and further information opportunities such as apps should be publicized, e.g., through campaigns. An improved HL can assist policy makers in creating a healthier environment by empowering individuals to become more environmentally aware and protect their own health. This, in turn, has the potential to reduce health-related costs.<br
Keywords: health literacy; environment; public health; air pollution; particulate matter

Health-oriented leadership, gender-differences and job satisfaction: results from a representative population-based study in Germany - Lutz, Regina; Jungbäck, Nicola; Wischlitzki, Elisabeth; Drexler, Hans (BMC Public Health, 2023)
Background: In recent years, the topic of health-oriented leadership (HoL) has often been investigated with health-related outcomes like general health, strain, depression, and anxiety symptoms. In contrast, research which considers the gender of leaders and employees in connection to HoL as well as studies on relationships between HoL and job satisfaction, are scarce. The aim of this paper is to explore the relationships between HoL and health status assessed by employees and leaders, to analyse the relationships between HoL and job satisfaction as a non-health-related outcome for employees and leaders and to examine differences in the assessment of HoL between men and women in a representative dataset of the working population in Germany. Methods: Data were collected via an access panel as a cross-sectional survey. The quota sample included 643 German workers (managers and employees). We focused on staff-care as a core component of HoL. Statistical analyses were performed using Pearson correlations and regression analyses as well as t-tests and Mann-Whitney-U-Tests. Results: The results showed no significant differences between male and female employees or leaders in assessing HoL. Regarding HoL we found relationships between self-rated health status or job satisfaction, both for the self-rated assessment of leaders and employees. Conclusions: Our findings indicate relationships between HoL and well-being as well as job satisfaction at the workplace. For interventions of any kind, the lack of gender effects leaves a wide scope for the implementation of health-promoting measures. In particular, the findings on the relationship between HoL and job satisfaction through leaders’ self-assessment could be used for salutogenic approaches to strengthen resources in leadership trainings.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Gender differences; Health-oriented leadership; Healthy leadership; Job satisfaction; Leadership style; Self-rated health status

Hemmung der Neurotoxischen Esterase: Bewertung von Studienergebnissen - Weistenhöfer, Wobbeke; Drexler, Hans; Schmitz-Spanke, Simone (61. Jahrestagung der DGAUM, 2021)

Human metabolism and renal excretion of selenium compounds after oral ingestion of sodium selenate dependent on trimethylselenium ion (TMSe) status - Jäger, Thomas; Drexler, Hans; Göen, Thomas (Archives of Toxicology, 2016)
An in vivo metabolism study in humans was carried out to investigate the toxicokinetics and metabolism of sodium selenate differentiating by the trimethylselenium (TMSe) status. Therefore, the changes in blood plasma concentration and the urinary excretion within 24 h of seven healthy subjects after oral administration of a dietary supplement containing sodium selenate (50 ?g selenium) were analyzed. Three subjects belong to the subgroup of TMSe eliminators, and four subjects were related to the non-TMSe eliminators subgroup. The concentrations of total selenium in blood plasma and urine samples were determined by inductively coupled plasma-mass spectrometry (ICP-MS). Additionally, speciation analysis of urine samples was performed using ICP-MS coupled to a liquid chromatography system. Plasma selenium concentration changed from 82.5 ± 12.5 ?g Se/L before to 85.1 ± 12.0 ?g Se/L 2-3 h after supplementation. Considering the individual 24-hour background amounts of renal excreted selenium, the ingestion caused an additional excretion of 15.4 ± 3.3 ?g Se/24 h (?31.1 ± 7.6 % of the administered dose) with a maximum elimination already 2 h after exposure. The differentiated analysis revealed that in all subjects, the main elimination product (30.1 ± 6.9 % of the administered dose) was unmetabolized selenate. TMSe was only detected in the urine of the TMSe eliminators. This subgroup excreted in comparison with the non-TMSe eliminators a significantly lower amount of selenate. Only one subject metabolized selenate to a larger portion to methyl-2-acetamido-2-deoxy-1-seleno-?-D-galactopyranoside (SeSug1) and methyl-2-amino-2-deoxy-1-seleno-?-D-galactopyranoside (SeSug3). All other subjects showed only a minor metabolism of selenate to selenium-containing carbohydrates. By individuals, which do not excrete TMSe in urine basically, selenate is metabolized only marginally and is excreted rapidly via urine generally. In contrast, a considerable portion of this inorganic selenium compound is metabolized by individuals, which eliminate TMSe basically. An elevated metabolism may also be provided by individuals, which eliminate high levels of selenium-containing carbohydrates basically. The difference in metabolism may imply a different disposition for pharmacological or toxic effects by exposure to inorganic selenium compounds.
EVALuna2:9739

Human metabolism and renal excretion of selenium compounds after oral ingestion of sodium selenite and selenized yeast dependent on the trimethylselenium ion (TMSe) status - Jäger, Thomas; Drexler, Hans; Göen, Thomas (Archives of Toxicology, 2016)
A human in vivo metabolism study was carried out to investigate the impact of the trimethylselenium ion (TMSe) status on metabolism and toxicokinetics of sodium selenite and selenized yeast. Nine healthy human volunteers were orally exposed to 200 µg selenium as sodium selenite and seven with selenized yeast (100 µg selenium). In each intervention group, three subjects belong to TMSe eliminators. Blood samples were withdrawn before and up to 6 h after administration. Urine samples were collected before and within 24 h after administration. Total selenium (Se) was quantified in blood plasma and urine and low molecular Se species in urine. Selenium concentration in plasma increased from 84.5 ± 13.2 µg Se/L before to 97.4 ± 13.2 µg Se/L 2-3 h after selenite supplementation and 89.5 ± 12.9 µg Se/L to 92.1 ± 13.9 µg Se/L after selenized yeast intake. The oral ingestion caused an additional Se elimination via urine of 16.9 ± 10.6 µg/24 h (TMSe elim.: 10.8 ± 6.9 µg/24 h; non-TMSe elim.: 20.0 ± 11.3 µg Se/24 h) after selenite exposure and 11.8 ± 4.1 µg/24 h (TMSe elim.: 10.8 ± 4.6 µg/24 h; non-TMSe elim.: 12.6 ± 4.2 µg Se/24 h) after selenized yeast exposure. Methyl-2-acetamido-2-deoxy-1-seleno-?-D-galactopyranoside (SeSug1) was the main metabolite in all urine samples, whereas TMSe was another main metabolite in TMSe eliminators' urine. After selenite exposure, a small amount of the dose (0.5 ± 0.2 %) was oxidized to selenate and rapidly excreted via urine. With the exception of selenite exposure in TMSe eliminators, the comparison of total Se and the sum of quantified Se species revealed a high renal portion of unidentified species. The study indicated a different metabolism of inorganic and organic Se compounds in human, but also crucial differences of Se metabolism in TMSe eliminators and non-TMSe eliminators.
EVALuna2:9741

Human urinary and blood toxicokinetics of beryllium after accidental exposure - Hiller, Julia; Naglav-Hansen, Dominik; Drexler, Hans; Göen, Thomas (Journal of Trace Elements in Medicine and Biology, 2023)
Purpose: Beryllium is known to have adverse health effects and is classified as carcinogenic to humans. However, data on systemic beryllium exposure in humans are rare and especially human toxicokinetics are largely uncharted. As such, the first reported multi-annual course of blood and urine concentrations after a high exposure scenario provides important new insights. Methods: For a medical follow-up biomonitoring samples were collected for 56 months from a male subject after an accidental and multi-faceted high exposure. Sampling started on day 2 post-exposure for urine and day 147 for blood. The samples were analyzed by inductively coupled mass spectrometry (ICP-MS) and plotted longitudinally as a function of time. Terminal half-lives were calculated assuming a first-order elimination process. Main findings: Both matrices showed highly increased initial concentrations (about 100-fold), despite the 147-day delay in blood sampling, and a marked decline over time. In urine, a two-phase excretion process was suspected based on the longitudinal data. Calculations gave terminal half-lives of 117.5 days and 666.5 days for phases 1 and 2, respectively. Blood kinetics called for a terminal half-life of 103.5 days. Elimination kinetics in blood and urine were comparable, simultaneously gathered samples showed an excellent correlation (R² = 0.985). Principal conclusions: The long-term follow-up after a high initial exposure to beryllium provides the first detailed insights into the elimination course of systemically available beryllium in humans. Conform kinetics of beryllium in urine and blood and the strong correlation between both parameters indicate high data validity and support the good representation of the current systemically available beryllium by urine and blood concentration in humans. The relatively long terminal half-lives in both matrices suggest a possible accumulation in humans in case of repeated exposures.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Beryllium; Blood; Human; Toxikokinetic analysis; Urine

Hürden versus Ressourcen der Maßnahmenimplementierung im Rahmen der Gefährdungsbeurteilung psychischer Belastungen bei Lehrkräften - Wischlitzki, Elisabeth; Fischmann, Wolfgang; Drexler, Hans (54. Jahrestagung der Deutschen Gesellschaft für Sozialmedizin und Prävention, 2018)

Identifikation von Merkmalen psychisch stark beanspruchter Beschäftigter in kleinen und mittelständischen Unternehmen - Voss, Amanda Sophie; Amler, Nadja; Wischlitzki, Elisabeth; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2019)
Objective: The psychosocial risk assessment should contribute to keeping work-related influences on employees at a low level and avoiding stress. Whether or not mental stress places undue mental strain on employees depends, amongst other things, on their individual requirements. The objective of this work is to identify characteristics of employee groups subject to high levels of mental stress as a basis for targeted measures in workplace health promotion and prevention. Method: A questionnaire was used to collect data on mental stress and strain from n = 1280 employees in 12 small and medium-sized enterprises (SMEs). A subgroup with a higher level of mental strain and a subgroup with a lower level of mental strain were identified by means of a hierarchical cluster analysis. The two groups were then compared in terms of differences in mental stress and resources. Results: Various factors such as pressure of work, lack of resources and health problems occur simultaneously in the cluster with a higher level of mental strain, which are in the end accompanied by a worse global assessment of the workplace. Men and persons over the age of 50 have a greater tendency to be in the high-strain group. With regard to the areas that typically cause mental stress, the group subject to strain report the highest/most frequent pressures in the area of “work organisation”, in particular for work under time pressure and work interruptions. In terms of resources, there are only small effects with consistently significant differences. Conclusions: The results confirm the preferred approach of WHM, which is to implement measures focusing on working conditions, and at the same time underline the importance of behavioural strategies. Employers should take into account that some employees are more sensitive to working conditions than others. A healthy corporate culture with a holistic WHM system and an attentive company medical officer should always have their specific needs in mind in order to keep them healthy and efficient for as long as possible.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Mental strain; Psychosocial risk assessment; SME; Workplace health management

IKKA-Score zur Vereinheitlichung der Beurteilung des individuellen Risikos durch SARS-CoV-2 - Wolfschmidt, Anna; Ochmann, U.; Nowak, D.; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2020)
Zielstellung: Die Einschätzung des individuellen Risikos für einen schweren Verlauf der Coronavirus-Krankheit-2019 (COVID-19) stellt hohe Anforderungen an die beurteilenden Ärztinnen und Ärzte. Das erarbeitete Score-System soll eine Hilfestellung zur Vereinheitlichung der Risikobeurteilung bieten, die übersichtlich und effizient genug ist, um einen Einsatz im Praxisalltag zu ermöglichen. Methoden: Die Entwicklung des IKKA-Scores erfolgte in vier Schritten. In Schritt 1 wurden vier Tätigkeitsgruppen definiert, die die Einsatzmöglichkeiten der Beschäftigten festlegen. In einem zweiten Schritt wurden Risikofaktoren bestimmt, für die eine Erhöhung der SARS-CoV-2-assoziierten Schutzbedürftigkeit anzunehmen ist, und vier Score-Kategorien festgelegt. Schritt 3 umfasste die Zuordnung von Punktwerten je nach Ausmaß der anzunehmenden Schutzbedürftigkeit innerhalb der Score-Kategorien. Abschließend wurden in Schritt 4 die erzielten Summenwerte des IKKA-Scores den vier Tätigkeitsgruppen zugeordnet. Ergebnisse: Der IKKA-Score setzt sich aus den vier Kategorien Immunsuppression (I), Krankheitsschwere bestehender Vorerkrankungen (II), Komorbiditäten/Risikofaktoren gemäß Robert Koch-Institut (RKI) (III) und Alter (IV) zusammen. In diesen Kategorien werden von der Ärztin/dem Arzt Punktwerte je nach Ausmaß der Risikofaktoren vergeben. Anhand der Score-Summe erfolgt die Zuteilung der Beschäftigten zu einer von vier Tätigkeitsgruppen. Von den personalverantwortlichen Vorgesetzten können den Tätigkeitsgruppen auf Basis der Gefährdungsbeurteilung risikoadaptiert Einsatzmöglichkeiten zugewiesen werden. Schlussfolgerung: Mit dem IKKA-Score wird Ärztinnen und Ärzten eine Entscheidungshilfe für die Beurteilung des individuellen Risikos durch SARS-CoV-2 zur Verfügung gestellt. Die Stärke des IKKA-Scores liegt in der Vereinheitlichung der Risikobeurteilung unter möglichst großer Übersichtlichkeit und geringem Zeitaufwand sowie in der Berücksichtigung bereits existenter Empfehlungen des Bundesministeriums für Arbeit und Soziales (BMAS).
CRIS-Team Scopus Importer:2024-12-16
Keywords: COVID-19; risk assessment; SARS-CoV-2; score

Immunity against vaccine-preventable diseases among pregnant employees in Germany. A situation analysis before the introduction of the Measles Protection Act - Wolfschmidt-Fietkau, Anna; Goertz, Ruediger S.; Goertzen, Stephanie; Schmid, Klaus; Seidling, Marie; Gherman, Elsa; Ochmann, Uta; Drexler, Hans (Vaccine, 2024)
Background: Immunization against vaccine-preventable diseases prior to pregnancy is an important measure of primary prevention both for the mother and the unborn child. We analyzed immunity rates against measles, mumps, rubella, varicella, and pertussis in pregnant employees in Germany prior to significant changes in legal conditions in 2020, to provide a basis of comparison for future research. Methods: We analyzed occupational-medical routine data in three collectives of pregnant women with an occupational risk of infection in the years 2018 and 2019: 1: hospital staff with regular access to an in-house company physician (n = 148); 2: employees in childcare with regular access to external occupational-health services (n = 139); 3: teachers with no regular access to occupational healthcare (n = 285). Immune status was assessed by a physician based on vaccination certificates, laboratory results, and medical documentation on prior infections. We compared immunity rates against measles, rubella, varicella, and pertussis as well as full immunity against all targeted vaccine-preventable diseases. Results: Altogether, n = 572 pregnant women were included in our study. Of these women, 96.5 % were immune to rubella, 95.8 % to varicella, 88.3 % to measles, 82.7 % to mumps, and 67.8 % to pertussis. Only 56.2 % of the women had full immunity against all targeted vaccine-preventable diseases. Collective 1 showed the highest immunity rates against measles and pertussis as well as the highest rate of full immunity against all targeted vaccine-preventable diseases. The immunity rates against rubella and varicella did not differ significantly between the collectives. With the exception of rubella, the lowest immunity rates during pregnancy were found in Collective 3. Conclusion: We found pregnancy-relevant immunity gaps in all our study groups with significant differences between the collectives. Considering the potentially devastating consequences of infections during pregnancy, all medical professionals and health-policy makers should be involved in an increased effort to improve vaccination rates prior to pregnancy.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Immunity; Infection prevention; Occupational medicine; Pregnancy; Vaccination

Immunity Protection of Pregnant Employees Working in the Healthcare Sector - Seidling, Marie; Goertzen, Stephanie; Schmid, Klaus; Drexler, Hans; Wolfschmidt, Anna (Geburtshilfe und Frauenheilkunde, 2025)
Background Infectious diseases during pregnancy can pose a serious health risk for mother and child. Employees with an occupational risk of infection are especially at risk. We investigated the immune status of pregnant employees working in the health service to determine the percentage of women who were adequately protected during pregnancy and the percentage of cases with a pregnancy-relevant risk. Methods This retrospective data collection was done using the standard records of the Occupational Health Department (Betriebsärztliche Dienststelle) of Friedrich-Alexander-Universität Erlangen-Nürnberg, Germany. The data of employees with a pregnancy reported between 1 May 2018 and 31 May 2020 were collected. This resulted in a total study population of 406 cases. We collected data on the respective occupational groups, occupational risk profile, employment bans for expectant mothers, occupational-medical consultations, and immunity status with regards to measles, mumps, rubella, varicella zoster virus, parvovirus B19, CMV, hepatitis A and B, tetanus, diphtheria, pertussis, and poliomyelitis. Results The investigated employees had attended a mean of three previous occupational-medical consultations; 45.8% had received advice about maternity protection from the occupational physician's office. The immunity rates of the total study population at the time of their last medical consultation prior to their due date varied, depending on the respective disease, from 77.3% (mumps) to 90.9% (varicella zoster virus). 182 cases (44.8%) were prohibited from working during their further pregnancy. Conclusion Medical advice on infection risks and immunization combined with the offer of vaccinations are decisive in determining the immune status and ensure that immunizations can be carried out in good time. To achieve full immunization before becoming pregnant, girls and women should be advised early on about preventive maternity protection measures.
CRIS-Team Scopus Importer:2025-03-14
Keywords: employment ban; health service; immunity; infections; occupational medicine; pregnancy

Impact of Daily Antiperspirant Use on the Systemic Aluminum Exposure: An Experimental Intervention Study - Letzel, Maximilian; Drexler, Hans; Göen, Thomas; Hiller, Julia (Skin Pharmacology and Physiology, 2020)
Background and Objectives: Adverse health effects such as neurotoxic and carcinogenic effects through aluminum from cosmetic products have been repeatedly discussed. The dermal uptake and impact on the systemic aluminum load is still poorly understood. Therefore, we investigated the effect of daily antiperspirant use on the systemic aluminum load under real-life conditions. Methods: 21 healthy subjects meeting certain selection criteria to ensure a low systemic aluminum background load were asked to use a commercial aluminum-containing antiperspirant for 14 days. A questionnaire enquired about shaving habits and other sources of aluminum. Aluminum levels were measured before and after the exposure in 24-h urine and plasma using atomic absorption spectroscopy. Urine samples (n = 6) with <700 mg/day creatinine excretion or more than 30% difference in 24-h creatinine excretion were excluded from further analysis. Results: No significant increase in plasma aluminum concentration or total excreted aluminum per day before and after exposure was measurable. No sample exceeded the reference values of the general population (maximum: 9.42 μg/g creatinine and 2.1 μg/L plasma). Shaving habits did not have a significant influence on the systemic aluminum load. Also, no correlation between the total amount of antiperspirant applied and the systemic aluminum level could be demonstrated. Conclusions: No measurable contribution to the overall systemically available aluminum load due to daily use of an antiperspirant for 14 days could be shown, but real-life data concerning long-term use or higher concentrations are still lacking. Considering toxicological occupational exposure data, adverse neurotoxic changes are unlikely in the case of urinary excretion of <50 μg aluminum/g creatinine (= no observed adverse effect level), even following long-term exposure.
CRIS-Team Scopus Importer:2019-10-08

Impact of physiologically relevant temperatures on dermal absorption of active substances - an ex-vivo study in human skin - Kilo, Sonja; Wick, J.; Mini Vijayan, Suvarna; Göen, Thomas; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans (Toxicology in Vitro, 2020)
Skin temperature plays a certain role in the dermal absorption of substances, but the extent and mechanisms of skin temperatures-induced modulation in ranges caused by physiological thermoregulation or environmental conditions are largely unknown. The influence of dermal temperature on the absorption of the model lipophilic compound (anisole) and the model hydrophilic compounds (1,4-dioxane, ethanol) through human skin was investigated at three dermal temperatures (25, 32 and 39 °C) in an ex-vivo diffusion cell model. The substances were applied to the skin and transdermal penetration was monitored. All substances showed temperature dependent variations in their penetration behavior (3 h: 25–39 °C: 202–275% increase in cumulative, transdermally penetrated amounts). The relative differences in absorption in relation to temperature were greatest within 45 min after exposure (25–39 °C: 347–653% rise in cumulated penetration), although absolute amounts absorbed were small (45 min vs. 3 h: 4.5–14.5%). Regardless of blood circulation, skin temperature significantly influences the amount and kinetics of dermal absorption. Substance-dependent, temperature-related changes of the lipid layer order or the porous pathway may facilitate penetration. The early-stage modulation of transdermal penetration indicates transappendageal absorption, which may be relevant for short-term exposures. For both, toxicological evaluation and perfusion cell studies, it is important to consider the thermal influence on absorption or to perform the latter at a standardized temperature (32±1 °C).
CRIS-Team Scopus Importer:2020-09-11
Keywords: Dermal absorption; Diffusion cell; Influence of temperature; Transdermal penetration

Impact of skin temperature and intradermal pH on transdermal fluoride absorption following hydrofluoric acid exposure: An ex vivo diffusion cell study in human skin - Mini Vijayan, Suvarna; Wolfschmidt, Anna; Göen, Thomas; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans; Kilo, Sonja (Toxicology Letters, 2025)
Accidents involving hydrofluoric acid (HF) can cause systemic poisoning due to the transdermal absorption of fluoride ions. The present study investigates the impact of skin temperature and intradermal pH on fluoride absorption and its kinetics. Human skin was exposed to 30 % HF for 3 minutes using a static diffusion cell model. The study compared cumulative fluoride absorption at two different skin temperatures (24°C and 32°C) and two intradermal pH values (6.5 and 7.2). Experiments were performed at least three times per treatment and per donor (n = 5), over a duration of 8 h and 12 h for pH and temperature experiments, respectively. Results showed that fluoride absorption increased with temperature, with a ∼17.8 % increase in cumulative penetration at 32°C compared to 24°C. The maximum flux rate through the skin was reached within the first hour and was ∼54 % lower at 24°C. Additionally, acidifying the skin to an intradermal pH of 6.5 led to a significant increase in cumulative fluoride absorption by ∼12.6 % and a ∼50.3 % increase in the maximum flux rate. The findings suggest that reducing fluoride absorption after accidental skin contact with HF may be achieved by lowering skin temperature and buffering intradermal pH to a physiological level. These results have important implications for first-aid measures in real-life scenarios involving HF exposure. Controlling skin temperature by cooling and intradermal pH with the addition of buffering agents may enhance decontamination strategies.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Clinical significance; Ex Vivo human skin; Franz Diffusion cell; Hydrofluoric acid; Intradermal pH; Skin temperature; Transdermal fluoride absorption

Importance of Exposure Level for Toxicological Risk Assessment - Drexler, Hans; Shukla, Anuradha (Springer International Publishing, 2021)
A health risk for an individual due to an exposure to a hazardous substance depends upon the properties of the substance, the amount of the substance, and the susceptibility of the individual. If an individual is susceptible to a particular hazardous substance only the amount of the substance determines the risk resulting from the exposure to this substance. In the case of local effects the concentration of the hazardous substance in the environment and the duration of the contact determine the risk, with the exception of allergic reactions where the susceptibility is more significant. In the case of systemic effects only the internal exposure or dose is relevant for the risk. Therefore, it is important for the marker of exposure to be a good surrogate for the dose in the target organ. If appropriate methods are available a biological monitoring is more significant for risk assessment as compared to ambient monitoring. If biomarkers of effect are available not only the general but also the individual risk can be assessed.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Dermal absorption; DNA adducts; Effect monitoring; Individual exposure; Internal exposure; Protein adducts; Sensitization; Susceptibility

Incidence and Mortality in Relation to the Density of Dermatologists in Bavaria - Drexler, K.; Drexler, Hans; Berneburg, M.; Apfelbacher, C.; Haferkamp, S. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Incidence and Mortality of Malignant Melanoma in Relation to Dermatologist Density in Bavaria - Drexler, Konstantin; Drexler, Hans; Geissler, Edward K.; Berneburg, Mark; Haferkamp, Sebastian; Apfelbacher, Christian (Advances in Therapy, 2021)
Introduction Malignant melanoma is an aggressive skin tumor with a good prognosis when treated in an early tumor stage, but has a poor prognosis with distant metastases. The incidence of malignant melanoma has increased continuously over the last decades, with little change in mortality. One explanation for this is that melanomas are increasingly detected in early stages, especially after the establishment of statutory skin cancer screening in 2008, which allows a free skin examination every 2 years for people older than 35 years. Methods In this study incidence and mortality of malignant melanoma were correlated with the dermatologist density in Bavarian administrative regions. In addition, the incidence data were compared before and after the introduction of statutory skin cancer screening. Results There was a significant correlation between the incidence of malignant melanoma and dermatologist density (r = 0.258, p = 0.044), but no correlation between mortality and dermatologist density (r = 0.201, p = 0.121). Similarly, the increase of malignant melanoma incidence following the introduction of statutory skin cancer screening in 2008 was independent of dermatologist density (r = 0.021, p = 0.873). Conclusion The dermatologist density in Bavaria correlates positively with the incidence of malignant melanoma. Despite an increased incidence, mortality was not elevated in the respective administrative regions.
CRIS-Team WoS Importer:2021-10-15

Incidence and mortality of melanoma proportional to the catchment area of dermatologists in Bavaria - Drexler, K.; Drexler, Hans; Berneburg, M.; Apfelbacher, C. J.; Haferkamp, S. (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

Increased intima-media thickness in rayon workers after long-term exposure to carbon disulfide - Schramm, Axel; Uter, Wolfgang; Brandt, Meike; Göen, Thomas; Köhrmann, Martin; Baumeister, Thomas; Drexler, Hans (International Archives of Occupational and Environmental Health, 2016)
Long-term exposure to carbon disulfide (CS2) is associated with increased cardiovascular mortality. However, previous studies on actual vascular changes showed heterogeneous results. Intima-media thickness of the carotid arteries (IMT) represents an established marker of atherosclerosis and a reasonable surrogate marker for cardiovascular risk. IMT was examined in a large cohort of CS2 exposed workers and the association with cumulative CS2 exposure analysed.In a cross-sectional examination, 290 exposed and 137 non-exposed workers in a German rayon-manufacturing plant were assessed. Individual cumulative exposure was calculated from this assessment combined with the results of two cross-sectional studies in 1992 and 1999 and department-specific annual means of ambient (CECS2) and individual biological (CETTCA) monitoring results obtained 1992-2009. Furthermore, cumulative duration of working in CS2-exposed departments (CEYEARS) was calculated. Examination included assessment of a broad set of known cardiovascular risk factors and IMT measurement of the carotid arteries on both sides. Multiple linear regression analyses were performed with IMT as outcome and three variants of cumulative exposure (duration of exposure, cumulative CS2, and cumulative TTCA) as well as categorised maximum CS2 exposure, all adjusted for cardiovascular risk factors.All models of cumulative exposure showed a significant increase in IMT in the group with the highest level of exposure: CEYEARS > 20 years, ? = 0.045 mm; CECS2 > 270 ppm × years, ? = 0.052 mm; CETTCA > 33 mg/g creatinine × years, ? = 0.038 mm. Alternatively, addressing maximum exposure, workers with CS2 exposure of >10 ppm in at least 3 years exhibited a significant IMT increase (? = 0.068 mm).Long-term CS2 exposure is an independent risk factor concerning IMT changes. The amount of IMT increase, in a similar range as that associated with other cardiovascular risk factors, might be clinically relevant.
EVALuna2:5493

Indoor pollutants as presenting consultation issue in an environmental and occupational medicine outpatient clinic Innenraumschadstoffe als Konsultationsanlass in einer umwelt-, arbeits- und sozialmedizini-schen Sprechstunde - Greiner, Annette; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
Aim: Most adults spend about 90% of their time indoors, which is why indoor air should not have negative effects on health. The aim of this single-centre study was to find out what proportion of patients in an outpatient clinic for environmental and occupational medicine had indoor-associated complaints. We wanted to identify common complaints, the indoor areas where these complaints occurred, and the noxious agents on which the patients blamed these complaints. Group and Method: The files of 623 outpatients seen in the Erlangen institute and outpatient clinic for occupational, social, and environmental medicine from 2012 to 2016 were evaluated retrospectively, and patients with indoor-associated complaints were identified. Patients with social medicine-related issues were excluded. Results: 162 of 623 patients were presenting with indoor-associated health disorders: of these, 89 patients had environmental medicine issues, 52 patients had occupational disorders and 21 patients presented with combined issues. For environmental medicine patients, the share of indoor-associated i health complaints was 35% in 2012, increasing to 53% in 2016. The most frequent reason for attending the clinic was mould (32 patients), followed by PCP/lindane (31 patients). Other causes reported by patients included odours, renovation works, unusual readings from indoor air moni- i toring or materials sampling, influences from outdoor air, formaldehyde or pyrethroids. Most patients complained about respiratory (71%) and neu- i rological problems (35%) such as polyneuropathy, paraesthesia or vertigo. Conclusions: There is a strong need for soundly-based advice drawing on the latest science for patients experiencing indoor-associated complaints and having contact with noxious indoor agents.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Indoor air-environmental medicine-mould-PCP-odours

Influence of artificial sebum on the dermal absorption of chemicals in excised human skin: A proof-of-concept study - Schneider, Daniela; Dennerlein, Kathrin; Göen, Thomas; Schaller, Karl-Heinz; Drexler, Hans; Korinth, Gintautas (Toxicology in Vitro, 2016)
In an initial diffusion cell study, the influence of artificial sebum on dermal penetration and intradermal reservoir of ethanol and toluene was investigated in comparison with the effects of a skin cream (o/w- and w/o-emulsion) and untreated (control) skin. Human skin was exposed to neat ethanol and toluene for 4h, respectively. During the experiments, the penetration of the compounds was assessed in the receptor fluid. The amounts of the test compounds in the skin were determined at the end of exposure. In the control experiments, 42% of the total resorbed ethanol amounts were found in the intradermal reservoir after 4h, whereas 82% of the toluene amounts were found in the skin compartments. The treatment with artificial sebum showed no significant differences in dermal absorption of both test compounds compared to control skin. In contrast, the treatment with skin cream increased the percutaneous penetration (p<0.001) and the intradermal reservoir of ethanol 2-fold but not of toluene. In all exposure scenarios, a relevant intradermal reservoir was formed. The results indicate that sebum does not influence the percutaneous penetration and the intradermal reservoir of epidermally applied chemicals, whereas the application of skin creams may increase the dermal penetration of the compounds.
EVALuna2:9746

In Reply - Drexler, Hans (Deutsches Ärzteblatt international, 2018)
CRIS-Team Scopus Importer:2020-05-11

Intradermal and transdermal absorption of beta-naphthylamine and N-Phenyl-beta-naphthylamine in a viable human skin model - Mini Vijayan, Suvarna; Baierl, Moritz; Göen, Thomas; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans; Kilo, Sonja (Toxicology in Vitro, 2024)
Technical products containing N-Phenyl-beta-naphthylamine (PBNA) are contaminated with beta-naphthylamine (BNA), a known carcinogen. Both amines penetrate the skin to different degrees, but little is known about their dermal-depot formation. This study investigated the dermal penetration of PBNA and its degradation product BNA using a viable human-skin model. PBNA (259 μg) or BNA (0.52 μg) in n-hexane and industrial grease were applied to freshly excised human skin (n = 6, 0.64 cm2) for 2-72 h. After temporary/continuous and single/repeated exposure, samples were taken (stratum corneum, epidermis/dermis, receptor fluid) and analyzed for their amine content by GC–MS. Continuous exposure led to a PBNA dermal depot of ∼47 μg/cm2 over 72 h. Temporary applications also resulted in lower but consistent PBNA dermal depots. A single 2-h application resulted in a dermal depot of ∼16 μg/cm2 after 72 h, while this was ∼25 μg/0.64 cm2 with repeated applications. BNA behaved differently; with repeated 2-h applications, intradermally retained BNA initially increased 3–6 fold, then dropped to ∼200–250 ng/cm2. This incomplete decline upon repeated short-term exposure to PBNA suggests that a BNA dermal depot is formed either due to contamination of PBNA with BNA or to enzymatic conversion of PBNA to BNA. Additionally, PBNA dermal depots were saturable under the given conditions. These findings highlight the importance of understanding the dermal-exposure dynamics of potential carcinogenic compounds in industrial settings.
CRIS-Team Scopus Importer:2024-10-18
Keywords: beta-naphthylamine; Dermal depot; Intradermal penetration; N-Phenyl-beta-naphthylamine; Transdermal absorption; Viable skin

Ionizing radiation and skin cancer—a review of current evidence - Caramenti, Luca; Breckow, Joachim; Hildebrandt, Guido; Drexler, Hans; Volkmer, Beate; Hauptmann, Michael (Journal of Radiological Protection, 2024)
Cancer of the skin represents a challenge for radiological protection, as it is very common and involves the largest organ of the human body, which is exposed to environmental stress, including ionizing radiation (IR). The most common subtypes, basal cell carcinoma (BCC) and squamous cell carcinoma (SCC), have very low mortality. Current consideration of skin cancer in radiological protection is mainly based on data from the 1990s, which indicate that BCC may be induced by IR, SCC is only weakly associated with IR, and malignant melanoma (MM) is not considered as IR-induced. In a semi-systematic review of the evidence between 1990 and 2023, we snowballed 20 index articles. We identified 33 articles with information on a potential dose-response relationship between skin cancer and IR exposure and assessed the evidence for a causal association. Exposure situations included a-bomb survivors, therapeutic and occupational exposure (airlines, nuclear and medical facilities) and residents exposed to radon or other radiation sources. There is currently no epidemiological evidence that MM or SCC are caused by IR. The only skin cancer type with evidence for a causal relationship is BCC, and evidence is limited to exposures above about 0.5 Gy with a wide range of risk levels per dose. Thus, IR-inducible skin cancer refers to BBC only and only at levels of exposure beyond those experienced by the vast majority of people exposed today.
CRIS-Team Scopus Importer:2024-11-08
Keywords: ionizing radiation; semi-systematic review; skin cancer

Is ultraviolet exposure acquired at work the most important risk factor for cutaneous squamous cell carcinoma? Results of the population-based case-control study FB-181 - Schmitt, J.; Haufe, E.; Trautmann, F.; Schulze, H. -J.; Elsner, P.; Drexler, Hans; Bauer, A.; Letzel, S.; John, S. M.; Fartasch, M.; Bruening, T.; Seidler, A.; et al. (British Journal of Dermatology, 2018)
BACKGROUND: Squamous cell carcinoma (SCC) is one of the most frequent types of cancer constituting a significant public health burden. Prevention strategies focus on limiting ultraviolet (UV) exposure during leisure time. However, the relative impact of occupational and nonoccupational UV exposure for SCC occurrence is unclear. OBJECTIVES: To investigate the association between occupational and nonoccupational UV exposure for SCC in a multicentre population-based case-control study hypothesizing that high occupational UV exposure increases the risk of SCC. METHODS: Consecutive patients with incident SCC (n = 632) were recruited from a German national dermatology network. Population-based controls (n = 996) without history of skin cancer were recruited from corresponding residents' registration offices and propensity score matched to cases. Lifetime UV exposure, sociodemographic and clinical characteristics were assessed by trained physicians. Occupational and nonoccupational UV exposure doses were estimated by masked investigators using established reference values. Odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were assessed using conditional logistic regression adjusting for relevant confounders. RESULTS: Total solar UV exposure was significantly associated with increased SCC. The OR for high (> 90th percentile) vs. low (< 40th percentile) and high vs, moderate (40-59th percentile) occupational UV exposure was 1·95 (95% CI 1·19-3·18) and 2·44 (95% CI 1·47-4·06) for SCC. Adjusting for occupational UV exposure, nonoccupational UV exposure was not significantly related to SCC incidence. Dose-response relationships were observed for occupational but not for nonoccupational solar UV exposure. CONCLUSIONS: Solar occupational UV exposure is a major determinant of incident SCC. Our findings indicate that prevention strategies should be further expanded to the occupational setting.
EVALuna2:34673

Jahrestagung der DGAUM 2016 in münchen: Kommen sie zur Mitgliederversammlung am Mittwoch, 09. März 2016! - Drexler, Hans; Nesseler, Thomas (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2016)
CRIS-Team Scopus Importer:2020-05-11

Konzept für ein ganzheitliches Gesundheitsmanagement in KMU - Fischmann, Wolfgang; Voss, Amanda Sophie; Drexler, Hans (Public Health Forum, 2020)
Company health management is often not established in small and medium-sized companies. For the meaningful implementation of associated content and processes, know-how would have to be built up and resources needed to be invested that often do not exist. As part of the "RegioKMUnet" research and development project, a concept was developed on its basis SMEs can get to health management more easily and efficiently.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Health management; Health management measures; Networks; Risk assessment of psychological stress; Small and medium-sized enterprises

Koordination und Kommunikation im UFP-Projektverbund - Pfleger, Elisabeth; Drexler, Hans (2020)

Künstliche UV-Strahlung durch Schweißen und Aderhaut-Melanome: Eine wissenschaftliche Bewertung des Zusammenhangs auf Basis des deutschen Berufskrankheitenrechts - Hiller, Julia; Drexler, Hans; Weistenhöfer, Wobbeke (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2016)
Background: The ..International Agency for Research on Cancer" (IARC) has established a causal relationship between welding and the occurrence of uveal melanoma and it classified welding as a human carcinogen in its Monographs 100D (2012). A literature review has now been undertaken as to whether uveal melanoma caused by welding meets the requirements for being recognised as an occupational disease under German legislation. Method: A systematic literature search was conducted on the association between the risk of a uveal melanoma and welding. Findings: An association between welding or photokeratitis (inter alia through welding) and uveal melanoma was investigated in multiple case-control studies and one meta- Analysis. Although predominantly positive associations were found, the causation was greatly limited by the frequent lack of statistical significance in the findings, the overlap of some study collectives and uncertain pathomechanisms. It is not currently possible to infer with sufficient certainty that welders have a considerably higher (= double) risk of job-related uveal melanoma. Conclusion: Current literature varies in terms of the nature and strength of a causal relationship between welding and the risk of a uveal melanoma and does not meet the scientific requirements of German occupational disease legislation. Further critical monitoring and research is needed regarding the pathogenic agent, a mechanism of action, a dose-effect relationship and the exact extent to which occupation is relevant.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Causation; Occupational disease; Photokeratitis; Uveal melanoma; Welding

Lead, cadmium, mercury, and chromium in urine and blood of children and adolescents in Germany - Human biomonitoring results of the German Environmental Survey 2014-2017 (GerES V). - Vogel, Nina; Murawski, Aline; Schmied-Tobies, Maria I. H.; Rucic, Enrico; Doyle, Ulrike; Kaempfe, Alexander; Hoera, Christian; Hildebrand, Jörg; Schäfer, Moritz; Drexler, Hans; Göen, Thomas; Kolossa-Gehring, Marike (International Journal of Hygiene and Environmental Health, 2021)
Metals reach humans through food and drinking water intake and inhalation of airborne particles and can have detrimental health effects in particular for children. The metals presented here (lead, cadmium, chromium, and mercury) could lead to toxic effects such as neurotoxicity, mutagenicity, and have been classified as (possible) carcinogens. Using population representative data from the German Environmental Survey 2014-2017 (GerES V) from 3- to 17-year-old children on lead and cadmium in blood (n = 720) and on cadmium, chromium, and mercury in urine (n = 2250) we describe current internal exposure levels, and socio-demographic and substance-specific exposure determinants. Average internal exposure (geometric means) in blood was 9.47 μg/L for lead and below 0.06 μg/L (limit of quantification) for cadmium, and in urine 0.072 μg/L for cadmium, 0.067 μg/L for mercury, and 0.393 μg/L for chromium, respectively. Younger children have higher concentrations of lead and chromium compared to 14-17-year-old adolescents, and boys have slightly higher mercury concentrations than girls. With respect to substance specific determinants, higher lead concentrations emerged in participants with domestic fuel and in non-smoking children with smokers in the household, higher levels of cadmium were associated with smoking and vegetarian diet and higher levels of mercury with the consumption of seafood and amalgam teeth fillings. No specific exposure determinants emerged for chromium. The health based guidance value HBM-I was not exceeded for mercury and for cadmium in urine it was exceeded by 0.6% of the study population. None of the exceedances was related to substantial tobacco smoke exposure. Comparisons to previous GerES cycles (GerES II, 1990-1992; GerES IV, 2003-2006) indicate continuously lower levels.
EVALuna2:470402

Legal Changes in Occupational Diseases - Effects on the Assessment of the Reduction in Earning Capacity (MdE) in the case of work-related Skin Diseases within the Meaning of BK No. 5101 Case Studies and new Obligations to Cooperate - Krohn, S.; Skudlik, C.; Bauer, A.; Bernhard-Klimt, C.; Dickel, H.; Drexler, Hans; Elsner, P.; Engel, D.; Fartasch, M.; Glaubitz, S.; Gauglitz, G.; Goergens, A.; et al. (Dermatologie in Beruf und Umwelt, 2021)
CRIS-Team WoS Importer:2021-10-01

Legal term / interpretation "Serious or recurrent skin disease" from January 1, 2021: Consultation result of the Bamberg AG recommendation - Skudlik, C.; Krohn, S.; Bauer, A.; Bernhard-Klimt, C.; Dickel, H.; Drexler, Hans; Elsner, P.; Engel, D.; Fartasch, M.; Glaubitz, S.; Gauglitz, G.; Goergens, A.; et al. (Dermatologie in Beruf und Umwelt, 2020)
CRIS-Team WoS Importer:2021-01-01

Light and shadow in work in the sun: UV exposure at the workplace outdoors - For a long time a little noticed noxious agent - Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2018)
CRIS-Team Scopus Importer:2020-05-11

Long-/Post-COVID-Beschwerden in einem Hotspot-Kollektiv der ersten Infektionswelle in Deutschland - Wolfschmidt, Anna; Ott, Stephan; Richter, Steffi; Schmidt, Johannes; Uter, Wolfgang; Drexler, Hans; Finkenzeller, Thomas (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2024)
Introduction: Despite a high number of long/post-COVID cases and an enormous psychological strain on the part of the patients, no scientific consensus has yet been reached on a clearly defined disease entity. The comprehensive media coverage has made the public more sensitive to this topic, which makes it more difficult to take an objective perspective. Methods: We report on long/post-COVID symptoms in a hotspot collective of the first SARS-CoV-2 wave of infections in Germany; these infections began in Spring 2020 and therefore preceded the start of an intensive media coverage. In June/July 2021, 122 employees of the Kliniken Nordoberpfalz AG who tested positive for SARS-CoV-2 during the first wave of the pandemic were asked about their infection and its consequences using a standardised questionnaire. Results: 82 participants (67 %) complained of persistent symptoms (post-COVID: 29 %). Long/post-COVID symptoms occurred more frequently in those who had experienced symptoms during the acute phase of the infection. Patients with stomach pain as an acute symptom more frequently reported a symptom duration of > 12 weeks. The probability of symptoms persisting > 12 weeks was reduced if throat pain or sniffling had been reported as an acute symptom. Emergence and duration of symptoms were independent of any demographic or occupational factors or of pre-existing conditions. Discussion: Due to having been infected in a hotspot region during the first wave of the pandemic, the study collective exhibits certain peculiarities which must be considered when interpreting the results. The lack of evidence for many risk factors discussed in the literature, together with the challenges facing scientific studies, seems to suggest a more differentiated approach to dealing with post-COVID.
CRIS-Team Scopus Importer:2024-11-29
Keywords: COVID sequelae; First wave; Long-COVID; Post-COVID; Risk factor; SARS-CoV-2

Low internal exposure and absence of adverse effects in workers exposed to high air levels of inorganic selenium - Greiner, Annette; Göen, Thomas; Hildebrand, Jörg; Feltes, Ruth; Drexler, Hans (Toxicology Letters, 2018)
Selenium is an essential trace element for humans, but adverse health effects may occur after elevated intake. The margin between it is small. This study aimed to assess external and internal exposure in workers of a selenium-processing plant, in which elemental and inorganic selenium occurred. Selenium was analyzed in the form of the selenium concentration in plasma (Se-P), in erythrocytes (Se-RBC) and in personal air samples (Setotal-Air) of 17 exposed workers. Internal exposure was compared to 20 controls without occupational selenium exposure. For potential effects, glucose, HbA1c, proinsulin, prothrombin time and GPX were determined. Setotal-Air had a maximum of 2394 μg/m3 (median 319 μg/m3), containing a small water-soluble fraction (median 12.7 μg/m3, range 0.07-975 μg/m3). Se-P of the exposed ranged from 62 to 123 μg/L (median 105 μg/L), whereas the median of Se-RBC was 63.4 μg/L blood (range 51.9-92.7 μg/L). Both were significantly higher than the controls. No significant difference was found for the effect parameters. Biological effect monitoring of employees occupationally exposed to very high levels of selenium and inorganic selenium compounds did not show any indication of adverse health effects. The moderate increase of the internal selenium exposure compared to the high ambient exposure to selenium and its compounds suggests an efficient air protection or an extremely low resorption of elemental and inorganic species of selenium via inhalation.
EVALuna2:34907

Memorandum 'Development of health services research in Bavaria from the perspective of the Bavarian state working group 'health services research (LAGeV)': Status quo - Potential - strategies - Hollederer, Alfons; Braun, Günther E.; Dahlhoff, Gerhard; Drexler, Hans; Engel, Jutta; Grässel, Elmar; Häusler, Elisabeth; Heide, Herwig; Heuschmann, Peter; Hörl, Gabriele; Imhof, Hermann; Kaplan, Max; et al. (Gesundheitswesen, 2015)
The aim of the memorandum on the development of health services research (HSR) in Bavaria is to operationalise the global objectives of the State Working Group Health Services Research (LAGeV) and to collectively define future topics, specific implementation steps, methods as well as ways of working for the future course of the LAGeV. The LAGeV is an expert committee that integrates and links the competencies of different actors from science, politics and health care regarding HSR and facilitates their cooperation. The memorandum is based on an explorative survey among the LAGeV members, which identified the status quo of health services research in Bavaria, potential for development, important constraints, promoting factors, specific recommendations as well as future topics for the further development of HSR in Bavaria. From the perspective of the LAGeV members, the 12 most important future topics are: 1) Interface and networking research, 2) Innovative health care concepts, 3) Health care for multimorbid patients, 4)Health care for chronically ill patients, 5) Evaluation of innovations, processes and technologies, 6) Patient orientation and user focus, 7) Social and regional inequalities in health care, 8) Health care for mentally ill patients, 9) Indicators of health care quality, 10) Regional needs planning, 11) Practical effectiveness of HSR and 12) Scientific use of routine data. Potential for development of HSR in Bavaria lies a) in the promotion of networking and sustainable structures, b) the establishment of an HSR information platform that bundles information and results in regard to current topics and aims to facilitate cooperation as well as c) in the initiation of measures and projects. The latter ought to pinpoint health care challenges and make recommendations regarding the improvement of health care and its quality. The cooperation and networking structures that were established with the LAGeV should be continuously expanded and be used to work on priority topics in order to achieve the global objectives of the LAGe
Keywords: Bavaria; health services research; health system; innovative health care concepts; interface and networking research; quality of health care

Metabolism and toxicokinetics of 1,4-dioxane in humans after inhalational exposure at rest and under physical stress - Göen, Thomas; Von Helden, Franziska; Eckert, Elisabeth; Knecht, Udo; Drexler, Hans; Walter, Dirk (Archives of Toxicology, 2016)
The present study investigated the toxicokinetics of 1,4-dioxane in humans exposed at rest and during physical stress. Eighteen volunteers were divided into three groups of six individuals each, who were exposed separately in three experiments to 20 ppm (73 mg/m(3)) 1,4-dioxane for 8 h. The first group was exposed at rest (Experiment 1), whereas the other groups performed exercises on a bicycle ergometer for 10 min every hour, corresponding to a physical exercise of 50 W (Experiment 2) and 75 W (Experiment 3), respectively. Blood samples were collected after 4 and 8 h, and all urine samples were collected over 24 h. The samples were analysed for 1,4-dioxane and its metabolite 2-(2-hydroxyethoxy)acetic acid (HEAA). The amount of urinary-eliminated HEAA increased during exposure and showed its maximum 9.8 ± 1.9 h after the beginning of exposure. The levels of 1,4-dioxane in blood and urine, however, barely rose above the limit of detection. Depending on the physical stress of the volunteers, the maximum elimination rate of HEAA in urine was significantly increased with 23.2 ± 7.7, 30.4 ± 7.2 and 41.8 ± 23.8 mg/h for Experiments 1, 2 and 3, respectively. Likewise, the cumulative HEAA excretion over 24 h increased with increasing physical stress; 53 ± 15 % of the theoretical inhaled 1,4-dioxane dose was excreted as HEAA in urine during the first 24 h. The average maximum level of HEAA ranged between 378 and 451 mg/g creatinine and increased with the applied physical stress. The half-life of HEAA was found to be 3.4 ± 0.5 h. Twenty-four hours after the beginning of the exposure, 31-51 mg HEAA/g creatinine were still detected in urine, indicating only a low accumulation of the metabolite during a working week. The study results revealed an increasing effect of the applied physical stress on the total eliminated amounts of HEAA as well as on the maximum HEAA levels at the end of exposure. For the estimation of biomonitoring equivalents to occupational exposure limits, this effect should be taken into account.
EVALuna2:9743

Minderung der Erwerbsfähigkeit bei BK 5103 Plattenepithelkarzinome oder multiple aktinische Keratosen der Haut durch natürliche UV-Strahlung - Diepgen, T. L.; Bauer, A.; Bernhard-Klimt, C.; Elsner, P.; Drexler, Hans; Fartasch, M.; John, S. M.; Köllner, A.; Letzel, S.; Merk, H.; Mohr, P.; Wehrmann, W. (Dermatologie in Beruf und Umwelt, 2015)
CRIS-Team Scopus Importer:2020-05-11

Minderung der Erwerbsfähigkeit bei den Berufskrankheiten Nr. 5102, 1108 und 2402 - Diepgen, T. L.; Drexler, Hans; Krohn, S. (Dermatologie in Beruf und Umwelt, 2015)
CRIS-Team Scopus Importer:2020-05-11

Minderung der Erwerbsfähigkeit bei der Berufskrankheit 5103: Trends und Vergleich der Begutachtungspraxis von 2010 – 2015 - Hiller, Julia; Braun, Michael; Drexler, Hans (Dermatologie in Beruf und Umwelt, 2016)
Introduction: New recommendations for the assessment of the loss of earning capacity (LEC) were compiled after "squamous cell carcinoma and multiple actinic keratoses of the skin through natural UV radiation" and introduced as an occupational disease (BK 5103) in Germany in January 2015. The practice of medical reporting and principles for the estimation of LEC were analyzed. Methods: 108 consecutive medical expert reports from 2010 until July 2015 were identified and the LEC as well as further data were recorded. Additionally the data were used to determine and compare the LEC according to the two available assessment charts. Results: Recognition as an occupational disease was recommended for 59,2% of the collective and the LEC was predominantly (> 80%) rated with less than 20%. A comparison between the LEC values determined by the two varying LEC charts showed a slightly higher average value under the old chart (8,4% vs. 6,9%), which was also applicable to more cases and therefore included more cases with precanceroses (63% vs. 56%). In a direct comparison of the two charts higher differences of 10-20% in the determined LEC appeared especially among cases with squamous cell carcinoma. This was caused by a modification of the assigned LEC rates and standards for the disease activity between the two charts. Conclusions: A revision of the recommendations for the LEC was necessary after the introduction of a new occupational disease. By this, consistent standards for the evaluation of disease cases are provided and more fairness among different occupational diseases can be reached.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Actinic keratosis; Loss in earning capacity; Occupational disease; Squamous cell carcinoma

Multiple chemical sensitivity - Drexler, Hans; Greiner, Annette (Kanerva's Occupational Dermatology, 2019)
Multiple chemical sensitivity (MCS) is an enigmatic term, and although this combination of symptoms has been written about for over 50 years, it is unclear whether this is a disease (a pathophysiological process with a molecular mechanism) or an illness (a subjective feeling of malaise). The Center for Disease Control and Prevention (CDC) does not recognize MCS as a disease (Spencer and Schur 2008). As implied by its name, MCS is a condition in which chemical effects are blamed for causing the subjectively experienced symptoms/complaints. The allergologist Theron Randolph was a major influence in the formation of a movement in the 1950s which called itself clinical ecologists and described for the first time the combination of symptoms which later came to be known as MCS. As he assumed the presence of an allergic pathogenic mechanism, he called this illness the “All Allergy Syndrome.” The idea of an underlying allergic pathogenic mechanism leads the affected persons repeatedly to allergologists, usually after dozens of specialists have already been consulted. Regardless of the diagnostic significance, a patch test using chemical substances is frequently requested. The fact that a positive patch test can only explain an allergic skin reaction and is of no use in explaining other diverse symptoms is often tenaciously ignored by these patients. In addition, these patients also demand specialized allergological procedures such as the lymphocyte transformation test, the histamine release test, or the mast cell degranulation test. The term sensitization has a double meaning in connection with the genesis of MCS. In allergology, sensitization means the immunological processes that are necessary for the immune system to react to an exogenous substance with an allergic reaction. In psychology the term sensitization is used when mental processes recur on repeated exposure after an initial incident. Allergologists and dermatologists are repeatedly confronted by both this conceptualization (sensitization, All Allergy Syndrome) and the wish for clarification by the MCS patients and their ideas about the genesis of MCS.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Idiopathic environmental intolerance; IEI; MCS; Multiple chemical sensitivity

Musculoskeletal disorders in surgeons—a problem that is often underestimated Muskuloskelettale Erkrankungen bei Operateuren – eine oftmals zu wenig betrachtete Problematik - Drexler, Hans (Urologe, 2020)
CRIS-Team Scopus Importer:2020-04-17

Networks on health promotion for small and medium-sized enterprises [Netzwerke zur Gesundheitsförderung für KMU] - Fischmann, Wolfgang; Wischlitzki, Elisabeth; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2019)
CRIS-Team Scopus Importer:2019-05-02

Neue Berufskrankheiten in Deutschland - Letzel, Stephan; Drexler, Hans (Deutsche Medizinische Wochenschrift, 2015)
Every physician is legally required to officially report potential occupational diseases in case of reasonable suspicion.Due to these legal reporting requirements, knowledge about occupational diseases including necessary actualizations is essential for all physicians. In January 2015 the third regulation to change the Ordinance on Occupational Diseases came into force, adding four new diseases to the existing list of occupational diseases. New diseases include a laryngeal carcinoma caused by intensive and perennial exposition to aerosols containing sulphuric acid, and squamos-cell carcinoma or multiple actinic keratosis of the skin caused by natural UV radiation. Furthermore the carpal tunnel syndrome, a pressure damage of the Nervus medianus, caused by repetitive manual tasks with flexion and extension of wrists has been added as well as the hypothenar- and thenar-hammer-syndrome which are vascular damages of the hand caused by shock-type application of force.
EVALuna2:9729

New ways of working and psychological well-being: Work intensity as a target variable of job resources - Soucek, Roman; Voss, Amanda Sophie; Drexler, Hans; Moser, Klaus (International Journal of Workplace Health Management, 2024)
Purpose Digitalization and flexibility of workplaces as aspects of new ways of working are associated both positively and negatively with employees’ well-being. However, the mechanisms behind this relationship are not clear yet. We present work intensity as a link between new ways of working and psychological well-being. Furthermore, we address two job resources to alter this association: autonomy and boundary control. Design/methodology/approach Overall, 1,099 employees of a public administration organization participated in the survey and answered a web-based questionnaire. The organization was in the transition to new ways of working including the introduction of a digital filing system and remote work. Findings The results of regression analyses provided evidence that flexibility and dissolution of boundaries were positively related to work intensity, which in turn was associated with emotional exhaustion and work engagement. Thus, new ways of working were negatively associated with psychological well-being, mediated by work intensity. Further analyses revealed that the job resources of autonomy and boundary control moderated the relationship between flexibility respectively dissolution of boundaries with work intensity. Thus, these job resources acted as buffering factors and mitigated the association of new ways of working with work intensity. Originality/value The results indicated that work intensity could be perceived as a conceptual bridge between new ways of working and psychological well-being providing a promising target variable for the deployment of job resources to preserve employees’ well-being.
Keywords: work intensity; boundary control; new ways of working

Nickel allergy is associated with wheezing and asthma in a cohort of young German adults: results from the SOLAR study - Kolberg, Laura; Forster, Felix; Gerlich, Jessica; Weinmayr, Gudrun; Genuneit, Jon; Windstetter, Doris; Vogelberg, Christian; Von Mutius, Erika; Nowak, Dennis; Drexler, Hans; Schaefer, Torsten; Radon, Katja (ERJ Open Research, 2020)
Background: Nickel allergy is the most prevalent contact allergy. It belongs to a different hypersensitivity type to asthma and rhinoconjunctivitis. The aim of this analysis was to assess whether self-reported nickel allergy is associated with incident wheezing, asthma and rhinoconjunctivitis in young German adults, taking into account potential effect modification by sex.
CRIS-Team WoS Importer:2020-05-22

Nutzen und Nachhaltigkeit von Netzwerken zur betrieblichen Gesundheitsförderung in kleinen und mittleren Unternehmen – Am Beispiel der KMU-Netzwerke „Bewegte Unternehmen“ und „Vitale Unternehmen“ - Müller, Eva; Fischmann, Wolfgang; Kötter, Rudolf; Drexler, Hans; Kiesel, Johannes (Gesundheitswesen, 2018)
PURPOSE: The purpose of the study was to analyze if 2 regional networks of small and medium enterprises (SME) for workplace health promotion are sustainable, and to find out the motivation of the enterprises to join the network. It was also examined if there is a stable culture of cooperation 6 -10 years after the founding of the network. Additionally, the study checked the current work and suggestions for improvement to the network structure, so that in the future, promotion of workplace health can be further improved. METHOD: 2 regional networks, founded in 2005 and 2009, were studied. Standardized telephone interviews carried out between September 2013 and January 2014 enabled data collection for this cross-sectional study. 42 interviews with 6 open questions were organized with the managers of the companies or the person responsible for workplace health promotion. RESULTS: The results of the study show that 88.1% (n=37) of the network company members profited from the exchange of experiences. 50.0% (n=21) benefited from shared activities and 28.6% (n=12) from making new contacts. 9.5% (n=4) of the respondents expressed concerns about excessive bureaucracy resulting in too much effort for too little benefit and 7.1% (n=3) were also missing comprehensive structural measures. Suggestions for improvement were enhancement of practical work (26.2%, n=11) and the wish for stronger commitment (11.9%, n=5). 90.5% (n=38) considered their expectations as fulfilled and 66.7% (n=28) evaluated the current work as being quite positive. CONCLUSION: The networks have turned out to be sustainable, proven by the fact that the companies still are members of the networks for 6 and 10 years, respectively and are still satisfied with the network. The study shows that the majority of the members profits from the membership of these regional networks. Networks can help them to implement permanent workplace health promotion. To further improve the work of the network, a systematic and scientific workplace health promotion scheme is recommended.
EVALuna2:35294
Keywords: sustainability; workplace health promotion; benefit; SME; networks

Occlusive gloves and skin conditions: is there a problem? Results of a cross-sectional study in a semiconductor company - Weistenhöfer, Wobbeke; Wacker, Michaela; Bernet, Franziska; Uter, Wolfgang; Drexler, Hans (British Journal of Dermatology, 2015)
Although there is poor scientific evidence that working with occlusive gloves is as damaging as wet work, prolonged glove occlusion is considered to be a risk factor for developing hand eczema similar to wet work.To assess the effects of wearing occlusive gloves during the whole working day, without exposure to any additional hazardous substances, on skin condition and skin barrier function.We investigated 323 employees of a semiconductor production company in Germany: 177 clean-room workers wearing occlusive gloves during the whole shift (exposed group) and 146 employees working in administration (control group). A standardized interview was performed, the skin condition of both hands was studied using the quantitative skin score HEROS, and transepidermal water loss (TEWL) and stratum corneum hydration were measured.There was no significant difference in skin condition between the two subgroups. Values for TEWL and corneometry were significantly higher in exposed participants (P < 0·05). However, the TEWL values were similar to control values if participants took off the occlusive gloves at least 30 min before the measurement. Hence, the effect of occlusion on skin barrier function seems to be transient.Prolonged wearing of occlusive gloves with clean hands and without exposure to additional hazardous substances does not seem to affect the skin negatively.
EVALuna2:5457

Occupational Disease No. 5101 - Legal Concept of Severe or repeatedly relapsing Skin Disease Testing Algorithm and Case Studies - Skudlik, C.; Krohn, S.; Bauer, A.; Bernhard-Klimt, C.; Dickel, H.; Drexler, Hans; Elsner, P.; Engel, D.; Fartasch, M.; Glaubitz, S.; Gauglitz, G.; Goergens, A.; et al. (Dermatologie in Beruf und Umwelt, 2021)
CRIS-Team WoS Importer:2021-04-23

Occupational obstructive airway diseases: How can early diagnosis be made to avoid chronic courses? - Frei-Stuber, Ludwig; Drexler, Hans; Heutelbeck, Astrid; Nowak, Dennis (Pneumologie, 2023)
Since abolishing the obligation to terminate the harmful professional activity from January 1st, 2021 onwards for some occupational diseases including obstructive respiratory diseases in Germany, the recognition of occupational diseases coded under 4301, 4302 and 1315 according the Occupational Diseases Ordinance has increased significantly. By the time these diseasese are recognized, they are usually already at an advanced stage. Therefore, early detection will play a greater role in the future, as the statutory accident insurance can offer individual preventive measures in order to minimize the consequences of illness and thus also the socio-economic burden. However, precursors of such obstructive airway diseases are often overlooked. For optimizing early detection, the statutory accident insurance worked out an early notification procedure for the respiratory tract - comparable to the already well-established dermatological procedure. "Early cases" from the pilot regions can be reported there; to qualify for being reported as early cases, patients must persue insured professional activity with potential effects on the respiratory tract and suffer from a disease of the upper or lower respiratory tract according to the ICD-10 code (e.g. J31.0 chronic rhinitis).
CRIS-Team WoS Importer:2023-05-12

Occupational Skin Cancer according to BK 5103 - a follow-up review after its introduction in the year 2015 Berufskrankheit nach BK-Nr. 5103 - eine Bestandsaufnahme - Diepgen, Thomas; Drexler, Hans; Fartasch, M.; Elsner, P. (Dermatologie in Beruf und Umwelt, 2019)
The occupational disease BK 5103 „squamous cell carcinoma or multiple actinic keratoses due to natural UV-irradiation“was introduced at 01.01.2015 and is in the meantime the second frequent recognized occupational disease in Germany with 5.318 cases in the year 2017 and 12 death cases. In this article we will discuss the new developments of this occupational disease BK 5103 since it was introduced. Frequently a case is recognised as BK 5103 without expert witness only if the occupational UV exposure is high enough (at least 40% of the private exposure at the time of the first skin cancer occurrence. However, it is important to distinguish between skin cancer as a public disease and as an occupational disease. For this decision, additional criteria have to be evaluated like UV-exposure during holidays and leisure activities, UV skin damage at occupational and non-occupational body sites, skin type according to Fitzpatrick, other risk factors like immunosuppression, time between occupational UV-exposure and onset of the skin cancer.
CRIS-Team Scopus Importer:2019-08-23
Keywords: Actinic keratosis; Field cancerisation; Notification of an occupational disease; Occupational disease; Report about occupational skin cancer; Squamous cell carcinoma

Occupational skin cancer - Diepgen, Thomas L.; Drexler, Hans (Kanerva's Occupational Dermatology, 2019)
Occupational skin cancer can be induced due to industrial exposure to chemical carcinogens but nowadays more important due to occupational exposure to UV radiation (UVR). Occupational skin cancer is characterized by long induction periods (years or decades), and its first manifestation is often seen many years after the occupational exposure or even when the affected individuals are not more occupationally exposed. Important industrial chemicals are arsenic and inorganic arsenic compounds, polycyclic aromatic hydrocarbons (PAHs) with particularly high levels in brown coal tars (soft coal tars), coal tars (black coal tars), coal tar pitches, coal tar oils, and coke oven emissions and can cause basal cell carcinomas and squamous cell carcinomas. A published systematic appraisal of the epidemiologic literature and meta-analysis clearly indicates that occupational UV-light exposure is a substantial and robust risk factor for the development of cutaneous squamous cell carcinoma (SCC). The actually available evidence of the epidemiologic literature could also clearly show a significant risk increase for occupationally UV-exposed workers to develop basal cell carcinoma (BCC) compared to nonexposed workers. There is enough scientific evidence that outdoor workers have an increased risk to develop work-related occupational skin cancer due to natural UVR exposure, and adequate prevention strategies have to be implemented. The three measures that are successful and of particular importance in the prevention of nonmelanoma skin cancer in outdoor workers are the following: 1. Changes in behavior regarding awareness of health and disease resulting from exposure to natural UV radiation 2. Protection from direct UV radiation by wearing suitable clothing 3. Regular and correct use of appropriate sunscreens.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Actinic (solar) keratoses; Bowen’s disease; Keratoacanthoma; Malignant melanoma; Nonmelanoma skin cancer; Pitch skin disease; Tar keratoses

Occupational skin disease BK-No. 5101 - causality with case reports - Skudlik, C.; Krohn, S.; Bauer, A.; Bernhard-Klimt, C.; Dickel, H.; Drexler, Hans; Elsner, P.; Engel, D.; Fartasch, M.; Glaubitz, S.; Gauglitz, G.; Goergens, A.; et al. (Dermatologie in Beruf und Umwelt, 2021)
CRIS-Team WoS Importer:2021-07-23

Occupational UV-Exposure is a Major Risk Factor for Basal Cell Carcinoma: Results of the Population-Based Case-Control Study FB-181 - Schmitt, Jochen; Haufe, Eva; Trautmann, Freya; Schulze, Hans-Joachim; Elsner, Peter; Drexler, Hans; Bauer, Andrea; Letzel, Stephan; John, Swen Malte; Fartasch, Manige; Bruening, Thomas; Seidler, Andreas; et al. (Journal of Occupational and Environmental Medicine, 2018)
The aim of this study was to investigate the role of occupational and nonoccupational ultraviolet (UV)-exposure concerning the development of basal cell carcinoma (BCC).We undertook a population-based multicenter case-control study. Patients with first incident BCC (n = 836) were propensity score matched by age and sex to controls without skin cancer (n = 836). Sociodemographic characteristics, clinical characteristics, and lifetime UV-exposure were assessed by trained investigators. The differential estimation of occupational and nonoccupational UV-exposure dosages was based on validated instruments and established reference values. Associations were assessed using multivariable-adjusted conditional logistic regression models.Individuals with high levels of occupational UV-exposure were at significantly increased BCC-risk compared with individuals with low [odds ratio (OR) 1.84; 95% confidence interval (95% CI) 1.19 to 2.83 and moderate (OR 1.97; 95% CI 1.20 to 3.22) occupational UV-exposure. Nonoccupational UV-exposure was not independently associated with BCC.Skin cancer prevention strategies should be expanded to the occupational setting.
EVALuna2:9764

Ökonomische Relevanz vermeidbarer Beschäftigungsverbote an Schulen in Bayern - Wolfschmidt-Fietkau, Anna; Ochmann, Uta; Hiller, Julia; Nowak, Dennis; Schöffski, Oliver; Drexler, Hans (Gesundheitswesen, 2024)
Introduction According to the Maternity Protection Act, an occupational risk of infection (e. g. in childcare) – combined with individual immunity gaps – can result in an irresponsible risk for pregnant women in the workplace. If this risk cannot be eliminated by any other means, the employer must impose a prohibition of employment (PE) for the pregnant woman concerned. We classified PE as preventable if the underlying immunity gaps could have been closed by immunisation prior to pregnancy. Methods From 01.09.2016 to 25.03.2020, 1922 pregnant employees of Bavarian state schools obtained medical coun-selling on their occupational risk of infection as part of a research project. If the individual combination of occupational-risk profile and immunity status resulted in an irresponsible risk for the pregnancy, a PE was recommended by the attending physician. We determined the proportion of PE that would have theoretically been preventable by full immunisation prior to pregnancy and approximated the resulting – theoretically preventable – loss of working hours and personnel costs. Results In 425 cases (22 %), a PE was deemed necessary by the attending physician, whereby 193 (45 %) were retrospectively classified as theoretically preventable. Of these cases, 53 PE (27 %) were temporary (valid until the 20th week of pregnancy) and 140 were long-term (valid for the complete duration of the pregnancy). Based on these results, we approximated a loss of 2,746 working weeks for our collective, which entails theoretically preventable personnel costs totalling 5,763,305 € for the observation period of our study (3.6 years). We then extrapolated estimates for all employees of Bavarian state schools and found a loss of 4,260 working weeks and theoretically preventable personnel costs amounting to almost 8,941,000 € per year during our observation period. Conclusion Theoretically preventable PE caused by immunity gaps can entail a considerable loss of working hours and high personnel costs. Therefore, we should step up measures aimed at improving vaccination rates in women and increasing their willingness to be vaccinated. In view of the changes in legal and regulatory conditions in Germany since 2020, new investigations should be made as soon as there is sufficient data after the general employment prohibitions due to the SARS-CoV-2-pandemic have been lifted.
CRIS-Team Scopus Importer:2024-03-22
Keywords: occupational medicine; occupational risk of infection; personnel costs; pregnancy; prohibition of employment

PAK und UV-Strahlung: Synkanzerogenese? - Weistenhöfer, Wobbeke; Hiller, Julia; Lösch, Regina; Schmitz-Spanke, Simone; Drexler, Hans (60. Wissenschaftliche Jahrestagung der DGAUM, 2020)

Passgenaues betriebliches Gesundheitsmanagement – nichts leichter als das? Ergebnisse der Personalbefragung und Maßnahmenableitung im Modellprojekt „Gesund arbeiten in Thüringen" - Lösch, Regina; Fischmann, Wolfgang; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2020)
Keywords: Betriebliches Gesundheitsmanagement; BGM; Unternehmen

Patient satisfaction at a specialised outpatient clinic for people with work-related respiratory complaints - Lösch, Regina; Hiller, Julia; Kapp, Carolin; Drexler, Hans (SAFETY AND HEALTH AT WORK, 2022)
CRIS-Team WoS Importer:2022-03-18

Positionspapier: Telemedizin in der Berufsdermatologie - Aktueller Stand und Perspektiven - Elsner, Peter; Bauer, Andrea; Diepgen, Thomas Ludwig; Drexler, Hans; Fartasch, Manige; John, Swen Malte; Schliemann, Sibylle; Wehrmann, Wolfgang; Tittelbach, Joerg (Journal der Deutschen Dermatologischen Gesellschaft, 2018)
Teledermatology is the use of telecommunication technologies to exchange medical information for diagnosis, consultation, treatment and teaching in dermatology. While its use has been evaluated in a wide range of dermatological diagnoses, only few studies exist on its validity, diagnostic precision, feasibility, and cost-effectiveness in occupational dermatology. However, these studies show a considerable potential for diagnosis, prevention, treatment support and follow-up of patients with occupational skin diseases. Asynchronous (store and forward; SAF) or synchronous dermatology teleconsults could assist occupational medicine specialists not only in occupational preventive care, but also in the context of skin cancer screening in outdoor workers. Thus, teledermatology might contribute to earlier prevention and notification of occupational skin diseases. Modern smartphone apps with artificial intelligence technologies may also facilitate self-monitoring in employees working in high-risk jobs.
EVALuna2:34840

Prävention am Arbeitsplatz gestalten: Perspektiven für das Betriebliche Gesundheitsmanagement (BGM) - Drexler, Hans; Letzel, Stephan; Nesseler, Thomas (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2016)
CRIS-Team Scopus Importer:2020-05-11

Prevention in the field of occupational medicine-the role of occupational physicians in Workplace Health Management Prävention in der Arbeits-und Betriebsmedizin-Die Rolle des Betriebsarztes im betrieblichen Gesundheitsmanagement - Fischmann, Wolfgang; Amler, Nadja; Drexler, Hans (Public Health Forum, 2018)
Keywords: German occupational safety act; company doctor; Workplace Health Management; risk assessment; Workplace Health Promotion

Protection during production: Problems due to prevention? Nail and skin condition after prolonged wearing of occlusive gloves - Weistenhöfer, Wobbeke; Uter, Wolfgang; Drexler, Hans (Journal of Toxicology and Environmental Health-Part A-Current Issues, 2017)
Wearing of occlusive gloves during the whole working shift is considered a risk factor for developing hand eczema, similar to wet work. Moreover, the increased hydration due to glove occlusion may lead to brittle nails. Two hundred and seventy clean room workers, wearing occlusive gloves for prolonged periods, and 135 administrative employees not using gloves were investigated. This included a dermatological examination of the nails and the hands, using the Hand Eczema ScoRe for Occupational Screening (HEROS), measurement of transepidermal water loss (TEWL), and a standardized interview. Of the clean room workers, 39%, mainly women, reported nail problems, mostly brittle nails with onychoschisis. Skin score values showed no significant differences between HEROS values of both groups. TEWL values of exposed subjects were similar to TEWL values of controls 40 min after taking off the occlusive gloves. In a multiple linear regression analysis, male gender and duration of employment in the clean room were associated with a significant increase in TEWL values. The effect of occlusion on TEWL seems to be predominantly transient and not be indicative of a damaged skin barrier. This study confirmed the results of a previous investigation showing no serious adverse effect of wearing of occlusive gloves on skin condition without exposure to additional hazardous substances. However, occlusion leads to softened nails prone to mechanical injury. Therefore, specific prevention instructions are required to pay attention to this side effect of occlusion.
EVALuna2:9766

Psychische Beanspruchung und der Wunsch nach Änderung des Bewegungsverhaltens – Eine geschlechterspezifische Analyse im Rahmen des Modellprojekts „Gesund arbeiten in Thüringen“ - Lösch, Regina; Drexler, Hans; Wischlitzki, Elisabeth (61. Wissenschaftliche Jahrestagung der DGAUM, 2021)

Psychische Gefährdungsanalyse: Bestandsaufnahme für betriebliches Gesundheitsmanagement in KMU - Kiesel, Johannes; Fischmann, Wolfgang; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2016)

Psychische Komorbidität und Genesungszeit – die „Basis-MdE“ am Beispiel der BK 1301/1321 - Weistenhöfer, Wobbeke; Golka, Klaus; Dinkel, Andreas; Forchert, Martin; Drexler, Hans; Schöps, Wolfgang (63. Jahrestagung der DGAUM, 2023)

Psychische Traumatisierung im Fahrdienst: Über die Bedeutung der zeitnahen Versorgung nach traumatischen Ereignissen - Wrenger, Nina; Staples, Ronald; Grässel, Elmar; Drexler, Hans; Clarner, Annika (Gesundheitswesen, 2015)

Psychological strain and stress at the workplace [Psychische Belastung und Beanspruchung am Arbeitsplatz] - Fischmann, Wolfgang; Voss, Amanda Sophie; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2019)
CRIS-Team Scopus Importer:2019-05-02

Psychosocial risk management in the teaching profession: A systematic review - Wischlitzki, Elisabeth; Amler, Nadja; Hiller, Julia; Drexler, Hans (Safety and Health at Work, 2020)
Teachers are facing various job demands with psychosocial aspects being fundamental due to the nature of the occupation. While teachers´ work is associated with different psychosocial health risks, little is known on how to identify and tackle those. Thus, a systematic literature search according to the PRISMA statement was conducted via MEDLINE (PubMed), PSYNDEX (PubPsych) and ScienceDirect. Two reviewers independently screened 2261 titles, abstracts and 169 full-texts. According to the inclusion criteria established a priori, articles from peer-reviewed journals (English or German) on psychosocial risk management in teachers were incorporated. Despite a comprehensive and sensitive search, only four publications could be identified, outlining a process to implement risk management and different assessment tools. Taken together, data presented in the articles were scarce. Recommendations for process steps as well as the assessment of psychosocial risks can be derived from the findings. To implement effective psychosocial risk management in the teaching profession, further research is needed, though. Effective and practicable approaches, which are accepted by the target group, should be further developed and investigated. Relevant causes of occupational strain in the teaching profession must be identified and assessed reliably. Low-threshold interventions should be implemented, and the outcome must be evaluated afterward
Keywords: risk assessmenthazard assessmentschoolstrainstress

Psychotrauma after occupational accidents in public transportation. A pilot study to support concepts, influencing factors and occupational health-care - Clarner, Annika; Krahl, J.; Uter, Wolfgang; Drexler, Hans; Martin, A. (Gesundheitswesen, 2015)
Accidents, assaults and suicides occur quite frequently in public transportation. As a result of such extreme events at work, drivers are particularly prone to psychotrauma (PT). Therefore accident insurers stipulate support from the accident site to workplace reintegration with the inclusion of occupational medicine. The present study investigates the incidence, factors influencing psychological trauma as well as the occupational health-care after critical incidents.In a Bavarian public transportation corporation 59 employees were evaluated according to ICD-10 for trauma-related disorders, using full collection after application of a specific mental first aid programme and a subsequent occupational health examination.The incidence of PT was 44.1%, with 8.5% showing a post-traumatic stress disorder (PTSD) as consequence of the accident. As significant influencing factors the nature of the accident, the severity of third party injury, and own physical injuries were identified. The occupational medical care depended on the severity of the disease. PT led to the need for rehabilitation. Sick leave was most pronounced in drivers with PTSD.The study group showed high levels of emotional strain within the first month. With respect to occupational health-care, particular attention should be paid to drivers after serious accidents or those who sustained own injuries. As foundation for evidence based health-care measures after PT in transport must be scientifically evaluated and the identified risk factors must be well-founded as well.
EVALuna2:5522

Quantification of prominent organic UV filters and their metabolites in human urine and plasma samples - Klotz, Katrin; Hof, Kerstin; Hiller, Julia; Göen, Thomas; Drexler, Hans (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2019)
Monitoring human exposure to chemical UV filters is essential for an accurate assessment of the health risk caused by the resorbed compounds. We developed different procedures for the determination of the prominent UV filters octocrylene (OC), avobenzone (AVO) and 2-ethylhexyl salicylate (EHS) as well as for two OC and EHS metabolites in human urine and OC, AVO and 2-cyano-3,3-diphenylacrylic acid (CDAA) in plasma samples using liquid chromatography-tandem mass spectrometry (LC–MS/MS). Since the development of a multi-method for all analytes proved to be difficult, three different procedures were established for the determination of AVO, OC and its metabolite CDAA in urine and plasma as well as for EHS and its metabolite 5-hydroxy-EHS in urine. The methods have been validated with good sensitivity, precision and accuracy. The procedures were satisfactorily applied to the determination of the target compounds in human samples collected from volunteers after sunscreen application. These new analytical procedures can provide information on the internal exposure to the UV filters OC, AVO and EHS, which has been little studied.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Avobenzone; Biomonitoring; Ethylhexyl salicylate; Octocrylene; UV filter

Recommendations regarding the evaluation of a reduction in earning capacity for occupational skin cancer Minderung der Erwerbsfähigkeit bei arbeitsbedingten Hautkrebserkrankungen - Diepgen, T. L.; Bauer, A.; Bernhard-Klimt, C.; Elsner, P.; Drexler, Hans; Fartasch, M.; John, S. M.; Köllner, A.; Letzel, S.; Merk, H.; Mohr, P.; Skudlik, C.; et al. (Dermatologie in Beruf und Umwelt, 2017)
With the revision of the German Ordinance on Occupational Diseases at January 1, 2015, the new occupational disease BK 5103 "Squamous cell carcinoma or multiple actinic keratosis of the skin caused by natural UV-irradiation" was amended as a new occupational disease to the list of occupational diseases in Germany. Skin cancer can also be recognized as an occupational disease according to BK-Numbers 1108, 2402 und 5102. In the meantime the recommendations regarding the evaluation of a reduction in earning capacity for occupational skin cancer have been modified in a consensus conference by the task force "Bamberger Empfehlung" at January 24, 2017.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Actinic keratosis; Basal cell carcinoma; Compensation; Occupational disease; Skin cancer; Squamous cell carcinoma

Reduction in Earning Capacity (MdE) for work-related Skin Cancer MdE Tables for BK Numbers 5102 and 5103 - Krohn, S.; Skudlik, C.; Bauer, A.; Bernhard-Klimt, C.; Dickel, H.; Drexler, Hans; Elsner, P.; Engel, D.; Fartasch, M.; Glaubitz, S.; Gauglitz, G.; Goergens, A.; et al. (Dermatologie in Beruf und Umwelt, 2021)
CRIS-Team WoS Importer:2021-10-01

Re-evaluation of hazard classifications and exposure limits for lead - An example for an advanced mode of operation within the MAK commission during COVID-19 restrictions - Göen, Thomas; Drexler, Hans; Nowak, Dennis; Schriever-Schwemmer, Gerlinde; Schwarz, Michael; Van Thriel, Christioph; Hartwig, Andrea (SAFETY AND HEALTH AT WORK, 2022)
CRIS-Team WoS Importer:2022-03-18

Respiratory afflictions during hairdressing jobs: case history and clinical evaluation of a large symptomatic case series - Hiller, Julia; Greiner, Annette; Drexler, Hans (Journal of Occupational Medicine and Toxicology, 2022)
Objectives Respiratory symptoms at work are common among hairdressers. Various working materials, most notably bleaching ingredients such as ammonium persulfate, have been made responsible. The objective of this study is to achieve a better understanding of work-related respiratory symptoms of hairdressers by describing common features in a large affected collective. Methods One hundred forty-eight hairdressers with respiratory symptoms at work presenting between 2012 and 2019 were consecutively included in a case series. Anamnestic and diagnostic data including pulmonary function and allergy testing were retrospectively compiled from records and analysed. Additionally, cases were categorised in five groups with respect to occupational causation certainty. Results 30% of the predominantly female collective had changed jobs or were on longer sick-leave. Besides respiratory symptoms, 10% also reported contact urticaria to blonde dyes. In 60% an obstructive airway disease was confirmed. A specific hypersensitivity reaction to ammonium persulfate was found in 15%. Group 1 with a proven immunological occupational causation showed significantly lower age (p < 0.001) and tenure time (p = 0.001), higher sensitization rates against environmental allergens as well as a higher total IgE (p = 0.015), compared to group 4 (obstructive airway disease, specific occupational causation unlikely). Conclusions This case series contributes to a better characterization of work-related respiratory symptoms in hairdressing as one of the largest examined collectives of symptomatic hairdressers. Ammonium persulfate as the most common specific cause showed signs of a type-I-like hypersensitivity reaction with typical risk factors for atopy. Prick testing is recommended in all symptomatic cases. However, a specific occupational causation often cannot be proved.
CRIS-Team WoS Importer:2022-06-10

Ressourcen stärken, Gesundheit fördern – Lehrkräfte als Zielgruppe für Kurorte und Heilbäder - Wischlitzki, Elisabeth; Fischmann, Wolfgang; Drexler, Hans (8. LGL Kongress für den Öffentlichen Gesundheitsdienst, 2019)

Retrospektive Expositionsabschätzung der natürlichen UV-Strahlendosis: Erfahrungen mit dem Online-UV-Anamnese-Instrument im Feldversuch - Weistenhöfer, Wobbeke; Hiller, Julia; Drexler, Hans; Kiesel, Johannes (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
Cutaneous squamous cell carcinoma and multiple actinic keratoses can be recognized as occupational diseases if the site affected has been subjected to additional occupational UV exposure of at least 40 %. An online UV history tool that allows for the quantification of occupational and recreational UV doses was now tested in a field study.Ninety-nine patients with nonmelanoma skin cancer were examined. Patient history with respect to UV exposure was obtained using the online UV history tool. Initial validation was carried out with data from ten additional patients. In the context of a pilot study, the applicability of the tool was assessed using a questionnaire.Overall, patient history revealed a UV exposure between 3,792 and 53,163 SEDs. Patients with squamous cell carcinoma, actinic keratoses, or Bowen's disease (n = 22) had significantly higher SED values and were significantly older (73 vs. 66 years) than patients with basal cell carcinoma (n = 77). Occupational UV exposure was reported by 19 patients, two of whom showed an additional occupational UV exposure of more than 40 %, which prompted the filing of a (suspected) occupational disease report. With respect to validation, there was evidence of good inter-investigator reliability. The applicability of the tool was rated as good.The online UV history tool enables quick retrospective quantification of occupational and recreational UV exposure in case of suspicion of the occupational disease "cutaneous squamous cell carcinoma or multiple actinic keratoses caused by natural UV radiation
EVALuna2:9765

Risikofaktoren für einen schweren COVID-19-Verlauf in einer Hotspot-Region der ersten und zweiten SARS-CoV-2-Infektionswelle in Deutschland - Richter, Steffi; Finkenzeller, Thomas; Uter, Wolfgang; Drexler, Hans; Wolfschmidt, Anna (Gesundheitswesen, 2024)
Background During the first wave of the SARS-CoV-2 pandemic, Weiden Hospital was a hotspot and was thus in an exceptional medical situation. This study deals with the question of whether the recognized risk factors for a severe course of COVID- 19 also apply to the patients treated in Weiden Hospital during this time or whether other factors could have influenced patient outcomes. Methods In a retrospective analysis, data on 669 patients of Weiden Hospital with proven SARS-CoV-2 infections in the first year of the pandemic were evaluated. Risk factors for a severe case of COVID-19 were determined from medical and demographic information in a univariate analysis and subjected to logistic regression. The logistic regression analysis was performed for the overall collective as well as separately for patients from Wave 1 (3-6/2020) and 2 (7-12/2020). Results Looking at all of 2020, significant risk factors for severe COVID-19 included being male, being a smoker, being 71 years or older, and a history of depression. All other commonly recognized risk factors were not applicable for the Weiden collective. When looking at both waves separately, in Wave 1 age was not a significant risk factor, whereas in Wave 2 an age of 61 years or older was associated with an increased risk of severe progression. For patients who were admitted to hospital in Wave 2, the risk of severe progression was reduced almost by half. Conclusion It can be assumed that patient outcomes in Weiden's hotspot collective were predominantly determined by non-individual factors, like the difficult care situation in a hotspot clinic at the beginning of the pandemic. In preparation for future pandemics, provision of sufficient resources might significantly contribute to better patient outcomes.
CRIS-Team Scopus Importer:2024-11-29
Keywords: COVID-19; erste Welle; Hotspot; Pandemie; schwerer Verlauf

S1-AWMF-Leitlinie (Langversion). Berufliche Hautmittel: Hautschutz, Hautpflege und Hautreinigung. ICD 10: L23, L24 - Fartasch, M.; Diepgen, T. L.; Drexler, Hans; Elsner, P.; John, S. M.; Schliemann, S. (Dermatologie in Beruf und Umwelt, 2015)
Job-related hand dermatitis heads up the list of reported occupational diseases. Socalled skin products - understood to mean protective creams, skin cleansers and skin care products - are used for the primary and secondary prevention of job-related hand dermatitis. In the interests of evidence-based medicine, the only preventive measures and/ or occupational skin products that should be used are those whose potential uses and efficacy are underpinned by scientific research. To this end, the Arbeitsgemeinschaft für Berufs- und Umweltdermatologie e.V. (Working Group for Occupational and Environmental Dermatology, ABD) of the DDG (German Dermatological Society) and the Deutsche Gesellschaft für Arbeits- und Umweltmedizin (German Society for Occupational and Environmental Medicine, DGAUM) have summed up the latest scientific findings and recommendations in the updated guideline. The benefit of the combined application of protective creams and skin care products in the primary and secondary prevention of work-related contact dermatitis has been widely confirmed by recent clinical-epidemiological studies. The guideline clearly explains the necessity of demonstrating the efficacy of protective creams and cleansing products by means of in vivo methods in the sense of repetitive applications. Transferable standardised testing systems designed to examine the irritation potential and thus the compatibility of occupational skin cleansers and the reduction of irritation by protective skin creams have now been developed and validated by multicentre studies for skin protection creams and cleansers. The status of the current assessment of the safety of occupational skin products is also summarised.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Guideline; Occupational contact dermatitis; Prevention; Protective creams; Skin care products; Skin cleansers

S1 guideline on occupational skin products: protective creams, skin cleansers, skin care products (ICD 10: L23, L24) - short version - Fartasch, Manige; Diepgen, Thomas L.; Drexler, Hans; Elsner, Peter; John, Swen Malte; Schliemann, Sibylle (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
Job-related hand dermatitis heads up the list of reported occupational diseases. So-called skin products - understood to mean protective creams, skin cleansers and skin care products - are used for the primary and secondary prevention of job- related hand dermatitis. In the interests of evidence-based medicine, the only preventive measures and/or occupational skin products that should be used are those whose potential uses and efficacy are underpinned by scientific research. To this end, the Arbeitsgemeinschaft für Berufs- und Umweltdermatologie e.V. (Working Group for Occupational and Environmental Dermatology, ABD) of the DDG (German Dermatological Society) and the Deutsche Gesellschaft für Arbeits- und Umweltmedizin (German Society for Occupational and Environmental Medicine, DGAUM) have summed up the latest scientific findings and recommendations in the updated guideline. The benefit of the combined application of protective creams and skin care products in the primary and secondary prevention of work-related contact dermatitis has been widely confirmed by recent clinical-epidemiological studies. The guideline clearly explains the necessity of demonstrating the efficacy of protective creams and cleansing products by means of in vivo methods in the sense of repetitive applications. Transferable standardised testing systems designed to examine the irritation potential and thus the compatibility of occupational skin cleansers and the reduction of irritation by protective skin creams have now been developed and validated by multicentre studies for skin protection creams and cleansers. The status of the current assessment of the safety of occupational skin products is also summarised.
EVALuna2:9727

S3 guidelines: Epicutaneous patch testing with contact allergens and drugs – Short version, Part 1 - Mahler, Vera; Nast, Alexander; Bauer, Andrea; Becker, Detlef; Brasch, Jochen; Breuer, Kristine; Dickel, Heinrich; Drexler, Hans; Elsner, Peter; Geier, Johannes; John, Swen Malte; Kreft, Burkhard; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
Epicutaneous patch testing is the diagnostic standard for the detection of allergic contact dermatitis. The present guidelines are aimed at residents and board-certified physicians in the fields of dermatology and allergology as well as other medical specialties involved in establishing the indication for patch testing and its execution in patients with contact dermatitis and other forms of delayed-type hypersensitivity. The target audience also includes other health care providers and insurance funds. Based on a systematic literature search and a formal consensus process (S3), the guidelines were developed by dermatologists in collaboration with pediatricians, occupational medicine physicians, nursing staff as well as patient representatives. The systematic methodological approach and appraisal of evidence upon which the recommendations are based are outlined in a separate method report that also contains evidence tables. The guidelines address general aspects of patch testing as well as medicolegal issues. The recommendations given relate to topics such as the indication for patch testing, informed patient consent, as well as the choice of test substances, test chambers and test site, duration of exposure, reading times and interpretation of test reactions. Furthermore, recommendations are provided with respect to endogenous and exogenous factors, specific patient groups (children, pregnant women, immunosuppressed individuals) as well as possible risks and adverse events associated with patch testing using contact allergens. Note: This publication is part 1 of the short version of the S3 guidelines for “Epicutaneous patch testing using contact allergens and drugs” (registry no. 013 – 018; date: March 20, 2019; valid until December 31, 2021). Part 2 of the short version will be published in the next issue. The long version of these guidelines can be accessed at www.awmf.org. The method report is available as online publication (https://www.awmf.org/leitlinien/detail/ll/013-018.html) and contains the evidence tables in its appendix.
CRIS-Team Scopus Importer:2019-10-29

S3-Leitlinie: Durchführung des Epikutantests mit Kontaktallergenen und Arzneimitteln – Kurzfassung Teil 1 - Mahler, Vera; Nast, Alexander; Bauer, Andrea; Becker, Detlef; Brasch, Jochen; Breuer, Kristine; Dickel, Heinrich; Drexler, Hans; Elsner, Peter; Geier, Johannes; John, Swen Malte; Kreft, Burkhard; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
CRIS-Team Scopus Importer:2019-10-29

S3-Leitlinie: Durchführung des Epikutantests mit Kontaktallergenen und Arzneimitteln - Kurzfassung Teil 2. - Mahler, Vera; Nast, Alexander; Bauer, Andrea; Becker, Detlef; Brasch, Jochen; Breuer, Kristine; Dickel, Heinrich; Drexler, Hans; Elsner, Peter; Geier, Johannes; John, Swen Malte; Kreft, Burkhard; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
Zusammenfassung Der diagnostische Standard zum Nachweis einer bestehenden allergischen Kontaktdermatitis ist der Epikutantest. Die vorliegende Leitlinie richtet sich an Assistenz- und Facharzte der Dermatologie, Allergologie und Arzte weiterer Fachgruppen in Klinik und Praxis, die an der Indikationsstellung oder Durchfuhrung von Epikutantests bei Patienten mit Kontaktekzemen und weiteren Spattypallergien beteiligt sind, sowie Kooperationspartner der Arzteschaft (Fachberufe im Gesundheitswesen, Kostentrager). Die Leitlinie zur Durchfuhrung des Epikutantests mit Kontaktallergenen wurde auf der Basis einer systematischen Literatursuche zu definierten Schlusselfragen evidenzbasiert und im formellen Konsensusverfahren (S3) von Dermatologen unter Einbindung von Padiatern, Arbeitsmedizinern, Assistenzpersonal und Patientenvertretern erstellt. Bezuglich der methodischen und inhaltlichen Arbeit, auf denen die Empfehlungen basieren, wird auf Methodenbericht und Evidenztabellen verwiesen. Die Leitlinie stellt allgemeine Aspekte der Epikutantestung sowie medizinrechtliche Aspekte dar. Es werden Empfehlungen gegeben zur Indikationsstellung, Patientenaufklarung, Auswahl von Testsubstanzen und Kammersystemen, Expositionsort, -dauer und Ablesezeitpunkten, Interpretation von Testreaktionen, endogenen und exogenen Einflussfaktoren, Testung besonderer Personengruppen (Kinder, Schwangere, Immunsupprimierte) sowie Risiken und unerwunschten Nebenwirkungen bei der Durchfuhrung des Epikutantests mit Kontaktallergenen.
EVALuna2:280871

Schadstoffbelastung in Innenräumen - Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
CRIS-Team Scopus Importer:2020-05-11

Science communication on the public health risks of air pollution: a computational scoping review from 1958 to 2022 - Pfleger, Elisabeth; Adrian, Christoph; Lutz, Regina; Drexler, Hans (Archives of Public Health, 2023)
Background Air pollutants are a health risk for the entire population. Particulate matter (PM) including the smallest fraction, ultra-fine particles (UFP), therefore continue to be the focus of scientific research in this area. To protect the population from the harmful effects of exposure to PM, communication and information of research results are of spe- cial relevance as individuals with heightened awareness of the harms of poor air quality are more likely to take action to improve their exposure. Methods We conducted a scoping review of the scientific literature on science communication of public health information about risks associated with air pollutants to generate an initial over-view of existing research in this field. We searched the PubMed and Scopus databases and analyzed the data using a structured topic modeling (STM) approach. Results The existing scientific literature dates back to 1958 but increases significantly from the 1990s onwards. Publi- cations are mainly found in the discipline of environmental research and are primarily concerned with health effects. It is often stated that adequate communication of the results to the public would be important, but specific approaches are rare. Overall, the topic of risk communication seems to be underrepresented for both air pollutants and UFP. Conclusions To protect public health, it is important to conduct more intensive science and risk communication related to scientific findings on the risks of air pollutants. For adequate communication and information, further research is needed to provide specific approaches that also involve the affected population and take different target groups into account. In addition, the effectiveness of communication efforts should also be analyzed.
Keywords: Air pollution; Public health; Science communication; Health communication; Information; Risk; Scoping review; Ultra-fine particles

Seltene Berufskrankheiten - Drexler, Hans (Internist, 2020)
Rare work-related illnesses do not usually meet the requirements to be recognised and compensated as a legal occupational disease. However, common diseases (e.g. ovarian carcinoma) are sometimes caused by occupational influences (e.g. asbestos), making the occupational disease ovarian cancer caused by occupational exposure to asbestos a rare disease. Since in our modern working world the occupational influences that are harmful to health are decreasing qualitatively (substitutes) and quantitatively (limit values), the diseases they cause are also becoming increasingly rare.
CRIS-Team WoS Importer:2020-05-08

Sensory irritation as a basis for setting occupational exposure limits - Bruning, Thomas; Bartsch, Rüdiger; Bolt, Hermann Maximillian; Desel, Herbert; Drexler, Hans; Gundert-Remy, Ursula; Hartwig, Andrea; Jäckh, Rudolf; Leibold, Edgar; Pallapies, Dirk; Rettenmeier, Albert W.; Schlüter, Gerhard; et al. (Archives of Toxicology, 2014)
There is a need of guidance on how local irritancy data should be incorporated into risk assessment procedures, particularly with respect to the derivation of occupational exposure limits (OELs). Therefore, a board of experts from German committees in charge of the derivation of OELs discussed the major challenges of this particular end point for regulatory toxicology. As a result, this overview deals with the question of integrating results of local toxicity at the eyes and the upper respiratory tract (URT). Part 1 describes the morphology and physiology of the relevant target sites, i.e., the outer eye, nasal cavity, and larynx/pharynx in humans. Special emphasis is placed on sensory innervation, species differences between humans and rodents, and possible effects of obnoxious odor in humans. Based on this physiological basis, Part 2 describes a conceptual model for the causation of adverse health effects at these targets that is composed of two pathways. The first, "sensory irritation" pathway is initiated by the interaction of local irritants with receptors of the nervous system (e.g., trigeminal nerve endings) and a downstream cascade of reflexes and defense mechanisms (e.g., eyeblinks, coughing). While the first stages of this pathway are thought to be completely reversible, high or prolonged exposure can lead to neurogenic inflammation and subsequently tissue damage. The second, "tissue irritation" pathway starts with the interaction of the local irritant with the epithelial cell layers of the eyes and the URT. Adaptive changes are the first response on that pathway followed by inflammation and irreversible damages. Regardless of these initial steps, at high concentrations and prolonged exposures, the two pathways converge to the adverse effect of morphologically and biochemically ascertainable changes. Experimental exposure studies with human volunteers provide the empirical basis for effects along the sensory irritation pathway and thus, "sensory NOAEChuman" can be derived. In contrast, inhalation studies with rodents investigate the second pathway that yields an "irritative NOAECanimal." Usually the data for both pathways is not available and extrapolation across species is necessary. Part 3 comprises an empirical approach for the derivation of a default factor for interspecies differences. Therefore, from those substances under discussion in German scientific and regulatory bodies, 19 substances were identified known to be human irritants with available human and animal data. The evaluation started with three substances: ethyl acrylate, formaldehyde, and methyl methacrylate. For these substances, appropriate chronic animal and a controlled human exposure studies were available. The comparison of the sensory NOAEChuman with the irritative NOAECanimal (chronic) resulted in an interspecies extrapolation factor (iEF) of 3 for extrapolating animal data concerning local sensory irritating effects. The adequacy of this iEF was confirmed by its application to additional substances with lower data density (acetaldehyde, ammonia, n-butyl acetate, hydrogen sulfide, and 2-ethylhexanol). Thus, extrapolating from animal studies, an iEF of 3 should be applied for local sensory irritants without reliable human data, unless individual data argue for a substance-specific approach.
EVALuna2:9713

Setting-based skin cancer prevention at the workplace: A survey among German outdoor workers - Görig, Tatiana; Breitbart, Eckhard W.; Drexler, Hans; Diehl, Katharina (American Journal of Industrial Medicine, 2023)
Background: Outdoor workers are at increased risk of developing skin cancer. Setting-based prevention at the workplace can reduce the UV exposure of outdoor workers through appropriate technical or organizational measures. We explored the implementation of setting-based UV protection at the workplace in Germany from the perspective of outdoor workers. Methods: A Germany-wide sample of 319 outdoor workers from different employment sectors (64.3% male) was surveyed via telephone on different technical and organizational measures for UV protection at the workplace. Bivariate analyses were performed to explore associations with job-related characteristics. Results: In general, 28.0% were rarely or never provided with a place in the shade during working hours, and 27.4% rarely or never provided with a shaded place during breaks. One-third had rarely or never the opportunity to work in the shade on hot summer days. Overall, 51.9% reported receiving protective clothing from their employer, 45.5% were provided with headgear, and 25.1% with sunscreen. About one-third had often or always the option of starting work earlier in the morning on hot summer days to work less in the sun, while 18.6% had to work overtime on such days. One-third (35.4%) had been educated at work about risks of solar radiation and sun protection measures. Conclusions: Our study is among the first to present findings on the implementation of different setting-based UV protection measures at the workplace and provides starting points for employers and policy makers to improve UV protection at the workplace.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Germany; occupational exposure; outdoor workers; skin cancer prevention; sun-safety

Sickness absence among peer-supported drivers after occupational trauma - Clarner, Annika; Uter, Wolfgang; Ruhmann, L.; Wrenger, Nina; Martin, A.; Drexler, Hans (Occupational Medicine-Oxford, 2017)
Psychological first aid is a common approach for providing support after potentially traumatic events (PTEs). In Germany, a peer support model is recommended by the German Statutory Accident Insurance (DGUV) to reduce sickness absence after occupational accidents, especially in public transportation. However, data on the effectiveness of peer support are very sparse.To analyse whether peer support has an impact on sickness absence after work-related traumatic events in public transportation.An analysis was conducted in two German public transportation corporations. Due to ethical requirements, we used a historical cohort study comparing peer support by colleagues (VAG-1), peer support at supervisor level (VGF) and a non-intervention group (VAG-0). The study period was from March 2003 to December 2012. We used a negative binominal regression model to estimate the relative risk associated with the interventions and potential confounders.A total of 259 incident PTEs in employees were observed. A regression analysis identified the severity of PTE (severe and fatal events), VGF and age as significant factors in predicting duration of post-event sickness absence. In a stratified analysis, the mode of peer support (VGF) and age predicted sickness absence for less severe PTEs but this was not significant for severe PTEs.Severe and fatal PTEs had the strongest impact on sickness absence after PTEs. For less severe PTE, peer support provided by colleagues may be superior to supervisor support.
EVALuna2:9760

Skin cancer induced by natural UV-radiation as an occupational disease–requirements for its notification and recognition - Diepgen, Thomas L.; Brandenburg, Stephan; Aberer, Werner; Bauer, Andrea; Drexler, Hans; Fartasch, Manige; John, Swen Malte; Krohn, Steffen; Palfner, Stefanie; Roemer, Wolfgang; Schuhmacher-Stock, Uta; Elsner, Peter (Journal der Deutschen Dermatologischen Gesellschaft, 2014)
In Germany over 2.5 million employees have an increased risk of skin cancer due to their occupational exposure to natural UV-irradiation. The medical consultation board "Occupational diseases" of the Ministry of Labor and Social affairs has investigated the association between occupational UV-irradiation and skin cancer risk and recommends to add the following new occupational disease into the appendix1 of the German ordinance on occupational diseases: "Squamous cell carcinoma and multiple actinic keratosis due to natural UV-irradiation". In this article we report in the view of the German Society of Occupational and Environmental Dermatology (ABD) and the German Statutory accident insurance (DGUV), whose criteria have to be fulfilled for the notification and recognition of an occupational skin cancer due to natural UV-irradiation.
EVALuna2:9720

Sonne, Outdoor-Working: Krebsgefahr? - Drexler, Hans (Dermatologie in Beruf und Umwelt, 2017)
CRIS-Team Scopus Importer:2020-05-11

Sonne, Outdoor-Working: Krebsgefahr? Stellungnahme des Präsidenten der DGAUM zur arbeitsmedizinischen Vorsorge bei Beschäftigung im Freien - Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
CRIS-Team Scopus Importer:2020-05-11

Ständige Erreichbarkeit von Beschäftigten in kleinen und mittleren Unternehmen – Kontaktaufnahmen in der Freizeit und psychische Beanspruchungen - Voss, Amanda Sophie; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2019)
Objective: One of the effects of digitisation has been the extended and permanent accessibility of employees during their leisure time, which can lead to mental stress. The results should help to identify starting points for WHM on how to deal with the permanent accessibility in terms of making contact in relation to official matters outside regular working hours. Method: Two cross-sectional surveys were conducted among employees in Bavarian SMEs by means of questionnaires in order to investigate the expected availability and amount of contact during leisure time by different groups of people. In addition, information was collected on the different tasks that the contact entailed and on the medium or the communication channel as well as the respective frequency with which contact was made. The evaluation of the results was descriptive. Results: Accessibility and expected availability during free time both vary across the different groups of people. Most of the statements on contact during leisure time and the highest incidences were reported in connection with the nature of the task. Overall, the analysis of the frequency with which contact is made shows that stress tends to increase at higher frequencies across all characteristics. Conclusions: Companies are advised to take behavioural and organisational measures to deal with permanent accessibility. Certain factors make a difference for respondents - by whom they expect to be contacted or are contacted during their free time and what the upcoming task will entail - and this should be taken into account. Further research is needed in order to derive suitable operational measures for dealing with permanent accessibility.
CRIS-Team Scopus Importer:2019-08-16
Keywords: Extended accessibility; Mental strain; Permanent accessibility; Workplace health management

Stellungnahme der Deutschen Gesellschaft für Arbeitsmedizin und Umweltmedizin (DGAUM) zur Neuauflage der DGUV-Grund-sätze für arbeitsmedizinische Untersuchungen - Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2015)
CRIS-Team Scopus Importer:2020-05-11

Subjective Workload, Job Satisfaction, and Work-Life-Balance of Physicians and Nurses in a Municipal Hospital in a Rural Area Compared to an Urban University Hospital - Koerber, Michael; Schmid, Klaus; Drexler, Hans; Kiesel, Johannes (Gesundheitswesen, 2018)
Medical and nursing shortages in rural areas represent a current serious public health problem. The healthcare of the rural population is at risk. This study compares perceived workload, job satisfaction and work-life balance of physicians and nurses at a clinic in a rural area with two clinics of a University hospital. Physicians and nurses were interviewed anonymously with a standardized questionnaire (paper and pencil), including questions on job satisfaction, subjective workload and work-life balance. The response rate was almost 50% in the University hospital as well as in the municipal hospital. 32 physicians and 54 nurses from the University hospital and 18 physicians and 137 nurses from the municipal hospital participated in the survey. Nurses at the University hospital assessed the organization of the daily routine with 94.1% as better than those at the municipal hospital (82.4%, p=0.03). Physicians at the University hospital were able to better implement acquired knowledge at a University clinic with 87.5% than their counterparts at the municipal hospital (55.5%, p=0.02). In contrast to their colleagues at the municipal hospital, only 50% of the physicians at the University hospital subjectively considered their workload as just right (83.3% municipal, p=0.02). 96.9% of the physicians at the University hospital were "daily" or "several times a week" under time pressure (municipal 50%, p<0.01). Nurses of both hospitals had sufficient opportunity to reconcile work and family life (62.9% University hospital, 72.8% Municipal hospital). In contrast, only 20% of the physicians at the University Hospital but 42.9% of the physicians of the municipal hospital had sufficient opportunities to balance workload and family (p=0.13). The return rate of almost 50% can be described as good. Due to the small number of physicians, especially from the municipal hospital, it can be assumed that some interesting differences could not be detected. There were only slight differences between the nurses from the two hospitals. In contrast, subjective workload and stress factors reported by physicians at the University Hospital were significantly higher than those by doctors at the municipal hospital.
EVALuna2:35489

Subjektive Arbeitsbelastung, Arbeitszufriedenheit, Work-Life-Balance von Ärzten und Pflegekräften eines Kommunalklinikums im ländlichen Raum im Vergleich zu einem groβstädtischen Universitätsklinikum - Körber, Michael; Schmid, Klaus; Drexler, Hans; Kiesel, Johannes (Gesundheitswesen, 2018)
Background Medical and nursing shortages in rural areas represent a current serious public health problem. The healthcare of the rural population is at risk. This study compares perceived workload, job satisfaction and work-life balance of physicians and nurses at a clinic in a rural area with two clinics of a University hospital. Method Physicians and nurses were interviewed anonymously with a standardized questionnaire (paper and pencil), including questions on job satisfaction, subjective workload and work-life balance. Results The response rate was almost 50% in the University hospital as well as in the municipal hospital. 32 physicians and 54 nurses from the University hospital and 18 physicians and 137 nurses from the municipal hospital participated in the survey. Nurses at the University hospital assessed the organization of the daily routine with 94.1% as better than those at the municipal hospital (82.4%, p=0.03). Physicians at the University hospital were able to better implement acquired knowledge at a University clinic with 87.5% than their counterparts at the municipal hospital (55.5%, p=0.02). In contrast to their colleagues at the municipal hospital, only 50% of the physicians at the University hospital subjectively considered their workload as just right (83.3% municipal, p=0.02). 96.9% of the physicians at the University hospital were daily or several times a week under time pressure (municipal 50%, p<0.01). Nurses of both hospitals had sufficient opportunity to reconcile work and family life (62.9% University hospital, 72.8% Municipal hospital). In contrast, only 20% of the physicians at the University Hospital but 42.9% of the physicians of the municipal hospital had sufficient opportunities to balance workload and family (p=0.13). Conclusion The return rate of almost 50% can be described as good. Due to the small number of physicians, especially from the municipal hospital, it can be assumed that some interesting differences could not be detected. There were only slight differences between the nurses from the two hospitals. In contrast, subjective workload and stress factors reported by physicians at the University Hospital were significantly higher than those by doctors at the municipal hospital.
CRIS-Team Scopus Importer:2020-05-11
Keywords: hospital; job satisfaction; nurses; physicians; work-life-balance; working conditions

Suitability of several naphthalene metabolites for their application in biomonitoring studies - Klotz, Katrin; Zobel, Melanie; Schäferhenrich, Anja; Hebisch, Ralph; Drexler, Hans; Göen, Thomas (Toxicology Letters, 2018)
Naphthalene occurs together with polycyclic aromatic hydrocarbons (PAHs) at industrial workplaces and is ubiquitous in the environment. For biological monitoring of naphthalene exposures, up to now mainly 1- and 2-naphthol in urine have been used. Recently, we proposed 1,2-dihydroxynaphthalene (1,2-DHN) and the 1- and 2-naphthylmercapturic acid (1- and 2-NMA) as new urinary biomarkers to characterise a naphthalene exposure. In this study, in a collective of nine occupationally exposed workers handling with creosote the naphthalene metabolites 1,2-DHN, 1- and 2-NMA as well as 1- and 2-naphthol were analysed in order to evaluate the suitability of the different parameters for their application in biomonitoring studies. Additionally, air sampling was conducted to characterise the exposure in task related exposure situations at different workplaces. In the analysed 51 urine samples, 1,2-DHN was the main metabolite with concentrations ranging from 2.3 to 886 μg/g creatinine (crea) (median 34 μg/g crea). For the sum of 1- and 2-naphthol, concentrations in the range of 2.6-174 μg/g crea (median 15 μg/g crea) were observed. 1-NMA concentrations were in the range of < LOD-2.4 μg/g crea (61% > LOD), while 2-NMA was not detected in the analysed urine samples. The biomarkers 1,2-DHN, 1- and 2-naphthol as well as 1-NMA showed significant correlations, which pointed out to naphthalene as the common exposure source. The poor correlations between naphthalene in the air and the biomarkers in urine may be a result of the varying exposure situations and may indicate not solely inhalative, but additional dermal uptake. 1,2-DHN was the most sensitive and, together with 1-NMA, the most specific parameter of the biological monitoring of naphthalene exposure at workplaces. Further studies with this parameter are needed for individuals at different workplaces as well as for persons of the general population without occupational PAH exposure to characterise 1,2-DHN levels as well as to establish their relationship with the naphthalene exposure.
EVALuna2:35248

Sun protection behavior in German outdoor workers: Prevalence and determinants - Diehl, Katharina; Brokmeier, Luisa; Konkel, Tobias; Drexler, Hans; Breitbart, Eckhard W.; Görig, Tatiana (18. Jahrestagung der DGEpi, 2023)

Sun Protection in German Outdoor Workers: Differences by Sex and Job-Related Characteristics - Diehl, Katharina; Brokmeier, Luisa; Konkel, Tobias; Breitbart, Eckhard W.; Drexler, Hans; Görig, Tatiana (Annals of Work Exposures and Health, 2023)
Background Ultraviolet (UV) exposure during outdoor work increases the risk of developing skin cancer. Therefore, the uptake of recommended sun protection behaviors is important to prevent UV-related skin damage in the population of outdoor workers. To develop targeted prevention campaigns, information on the use of sun protection behaviors in different industries is needed. Methods A total of 486 outdoor workers were surveyed on the use of several sun protection measures as part of the 7th wave of the National Cancer Aid Monitoring. Furthermore, details on job-related characteristics, sociodemographics, and skin type were assessed. Descriptive analyses stratified by sex were conducted. Results In general, use of sun protection was insufficient (e.g. 38.4% used sunscreen on the face). Sun protection behavior differed between female and male outdoor workers with females being more likely to use sunscreen and males being more likely to wear sun protective clothes and headgear. For male outdoor workers, we revealed several associations with job-related characteristics. For instance, those who were employed full time were more likely to wear sun protective clothes (e.g. shoulder-covering shirt: 87.1% versus 50.0%, P < 0.001). Discussion We identified deficits in sun protection behavior in outdoor workers and differences by sex- and job-related characteristics. These differences offer starting points for targeted prevention measures. In addition, the findings may inspire qualitative research.
CRIS-Team WoS Importer:2023-03-31

Syncarcinogenesis of natural UV radiation and polycyclic aromatic hydrocarbons in the development of squamous cell carcinomas of the skin? - Weistenhöfer, Wobbeke; Lutz, Regina; Hiller, Julia; Schmitz-Spanke, Simone; Drexler, Hans (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Squamous cell carcinomas (SCC) of the skin can be induced by occupational exposures to polycyclic aromatic hydrocarbons (PAHs), as in tar and soot, or to UV radiation and can be recognized and compensated as occupational diseases. A possible syncarcinogenic effect of these exposures in the development of SCC in humans is under discussion. For the scientific validation of this question, a systematic literature search was conducted using the databases PubMed, Web of Science, and Scopus. Studies on individuals with SCC of the skin and their precursors as well as occupational, non-occupational, or therapeutic exposure to UV radiation and PAHs were selected. In addition, animal studies with exposure to UV radiation and PAHs were evaluated. After screening the abstracts of 510 identified studies, the full texts of 131 studies were reviewed. None of the epidemiological studies provided robust evidence for a syncarcinogenesis of PAHs and UV radiation in the development of SCC of the skin in humans. Nevertheless, as there are indications for a (super-)additive effect of UV radiation and PAH exposure from animal studies and mechanistic investigations, syncarcinogenesis seems possible. However, quantitative dose-response relationships are lacking which would allow comparison of the onset of an adverse effect between the different exposure levels.
CRIS-Team Scopus Importer:2022-09-16

Systemic availability of lipophilic organic UV filters through dermal sunscreen exposure - Hiller, Julia; Klotz, Katrin; Meyer, Sebastian; Uter, Wolfgang; Hof, Kerstin; Greiner, Annette; Göen, Thomas; Drexler, Hans (Environment international, 2019)
Background: Chemical UV filters are common components in sunscreens and cosmetic products and used to protect the skin against harmful effects of sunlight like sunburn. However, the effectiveness of sunscreens in the prevention of skin cancer is in some parts still controversial. Meanwhile, questions about negative effects of the chemical UV filters on human health arise and request an effective risk assessment. Real-life exposure data in humans after application of these products are still rare. Thus, we explored whether and to what extent UV filters are absorbed through the skin into the human body. Material and methods: Plasma and urine samples from 20 healthy volunteers were collected before, during and after a real-life exposure scenario (1st application: 2 mg/cm2; 2nd and 3rd (after 2 and 4 h): 1 mg/cm2 each) using a commercial sunscreen formulation for one day. These samples were analyzed for their content of the currently prominent UV filters octocrylene and avobenzone as well as 2-cyano-3,3-diphenylacrylic acid (CDAA) as the main octocrylene metabolite by using different liquid chromatography electrospray-ionization tandem mass spectrometric procedures. Results: Following dermal sunscreen exposure, avobenzone, octocrylene and CDAA reached concentrations up to 11 μg/L, 25 μg/L and 1352 μg/L in plasma. In urine detection rates of avobenzone and octocrylene were low while CDAA showed a high detection rate and reached up to 5207 μg/g creatinine. Kinetic models could be fitted for octocrylene and CDAA in plasma and CDAA in urine. Concentration peaks were reached between 10 and 16 h after first application and half-life periods were in the range of 1.5 to 2 days. The lipophilic UV filter octocrylene and its metabolite CDAA showed a much slower elimination than other more hydrophilic UV filters. Concordantly, the metabolite CDAA in particular showed a markedly increased renal excretion over the whole sampling period and indicated high internal exposure to OC. Discussion: Real-life sunscreen usage leads to considerable bioavailability of organic UV filters and their metabolites which is rarely seen for other environmental exposures. A combined monitoring of the parent compound and its metabolites is important to fully address internal exposure to the UV filter in humans. Considering the kinetic profiles a prolonged systemic release due to depot formation in skin and a potential accumulation through multi-day exposure is presumed. High in-vivo loads call for a critical toxicological assessment of the UV filters and their metabolites.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Avobenzone; Biomonitoring; Exposure assessment; Octocrylene; Sunscreen; Toxicology; UV filter

Systemic Diseases by Absorption Through the Skin - Drexler, Hans; Kilo, Sonja (Kanerva’s Occupational Dermatology, 2019)

Teledermatologie: Chancen für die Arbeitsmedizin - Weistenhöfer, Wobbeke; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
CRIS-Team Scopus Importer:2020-05-11

Telefonische Sprechstunde am Institut und der Poliklinik für Arbeits-, Sozial- und Umweltmedizin der Friedrich-Alexander-Universität Erlangen-Nürnberg - Geiger, Maximilian; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2022)
Objective: With the spread of the COVID-19 pandemic, the goal was to establish telephone consultations at the Institute and Outpatient Clinic of Occupational, Social, and Environmental Medicine at the Friedrich-Alexander-University of Erlangen-Nürnberg. Methods: After initial contact, the patient’s suitability for a telephone consultation is verified and an outpatient appointment can be explicitly requested. Prior to the consultation, written consent and a referral must be submitted; the submission of additional documents is optional. During the telephone appointment, the data are first compared. If there is any indication of a need for biomonitoring, the samples are usually taken by the referring physician and the analysis is performed in our laboratory. Finally, a doctor’s letter is written. Results: Since March 2020, 139 patients out of 253 referrals have been advised by telephone and 30 on an outpatient basis. Of all telephone consultation cases, 53.2% (n=74) were female. The mean age of patients advised by phone was 51.3 years, the mean duration of the call was 54.3 minutes, and the mean potential travel distance was 69.7 kilometres. A potential 9,688.8 kilometres of travel were thus avoided due to the availability of phone consultations. Biomonitoring was initiated in 23.7% of cases, technical information was submitted in 88.5%, further diagnostics were recommended in 37.4%. A telephone consultation was deemed useful by physicians in 99.3% of cases. Conclusion: Our model of a telephone consultation in the areas of occupational and environmental medicine enabled meaningful and effective patient care including both anamnesis and medical advice.
CRIS-Team Scopus Importer:2024-12-16
Keywords: consultation in occupational and environmental medicine; telemedicine; telephone consultation

The Differentiated Roles of Resilient Behavior and Job Crafting in Interaction with Work Intensity and Their Impact on Employee Health and Performance. - Voss, Amanda Sophie; Soucek, Roman; Moser, Klaus; Drexler, Hans (International Journal of Environmental Research and Public Health, 2025)

The Health Effects of Aluminum Exposure - Klotz, Katrin; Weistenhöfer, Wobbeke; Neff, Frauke; Hartwig, Andrea; Van Thriel, Christoph; Drexler, Hans (Deutsches Ärzteblatt international, 2017)
Aluminum is regularly taken up with the daily diet. It is also used in antiperspirants, as an adjuvant for vaccination, and in desensitization procedures. In this review, we present the scientifically documented harmful effects of aluminum on health and the threshold values associated with them.This review is based on publications retrieved by a selective search of the PubMed and SCOPUS databases on the topic of aluminum in connection with neurotoxicity, Alzheimer's disease, and breast cancer, as well as on the authors' personal experience in occupational and environmental medicine.The reference values for the internal aluminum load (<15 ?g/L in urine, <5 ?g/L in serum) are especially likely to be exceeded in persons with occupational exposure. The biological tolerance value for occupational exposure is 50 ?g of aluminum per gram of creatinine in the urine. For aluminum welders and workers in the aluminum industry, declining performance in neuropsychological tests (attention, learning, memory) has been found only with aluminum concentrations exceeding 100 ?g/g creatinine in the urine; manifest encephalopathy with dementia was not found. Elevated aluminum content has been found in the brains of persons with Alzheimer's disease. It remains unclear whether this is a cause or an effect of the disease. There is conflicting evidence on carcinogenicity. The contention that the use of aluminum-containing antiperspirants promotes breast cancer is not supported by consistent scientific data.The internal aluminum load is measured in terms of the concentration of aluminum in urine and blood. Keeping these concentrations below the tolerance values prevents the development of manifest and subclinical signs of aluminum toxicity. Large-scale epidemiologic studies of the relationship between aluminum-containing antiperspirants and the risk of breast cancer would be desirable.
EVALuna2:9767

The Lifeline at the Scene of an Accident - Wrenger, Nina; Staples, Ronald; Grässel, Elmar; Drexler, Hans; Clarner, Annika (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2015)

The tissue viability imaging system—Suitable method for discovering minimal skin changes in occupational screenings? Results of a cross-sectional field study - Weistenhöfer, Wobbeke; Uter, Wolfgang; Bernet, Franziska; Drexler, Hans (Skin Research and Technology, 2019)
Background: For early detection of initial skin changes in occupational screenings, only few objective assessment systems are available. Objectives: With the aim of assessing an objective measurement method for hand eczema, we trialed the application of the tissue viability imaging (TiVi) system, quantifying erythema non-invasively by polarized light spectroscopy. Materials and Methods: In a field study with 625 employees of a semiconductor production company, 411 were exposed to prolonged wearing of occlusive gloves in the clean room. TiVi system and Hand Eczema Score for Occupational Screenings (HEROS), a quantitative skin score for the hands, were used, supplemented by a standardized personal interview. Results: TiVi values of 65 up to 246 for each hand (palm or back), for each participant summed to overall 289 up to 848 (median 389), were measured. Higher TiVi values were noted for men, smokers, and with increasing age. Correlation between TiVi and HEROS was only weak. Several factors like skin pigmentation, thickness of the skin, or tattoos seem to influence TiVi results. Conclusions: The practical relevance of one-time measurements with the TiVi system in occupational screenings seems to be limited. Specifically, the TiVi system cannot replace dermatological examinations at the workplace. Notwithstanding, the application for other scientific purposes might be useful.
CRIS-Team Scopus Importer:2019-07-23
Keywords: erythema; hand eczema; HEROS; microcirculation; prevention; skin score; TiVi

Thomas Ludwig Diepgen zum 65. Geburtstag - Elsner, Peter; Drexler, Hans (Dermatologie in Beruf und Umwelt, 2018)
CRIS-Team Scopus Importer:2020-05-11

Toxicokinetics of urinary 2-ethylhexyl salicylate and its metabolite 2-ethyl-hydroxyhexyl salicylate in humans after simulating real-life dermal sunscreen exposure - Hiller, Julia; Klotz, Katrin; Meyer, Sebastian; Uter, Wolfgang; Hof, Kerstin; Greiner, Annette; Göen, Thomas; Drexler, Hans (Archives of Toxicology, 2019)
Chemical UV filters are common components in sunscreens and cosmetic products. The question of adverse health risks is not completely resolved, partly owing to lacking human data from dermal exposure, which are essential for sound risk assessment. Therefore, we investigated the urinary toxicokinetics of 2-ethylhexyl salicylate (EHS) after a 1-day dermal real-life sunscreen application scenario. Twenty human volunteers were dermally exposed to a commercial sunscreen for 9 h under real-life conditions (2 mg/cm2 body surface area; double re-application; corresponding to 3.8 g EHS). Urine samples were analyzed for EHS and one of its specific metabolites 2-ethyl-5-hydroxyhexyl salicylate (5OH-EHS) using a two-dimensional liquid chromatographic electrospray–ionization tandem mass spectrometric procedure. EHS and 5OH-EHS were excreted after sunscreen application and reached up to 525 µg/g and 213 µg/g creatinine, respectively. The toxicokinetic models showed concentration peaks between 7 and 8 h after first application. First-phase terminal half-lives were 8–9 h. For 5OH-EHS, a second-phase terminal half-life could be determined (87 h). EHS and 5OH-EHS showed a faster elimination with 70–80% of the overall excretion occurring within 24 h after application compared to more lipophilic UV filters. Cumulative excreted amounts over 24 h reached up to 334 µg EHS and 124 µg of 5OH-EHS. Simulated real-life sunscreen use for 1 day leads to the bioavailability of the UV filter EHS in humans. The kinetic profiles with a prolonged systemic availability indicate a skin depot and make accumulation during consecutive multi-day exposure likely.
CRIS-Team Scopus Importer:2019-09-03
Keywords: 2-Ethylhexyl salicylate; Bioaccumulation; Biomonitoring; Sunscreen; UV filter

Tracing for arsenic exposure - a differentiation of arsenic compounds is essential for the health assessment - Weistenhöfer, Wobbeke; Ochsmann, Elke; Drexler, Hans; Göen, Thomas; Klotz, Katrin (Deutsche Medizinische Wochenschrift, 2016)
Arsenic is ubiquitous and harmful to health in occupation and environment. Arsenic exposure is measured through analysis of arsenic compounds in urine. The identification of several arsenic species is necessary to understand the hazardous potential of the arsenic compounds which differ highly in their toxicity. To estimate the extent of an occupational exposure to arsenic, arsenic species were evaluated for the first time by the working group "Setting of Threshold Limit Values in Biological Material" of the DFG Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area and Biologische Arbeitsstoffreferenzwerte (BAR) of 0.5 ?g / L urine for arsenic (III), 0.5 ?g / L urine for arsenic (V), 2 ?g / L urine for monomethylarsonic acid (MMA) and 10 ?g / L urine for dimethylarsinic acid (DMA) were set. If the reference value for total arsenic is exceeded, a further differentiation of arsenic species now enables to estimate the individual health risks taking into account special influences such as seafood consumption.
EVALuna2:9733

Umweltrisiken und Gesundheitskompetenz: Eine systematische Übersichtsarbeit - Pfleger, Elisabeth; Lutz, Regina; Drexler, Hans (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2023)
Hintergrund Bei der Entstehung von Erkrankungen können Umweltfaktoren eine wesentliche Rolle spielen. Das Verständnis der Beziehung zwischen Umweltrisiken und Gesundheit in der Bevölkerung gestaltet sich jedoch noch schwierig. Ziel der Arbeit ist es, den Stand der Forschung zum Zusammenhang zwischen Gesundheitskompetenz (GK) bzw. umweltbezogener Gesundheitskompetenz (UGK) und Umweltrisiken differenziert nach untersuchten Umweltrisiken, Population, Erhebung und Ausprägung der GK bzw. UGK und deren Interaktion mit anderen Variablen darzustellen. Methoden Es erfolgte eine systematische Literaturrecherche in den Datenbanken Pubmed, Scopus und LIVIVO. Eingeschlossen wurden Originalarbeiten in deutscher oder englischer Sprache, die die GK oder UGK im Kontext von Umweltrisiken oder -schadstoffen an einer Population untersuchen. Die Bewertung der methodischen Studienqualität erfolgte mithilfe des Navigation Guide. Ergebnisse 24 Studien wurden in die qualitative Analyse eingeschlossen. Die Operationalisierung der GK bzw. UGK erfolgte in 22 Studien heterogen. 9 Studien bezogen sich auf Umweltthemen im Allgemeinen und 15 Studien analysierten einzelne Umweltrisiken. 11 Studien bezogen sich auf die allgemeine Bevölkerung, 12 auf spezifizierte Zielgruppen und 1 Studie untersuchte beides. Das Niveau der GK bzw. UGK erwies sich in allen Populationen verbesserungswürdig. Interventionen wie Schulungen konnten die GK bzw. UGK steigern. Diskussion Die heterogenen Operationalisierungen erschweren die Vergleichbarkeit der Studien. Zukünftige Arbeiten sollten die Vereinheitlichung methodischer Aspekte forcieren. Insgesamt zeigt sich, dass Interventionen wie Schulungen zur Verbesserung der GK bzw. UGK förderlich waren. Diese sollten in der Praxis zur Erhöhung der GK bzw. UGK verstärkt in den Fokus gerückt werden.
Keywords: Gesundheitskompetenz; Umweltbezogene Gesundheitskompetenz; Umwelt; Gesundheit; Risikokommunikation

"Und wann kümmern wir uns um den Fahrer?" - Erstbetreuung als Teil der Versorgung bei drohender psychischer Traumatisierung im Fahrdienst: Bedeutung für die arbeitsmedizinische Versorgungspraxis - Clarner, Annika; Wrenger, Nina; Voss, Amanda Sophie; Uter, Wolfgang; Martin, A.; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
Background and objective: Events causing fatalities and serious damage occur in the railway, transportation and regional public transport (OPNV) sector every year. From the perspective of occupational medicine, it is essential to provide adequate care for drivers who are potentially at risk of psychological trauma. A widespread concept of provision is first-response systems in the form of layman- based acute care after accidents at work involving drivers (VBG [German accident insurance provider]). The objective of this paper was a scientific evaluation of these systems. Methodology: Two retrospective cohort studies were conducted with regard to factors influencing length of absence and illness progression among drivers working for two German transport companies in Bavaria and Hesse. Whilst the first study investigated factors influencing post-traumatic stress following first response care, the second cohort study examined the efficacy associated with different forms of first response (collegial, hierarchical or none). The study covered accidents at work between 2003 and 2013. Results: The pilot study covered 59 first response deployments. It was possible to analyse the progression of 259 cases of illness among drivers within the scope of the main study. Accidents in which the casualties were seriously or fatally injured constituted the strongest predictor for drivers. Differences relating to response systems were found in terms of the length of absences when slight damage occurred. There was clear evidence in the control group of an insignificant trend towards a reduction in periods of absence and a significantly low score for the development of post-traumatic stress. Conclusions: When it comes to the form of acute care provision, peer-based systems with an eye to periods of absence may be classed as worth recommending in the case of events causing less serious damage. On the other hand, it is not possible to infer a switchover to the English guideline (NICE) in the sense of "watchful waiting" without first response for Germany in future. The severity of injury is the biggest factor in post-traumatic stress after traumatic events in driving jobs and necessitates binding regulations for damaging events of this kind and accompanying research in the field of occupational medical care.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Accident; Incapacity for work or PTSD; Traffic; Transport; Trauma

Unnecessary Investigations in Environmental Medicine - Greiner, Annette; Drexler, Hans (Deutsches Ärzteblatt international, 2016)
Patients in environmental medicine often want a thorough diagnostic evaluation of nonspecific symptoms. Unconventional testing, as well as conventional testing for indications other than the established ones, can lead to false diagnoses and, in turn, to substantial emotional, social, and financial harm. The goal of this single-center study was to assess inappropriate diagnostic testing among the patients of a specialized university outpatient clinic for environmental medicine.The charts of 653 consecutive outpatients seen in the institute and outpatient clinic of occupational, social, and environmental medicine in Erlangen from 2010 to 2015 were evaluated, and inappropriate diagnostic tests were assessed.9% of the patients had received at least one inappropriate diagnostic test. The most common one was an inappropriate heavy-metal test (26%), followed by an inappropriately ordered hair analysis (15%) and biomonitoring in the blood or urine with an erroneous choice of the testing matrix or an erroneous interpretation of the findings (15%). Biomonitoring performed by us did not confirm the suspected environmental diagnosis in any case. Laboratory values exceeding the normal limits were rarer among these patients than in the patients for whom we considered biomonitoring to be indicated without any pretesting.An appreciable number of patients in environmental medicine were subjected to inappropriate diagnostic testing. When this happens, proper testing often needs to be done thereafter in order to confirm or refute the findings. This phenomenon should be more thoroughly assessed and quantified.
EVALuna2:9755

Unterstützung des BGM in KMU durch Netzwerke innerhalb eines Forschungsprojekts – Evaluation des Projekts RegioKMUnet - Voss, Amanda Sophie; Fischmann, Wolfgang; Lösch, Regina; Böhm, Katja; Wischlitzki, Elisabeth; Amler, Nadja; Drexler, Hans (60. Wissenschaftliche Jahrestagung der DGAUM, 2020)
Keywords: RegioKMUnet; Netzwerke; BGM

UV-irradiation-induced skin cancer as a new occupational disease - Diepgen, T. L.; Drexler, Hans; Elsner, P.; Schmitt, J. (Hautarzt, 2015)
With the revision of the German Ordinance on Occupational Diseases, skin cancer due to UV irradiation was amended as a new occupational disease to the list of occupational diseases in Germany. The new occupational disease BK 5103 has the following wording: "Squamous cell carcinoma or multiple actinic keratosis of the skin caused by natural UV irradiation". Actinic keratoses are to be considered as multiple according to this new occupational diseases if they occur as single lesions of more than five annually, or are confluent in an area > 4 cm(2) (field cancerization). It is estimated that more than 2.5 million employees are exposed to natural UV irradiation due to their work (outdoor workers) in Germany and therefore have an increased risk of skin cancer. In this article the medical and technical prerequisites which have to be fulfilled for this new occupational disease in Germany are introduced.
EVALuna2:9726

Vaccination Gaps of Employees in Institutions of Preschool Childcare before Introduction of the Measles Protection Act - Goertz, Ruediger Stephan; Gherman, Elsa; Wentzlaff, Holger; Drexler, Hans; Wolfschmidt, Anna (Gesundheitswesen, 2022)
Aim of the study The measles protection act and the updated recommendations of the permanent commission of vaccination (STIKO) include the obligatory proof of a double vaccination against measles for employees (born after 1970) in childcare. In addition, the standard and professional recommendations for vaccinations should be respected. A retrolective evaluation of vaccination gaps of employees in institutions for preschool childcare was performed. Methods The database of 2018 and 2019 of the B center dot A center dot D-Health center Erlangen have 1300 recorded cases of occupational medical consultations in preschool childcare. Double consultations and consultations with insufficient data were excluded. 1016 contacts were analyzed with regard to vaccination gaps of measles, mumps, rubella, varicella, pertussis, hepatitis A+B and early summer meningoencephalitis. The evaluation was primarily based on the employees' vaccination cards. Vaccination gaps were assumed in case of missing, commenced or incomplete vaccination protection. Results In this cohort of 1016 employees, the vaccination gap for measles increased from 16.2% to 20.6%, when applying the updated STIKO recommendation and the resulting change of definition of complete vaccination protection from measles. Further gaps were 22.7% for mumps, 18.9% for rubella, 2.3% for varicella, 27.8% for pertussis, 61.1% for hepatitis A and 60.5% and tick-borne encephalitis. The age group Conclusion The evaluation of the health center in Erlangen showed considerable age-dependent vaccination gaps in the cohort of employees of preschool childcare. The measles protection act that makes vaccination against measles mandatory contributes to closing this gap. There is room for counselling as well as for action regarding vaccine-preventable diseases in occupational medicine.
CRIS-Team WoS Importer:2022-07-15

Validity of different biomonitoring parameters for the assessment of occupational exposure to N,N-dimethylformamide (DMF) - Seitz, Mirjam; Kilo, Sonja; Eckert, Elisabeth; Mueller, Johannes; Drexler, Hans; Göen, Thomas (Archives of Toxicology, 2018)
This study was performed to assess the relation between occupational exposure to N,N-dimethylformamide after an 8 h work shift in the acrylic fibre industry and its three biological markers N-methylformamide (NMFtotal), N-acetyl-S-(N-methylcarbamoyl)cysteine (AMCC), and N-methylcarbamoyl adduct at haemoglobin (MCVal). External DMF exposure of 220 workers was determined during the whole shift. A standardised questionnaire was used to obtain information about the worker's general health status, medical treatment, smoking habits, protective measures, and possible symptoms caused by DMF exposure. NMF and AMCC were analysed in post-shift urine samples and MCVal in blood. For longitudinal assessment the average AMCC concentration was determined over a period of 4 weeks (weekly sampling) in a sub-collective of 89 workers. The median of DMF concentration in air was 3.19 mg/m3 (range < 0.15-46.9 mg/m3). The biological markers showed a median of 4.80 mg/L (range 0.20-50.6 mg/L) for NMFtotal, 4.75 mg/g creatinine (range 0.06-49.6 mg/g creatinine) for AMCC, and 57.5 nmol/g globin (range 0.5-414 nmol/g) for MCVal. A significant linear relationship was observed between DMF in air and NMF as well as between DMF in air and AMCC in post-shift urine samples. The mean AMCC values measured weekly over a period of 4 weeks correlated significantly with MCVal adducts too. Excluding workers who had been using breathing masks on the day of the study led to even tighter correlations. The results of the present study demonstrate the applicability of the DMF biomonitoring parameters NMFtotal in post-shift urine for the present-day exposure assessment, AMCC in the post-shift urine after several shifts for assessment of the cumulative exposure of the previous working days, and MCVal for assessment of long-term exposure during previous weeks and months. The data of the present study enable now the estimation of valid equivalents of these biomonitoring parameters to the external DMF exposure. From the risk assessment point of view, the exposure limit values for AMCC and MCVal, which are directly linked to the presumed toxic intermediate MIC, exhibit a significant advance.
EVALuna2:34674

Validity of different biomonitoring parameters in human urine for the assessment of occupational exposure to naphthalene - Klotz, Katrin; Weiß, Tobias; Zobel, Melanie; Bury, Daniel; Breuer, Dietmar; Werner, Silke; Sucker, Kirsten; Zschiesche, Wolfgang; Göen, Thomas; Brüning, Thomas; Drexler, Hans (Archives of Toxicology, 2019)
Up to date, information on the validity of human biomonitoring (HBM) parameters of naphthalene exposure is poor. This study was performed to reveal the relation between occupational exposure to naphthalene and biological exposure markers. Therefore, ten lowly and highly exposed workers from the abrasives industry were selected to characterise a broad exposure range. Naphthalene in air was determined by personal air monitoring during one shift. For biological monitoring, pre- and post-shift urine samples collected on 2 days of a working week were analysed for 1,2-dihydroxynaphthalene (1,2-DHN), 1- and 2-naphthol, 1- and 2-naphthylmercapturic acid (NMA). The naphthalene concentration in air was in the range of 0.5 to 11.6 mg/m3. The biomarkers in urine showed post-shift concentration in the range of 114–51,809 µg/L for 1,2-DHN, 0.8–666 µg/L for 1–NMA, 2–2698 µg/L for 1-naphthol and 4–1135 µg/L for 2-naphthol, respectively. 2-NMA was not detected. The urinary levels increased significantly from pre- to post-shift for all analysed parameters and an accumulation over the working week was observed. Significant positive correlations were observed between 1,2-DHN, 1-NMA, 1- and 2-naphthol in post-shift urine samples and personal exposure to naphthalene in the air. 1-NMA and 1,2-DHN, 1- and 2-naphthol have been demonstrated as suitable biomarkers for naphthalene exposure monitoring. Of the determined biomarkers, 1,2-DHN is by far the metabolite with the highest concentration in the urine samples.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Biomonitoring; Dihydroxynaphthalene; Mercapturic acid; Naphthalene; Naphthol; Urine

Verhältnisprävention von Hautkrebs am Arbeitsplatz – Ergebnisse einer bundesweiten Befragung von Außenbeschäftigten - Görig, Tatiana; Breitbart, Eckhard W.; Drexler, Hans; Diehl, Katharina (33. Deutscher Hautkrebskongress, 2023)

Vierzehn Thesen zum Stand und zum Entwicklungsbedarf der betrieblichen Prävention und Gesundheitsförderung - Letzel, Stephan; Nesseler, Thomas; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2016)
CRIS-Team Scopus Importer:2020-05-11

Welche Berufsgruppen an einem Klinikum sind besonders beansprucht?: Ein Vergleich mit anderen Branchen - Schmid, Klaus; Drexler, Hans; Fischmann, Wolfgang; Uter, Wolfgang; Kiesel, Johannes (Deutsche Medizinische Wochenschrift, 2011)
Background and objective: Increasing workload in health professionals and resulting health consequences have frequently been reported. We analysed the results from an employee attitude survey within a network of workplace health promotion and compared three occupational groups of a university hospital with two samples of employees of other industries.Method: The survey was conducted in the years 2005, 2006 and 2007 using a standardized method, addressing 1748 employees of six companies. In order to compare specific occupational groups, both within the hospital and amongst different companies, five occupational groups were selected (medical profession, nursing service and administration of the hospital, academics of another company and employees of a financial service provider).Results: Some results were specific for an occupational group, such as lower back pain and skin diseases in nurses and exhaustion in clinicians. Regarding several items the responses of employees of the hospital's administration were similar to that of the medical professionals and differed significantly from the responses of administrative and related employees in other companies. Employees of all occupational groups of the hospital were often frustrated and felt their work was not appreciated. Frequent demands included improved work atmosphere, better appreciation of work and better information regarding innovations.Conclusions: The analysis of standardized survey results specific for companies and occupational groups is an appropriate way to identify targets of health promotion. Constant over three surveys, again a high burden of stress was found in health care workers even affecting the administrative staff, regarding several work-related stress factors. According to our results activities to improve the working conditions in hospitals are urgently needed.
Keywords: physical stress; professional categories; mental stress; nursing; administration; comparison of companies; clinicians; job satisfaction; hospital

Weltkongress zum Biomonitoring mit starker deutscher Beteiligung - Drexler, Hans; Göen, Thomas; Schmitz-Spanke, Simone; Klotz, Katrin; Pink, Mario (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
CRIS-Team Scopus Importer:2020-05-11

Wenn Lehrkräfte ihren eigenen Ansprüchen nicht genügen können – Gesundheitszustand und gesundheitliche Beschwerden - Wischlitzki, Elisabeth; Fischmann, Wolfgang; Drexler, Hans (60. Wissenschaftliche Jahrestagung der DGAUM, 2020)
Einleitung Im Rahmen der Lehrergesundheit wurden gesundheitliche Beschwerden bereits beleuchtet. Schlüssig ist jedoch bisher nicht, welche Rolle Selbstkonzepte der Lehrkräfte im Detail spielen. Ziel dieser Forschung ist daher, den Gesundheitszustand sowie gesundheitliche Beschwerden im Hinblick auf die Aussage, den eigenen Ansprüchen genügen zu können, zu untersuchen. Methoden In 13 Schulen wurde im Zuge einer GB-Psych eine schriftliche Fragebogenerhebung durchgeführt. Es wurden dabei Belastungen, Beanspruchung und der Gesundheitszustand erhoben. Das Item „Können Sie den eigenen Ansprüchen an Ihre Arbeit unter den gegebenen Bedingungen genügen?“ wurde 4-stufig abgefragt: immer, meistens, selten, nie. Zur Auswertung der Daten erfolgte eine Dichotomisierung. Chi² Tests wurden mit 45 Items zu Soziodemographie, Belastung, Beanspruchung und dem Gesundheitszustand durchgeführt. Ergebnisse Die Stichprobe umfasst n=359 Lehrkräfte (Rücklauf 45%). Ein Viertel der Befragten kann selten oder nie seinen eigenen Ansprüchen genügen. Dabei zeigen sich keine signifikanten Unterschiede bzgl. soziodemographischer Merkmale. Es wird jedoch deutlich, dass ein schlechterer Gesundheitszustand (p<0,001), häufigeres Auftreten körperlicher und psychischer Beschwerden (z.B. Schlafstörungen p<0,001) sowie ein höheres Maß an emotionaler Erschöpfung (p<0,001) mit der Einschätzung einhergehen, den eigenen Ansprüchen nicht genügen zu können. Bzgl. der Arbeitsbedingungen stufen diese Lehrkräfte die pädagogisch-didaktischen Anforderungen sowie Anforderungen im Rahmen der Vermittlung von Sozialkompetenzen seltener als „gerade richtig“ ein (je p<0,001). Diskussion Komplexe Ursache-Wirkungs-Beziehungen müssen hier diskutiert werden, da die Einflussgrößen sich wechselseitig bedingen. So kommen sowohl das Selbstkonzept der Lehrkräfte, als auch die Arbeitsbedingungen oder der vorherrschende Gesundheitszustand jeweils als Auslöser und als Mediator in Betracht. Schlussfolgerung Den eigenen Ansprüchen nicht genügen zu können, geht mit einer schlechteren gesundheitlichen Situation der Betroffenen einher. Weitere Forschung zu Zusammenhängen ist notwendig, um Auswirkungen von Selbstkonzepten der Lehrkräfte auf ihre gesundheitliche Situation sowie die Rolle der beruflichen Rahmenbedingungen einschätzen zu können. Betriebsärzte und weitere Ansprechpartner für Lehrkräfte sowie Schulleitungen sollten dennoch sensibel für eine mögliche erhöhte Anspruchshaltung der Lehrkräfte sein und ggf. hierauf eingehe

We should pull together rather than perpetuating conflict - Drexler, Hans (MMW Fortschritte der Medizin, 2015)
EVALuna2:9747

Wird es zukünftig noch DGUV-Grundsätze geben? - Kluckert, Matthias; Brüning, Thomas; Nowak, Dennis; Letzel, Stephan; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2016)
CRIS-Team Scopus Importer:2020-05-11

"Working healthily in Thuringia": Interface between prevention and cure - Results of the survey of Thuringian doctors within the framework of the model project in accordance with §20 g of the Social Code Book V „Gesund arbeiten in Thüringen“ - Sedlaczek, Sabine; Quittkat, Christine; Amler, Nadja; Nesseler, Thomas; Rieger, Monika A.; Drexler, Hans; Letzel, Stephan (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2018)
CRIS-Team Scopus Importer:2020-05-11

Work-related bladder cancer -The BK 1301 matrix as an algorithm and decision aid in the context of an assessment of an occupational disease Das beruflich bedingte Harnblasenkarzinom-Die BK 1301-Matrix als Algorithmus und Entscheidungshilfe fur eine Zusammenhangsbegutachtung - Weistenhöfer, Wobbeke; Golka, K.; Bolm-Audorff, U.; Bolt, H. M.; Bruning, T.; Hallier, E.; Pallapies, D.; Prager, H. M.; Schilling, Teresa; Schmitz-Spanke, Simone; Uter, Wolfgang; Weis, T.; et al. (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2022)
The risk of developing bladder cancer can be influenced by various occupational and non-occupational risk factors. These need to be evaluated in the context of an assessment of an occupational disease according to no. 1301 (BK 1301: Mucosal changes, cancer and other neoplasms of the urinary tract (hereinafter referred to as "bladder cancer") caused by aromatic amines) of the Annex to the Ordinance on Occupational Diseases. The BK 1301 matrix presented here for the assessment of the causal relationship in urinary bladder cancers after proven and relevant occupational exposure to carcinogenic aromatic amines was derived as a convention by a working group, based on the results of a workshop with more than 230 participants. It can be applied even in the absence of an individual cumulative exposure dose. The decision matrix is intended to support experts experienced in occupational medicine in the field of BK 1301 in the assessment procedure. It also provides an overview of relevant aspects of work-related bladder cancer for the purposes of accident insurance institutions and courts. The BK 1301 matrix includes occupational indicators such as exposure duration, exposure frequency and exposure intensity, as well as the age of onset, the latency period and competing non-occupational risk factors such as smoking behaviour. Based on the BK 1301 matrix, the relevant arguments favouring or refuting a causal occupational relationship in the individual case can be evaluated in detail by the occupational physician, resulting in a recommendation for or against recognition of the bladder cancer as an occupational disease. This notwithstanding, the decision as to whether an occupational disease is indeed present is ultimately an administrative act of the responsible accident insurance institution, which may be subject to review by the social courts.
CRIS-Team Scopus Importer:2022-05-06
Keywords: aromatic amines; bladder cancer; convention; expert opinion; matrix; occupational disease 1301

Work-related posttraumatic stress disorder (PTSD) and other emotional diseases as consequence of traumatic events in public transportation: a systematic review - Clarner, Annika; Grässel, Elmar; Scholz, Johanna; Niedermeier, Alexander; Uter, Wolfgang; Drexler, Hans (International Archives of Occupational and Environmental Health, 2015)
Drivers in public transportation are at risk of experiencing potential traumatic events such as accidents involving persons, collisions, or suicides. In this context, the question arises to what extent psychological traumatization and posttraumatic diseases occur.The aim of this systematic review was to describe the frequency and nature of work-related posttraumatic disorders, to analyze risk and prognostic factors after potentially traumatic events (accidents resulting in damage to property and/or in injury or death), and address sick leave after such events in the realm of public transportation, based on the available literature.Systematic review based on four databases (PubMed, PSYNDEX/MEDLINE, ScienceDirect, PILOTS) between 1980 and June 2013.We identified seven studies (four longitudinal, three cross-sectional) that examine employees after person under train (PUT) events. PTSD prevalences varied broadly between 0.7 and 17 %. The same applies to dysthymia/neurotic depression (1-26 %). However, similarly low prevalences of major depression (1.3-2.8 %) and panic disorder (0.5-1.3 %) have been observed. Risk factors of PTSD comprised individual, work-related, event-related, and prognostic aspects. Following the traumatic event, a total of 69-81 % of the drivers were absent, and if sick leave occurs, this was on average 3-19 days.It became evident that drivers in public transportation run a high risk of sick leave. It was also striking that despite the immense impact of PUT and high number of suicides, only an infinitesimal number of studies exists. Due to various differences (period of follow-up, instrument of measurement and study period), it turned out that the comparability of the results of the studies is limited. For various reasons, further research is urgently needed, as from an occupational health point of view the issue of posttraumatic diseases and implications for fitness for service should be addressed.
EVALuna2:5463

Workshop „Ultrafeine Partikel“ - Pfleger, Elisabeth; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2020)

Zufriedenheit am Arbeitsplatz – Welcher Zusammenhang besteht zur Beurteilung von Vorgesetzten und Kollegen? - Fischmann, Wolfgang; Voss, Amanda Sophie; Lösch, Regina; Drexler, Hans (60. Wissenschaftliche Jahrestagung der DGAUM, 2020)

Zwei Seiten einer Medaille: Schüler als Belastungsfaktor oder Quelle der Wertschätzung? - Wischlitzki, Elisabeth; Fischmann, Wolfgang; Drexler, Hans (59. Wissenschaftlichen Jahrestagung der Deutschen Gesellschaft für Arbeitsmedizin und Umweltmedizin (DGAUM), 2019)

Zwischenbilanz BayUFP. Koordination und Kommunikation im UFP-Projektverbund - Pfleger, Elisabeth; Adrian, Christoph; Drexler, Hans; Zeh, Reimar (62. Jahrestagung der Deutschen Gesellschaft für Arbeitsmedizin und Umweltmedizin e.V., 2022)